Composite, related systems and articles, and methods of making and using
By using mild reagents to depolymerize waste PET under low temperature and low pressure conditions, nanostructured terephthalic acid is generated, which solves the problems of PET recycling and treatment in the prior art, and achieves an efficient, safe and economical plastic depolymerization effect.
Patent Information
- Application Number
- CN202380041376.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-18
- Filing Date
- 2023-05-19
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to efficiently recycle and dispose of discarded polyethylene terephthalate (PET) plastics, and traditional decomposition methods usually require high temperature, high pressure and harmful chemicals.
Additional isolation and purification steps are avoided by depolymerizing waste PET into nanostructured terephthalic acid (TPA) and related compounds under low temperature and low pressure conditions by using relatively mild reagents such as tin chloride, lithium chloride and potassium chloride, and depolymerization of waste PET into nanostructured terephthalic acid (TPA) and related compounds under low temperature and low pressure conditions. .
It realizes efficient depolymerization of PET under safe, simple and economical conditions, and generates nanostructured terephthalic acid, which has improved scalability and low environmental hazards.
Smart Images

Figure CN119487112A_ABST
Abstract
Description
[0001] Cross-references to related applications
[0002] This application claims the benefit of the following U.S. patent applications: USSN 63 / 344,349, filed May 20, 2022, entitled "Methods for producing nanostructured materials"; USSN 63 / 398,459, filed August 16, 2022, entitled "Complexes comprising organic compounds and crystalline metal oxides and methods of making the same"; and USSN 63 / 439,688, filed January 18, 2023, entitled "Methods for converting waste plastics into nanostructured monomers and related compounds". The entire disclosures of these applications are incorporated herein by reference. Field of the Invention
[0003] The present invention relates to various composites, related systems and articles, and methods of making and using the same. The present invention relates to composites containing nanostructured organic compounds, composites containing organic compounds and metal organic frameworks embedded in organic compounds, and composites containing partially crystalline organic compounds and crystalline metal oxides distributed in organic compounds, as well as related methods of making (e.g., methods of polymer depolymerization), methods of using (e.g., energy storage, pollutant removal), articles (e.g., electrodes) and systems (e.g., energy storage systems, systems containing these energy storage systems). In certain aspects, the present invention relates to composites containing silicon-containing materials and polymers composed of imide monomers, as well as related systems and articles, and methods of making and using the same. Background Art
[0004] A large amount of plastic is produced and consumed worldwide each year. For example, it is reported that approximately 30 million tons of polyethylene terephthalate ("PET") are consumed each year for the preparation of various products, such as approximately 400 billion beverage bottles. Typically, such products are discarded after a single use due to the lack of relatively simple and effective recycling methods. This leads to pollution of terrestrial and aquatic environments.
[0005] Existing chemical methods for breaking down waste PET into its monomers typically involve high-temperature pressurized containers and concentrated acid or alkaline solutions. In addition, PET recovery methods include the use of enzymes, which may require longer processing times due to their slow process kinetics. In many cases, existing polymer recovery methods also produce mixtures of different monomers, which require additional steps for separation and purification. SUMMARY OF THE INVENTION
[0006] The present invention can be applied to reduce the amount of waste plastic materials while providing methods, articles and systems related to energy storage.
[0007] The present invention relates to various composites, related systems and articles, and methods of making and using the same. In certain aspects, the disclosure relates to composites containing nanostructured organic compounds, composites containing organic compounds and metal organic frameworks embedded in the organic compounds, and composites containing partially crystalline organic compounds and crystalline metal oxides distributed in the organic compounds, and related methods of making, methods of using, articles (e.g., electrodes) and systems (e.g., energy storage systems, systems containing these energy storage systems). In certain aspects, the disclosed features include composites of silicon-containing materials and polymers composed of imide monomers, and related systems and articles, and methods of making and using the same.
[0008] The composites, articles and / or systems included in the present invention may exhibit one or more beneficial properties. For example, in certain embodiments, an electrode including a composite according to the disclosure may have a higher volume conductivity, metal ion storage capacity, coulombic efficiency and / or metal ion diffusion rate than certain other energy storage materials, articles and / or systems.
[0009] In a supplementary case, in certain embodiments, an electrode comprising a composite according to the disclosure may have a lower resistance at the interface between the electrode and the electrolyte and / or a lower Warburg coefficient compared to certain other energy storage materials, articles and / or systems. In addition, in certain embodiments, these composites may be relatively cheap and / or have lower environmental hazards compared to certain other energy storage materials, articles and / or systems. Further, in certain embodiments, the electrochemical performance problems associated with other types of battery negative electrode materials, energy storage materials, articles and / or systems (e.g., electrode pulverization due to large volume changes) can be avoided according to the disclosed technology. In certain embodiments, electrodes made using these composites can maintain stable performance without degradation over hundreds of cycles (e.g., there is almost no decay in maximum capacity). In some embodiments, electrodes and batteries comprising composites according to the disclosure may have a relatively high energy density and are safer than certain other electrodes and batteries. In certain embodiments, the voltage for inserting or extracting metal ions (such as lithium ions, sodium ions or potassium ions) from a negative electrode comprising the composite is less than 1V, and relative to metal / metal ions (such as Li + / Li、Na + / Na and K + The voltage feature can prevent metal deposition on the negative electrode of the energy storage device, thereby improving safety and enabling these devices to have relatively higher energy density than other energy storage devices.
[0010] In certain embodiments, the composites can be applied to wastewater treatment to reduce the concentration of organic pollutants in water by adsorption and / or photocatalytic degradation.
[0011] In certain embodiments, the disclosed method can decompose (e.g., depolymerize) waste plastics (e.g., polyethylene terephthalate (PET) from plastic water bottles) into monomers (e.g., terephthalic acid). In certain embodiments, the depolymerization of waste plastics is carried out without the use of dangerous (e.g., acidic or alkaline) chemicals, high pressure, high temperature, and / or long-term treatment of catalysts and / or reducing agents. On the contrary, in certain implementation cases, the disclosed method allows the use of relatively mild reagents (e.g., tin chloride (SnCl2), zinc chloride (ZnCl2), lithium chloride (LiCl) and / or potassium chloride (KCl)), relatively low temperatures, relatively low pressures (e.g., atmospheric pressure), relatively short processing times, and without the use of acids, bases, and / or enzymes. Therefore, in certain embodiments, the method can depolymerize waste plastics in a relatively safe, simple, cheap, and fast manner, while providing improved scalability, relatively easy separation of monomers and related compounds, without the need for additional separation and purification steps, and lower costs compared to certain other depolymerization methods. In certain embodiments, the disclosed methods can produce products that are relatively easy to produce and purify (e.g., without requiring a purification step). For example, in certain embodiments, the disclosed methods can produce a mixture containing a first organic compound and a second organic compound that can be relatively easily separated from the mixture (e.g., by evaporation). Thus, in certain embodiments, the disclosed methods can decompose PET into nanostructured terephthalic acid (TPA) at standard atmospheric pressure without the presence of other monomers, such as ethylene glycol.
[0012] In certain embodiments, the present methods can depolymerize plastics into nanostructured and / or nanocrystalline monomers and related compounds that are morphologically and / or structurally different from certain other materials (e.g., commercial terephthalic acid, which does not possess nanostructures and / or nanocrystals).
[0013] In certain embodiments, the disclosed methods may consume (e.g., depolymerize) waste plastics (e.g., polyethylene terephthalate (PET) from plastic water bottles) to produce the disclosed mixtures. In certain embodiments, the methods do not involve the use of environmentally harmful and / or expensive chemicals, which are commonly used in some cases to make battery negative electrode materials. Instead, in certain embodiments, the disclosed methods may use relatively inexpensive, abundant, and safe reagents with little or no carcinogenicity and / or genotoxicity (e.g., tin chloride (SnCl2), lithium chloride (LiCl), potassium chloride (KCl)). In certain embodiments, the conversion of tin chloride (SnCl2) into tin oxide (SnO2) in certain disclosed methods may result in the release of chlorine gas. The generated chlorine gas can be used in one or more industrial applications (e.g., drinking water treatment).
[0014] In certain embodiments, the disclosed methods can produce mixtures of nanostructured organic compounds (e.g., terephthalic acid). In certain embodiments, the compounds produced by the disclosed methods can have a dark (e.g., black) appearance due to unique light-matter interactions with nanostructured organic compounds (e.g., nanostructured terephthalic acid), which are not present in other (i.e., non-nanostructured) organic compounds.
[0015] In certain embodiments, the disclosed methods can be used to separate plastic mixtures by selectively depolymerizing some of the plastic components in the mixed plastics. For example, these methods can decompose depolymerizable polymers (e.g., PET) while not depolymerizing non-depolymerizable plastics (e.g., high-density polyethylene (HDPE)) in the mixture, thereby achieving separation of depolymerizable polymers and non-depolymerizable polymers.
[0016] In certain embodiments, the disclosed mixtures exhibit faster reaction kinetics relative to other organic compounds (e.g., commercial terephthalic acid without nanostructures and / or nanocrystals). Based on this, the disclosed mixtures can be used to prepare materials such as disodium terephthalate (Na2TP, Na2C8H4O4) and dilithium terephthalate (Li2TP, Na2C8H4O4), as electrodes for sodium ion and lithium ion batteries, respectively, polymers such as poly(succinate-terephthalate) (PBAT) and PET, and / or photosensitive nanoparticles, relative to other sources of terephthalic acid.
[0017] In certain embodiments, the disclosed methods can allow for the depolymerization of waste PET into pure nanostructured terephthalic acid (TPA) at atmospheric pressure without the production of other types of monomers such as ethylene glycol.
[0018] Commercial terephthalic acid (TPA) has been extensively applied in many fields, including the detection of hydroxyl radicals in solution, the preparation of 2-hydroxyterephthalic acid for biomedical cancer therapy and water treatment, the preparation of metal organic frameworks and photosensitive nanoparticles for biomedical imaging, the preparation of various polymers such as poly(succinate-terephthalate) (PBAT) and PET, and the preparation of electrode materials for metal ion batteries. For example, disodium terephthalate (Na2TP, Na2C8H4O4) and dilithium terephthalate (Li2TP, Na2C8H4O4) are used as electrode materials for sodium ion and lithium ion batteries, respectively.
[0019] In certain embodiments, the disclosed content not only provides a relatively simple, fast and sustainable method for depolymerizing PET into TPA, but also provides a method for preparing nanostructured TPA. Nanostructured TPA is different from commercial TPA and has unique microscopic morphological characteristics, which makes TPA materials applicable to various scenarios and improves the kinetics of these processes. Replacing commercial TPA with nanostructured TPA in the production process of various materials has a relatively fast, simple and efficient reaction, thereby obtaining economic and / or technical advantages. Therefore, greenhouse gas emissions in the production of TPA raw materials are reduced.
[0020] In certain embodiments, the disclosed methods can depolymerize plastics into nanostructured and / or nanocrystalline monomers and related compounds and composite materials, which have a variety of possible applications for new and / or known applications. These applications may include: preparing electrode materials and / or electrolyte materials and / or other functional components and / or structural components for energy generation and storage devices; preparing reagents for purifying water; serving as templates for preparing other nanostructured materials, which can be used for energy / environmental protection / biomedical and / or structural materials; preparing composite materials with enhanced mechanical and / or physical properties.
[0021] In certain embodiments, the disclosed methods can provide relatively simple and rapid depolymerization of PET into two or more types of monomers, wherein one monomer (e.g., TPA) is a condensed compound during the process, while the other monomers are in the gas phase and leave the reactor during the reaction. This can reduce (if not completely avoid) the subsequent purification steps of mixed monomer separation commonly used in current chemical depolymerization technology. Therefore, in certain embodiments, the disclosed methods can reduce the economic cost and process complexity of monomer synthesis.
[0022] In certain embodiments, relatively low-cost and relatively readily available materials are disclosed that can be applied to sustainable development of current and future emerging technologies, such as green energy production / storage and composite materials.
[0023] In one aspect, a mixture is disclosed, comprising: a nanostructured organic compound, comprising a plurality of molecules having a chemical formula of C x O y H z , where: x ranges from 2 to 12; y ranges from 2 to 8; z ranges from 2 to 14
[0024] In one aspect, a mixture is provided, comprising: an organic compound; and a metal-organic framework embedded in the organic compound.
[0025] In one aspect, a mixture is provided, comprising: an organic compound; and a crystalline metal oxide, wherein the organic compound is at least partially crystalline and the metal oxide crystals are distributed in the organic compound.
[0026] In one aspect, a composite is provided, comprising: a material containing silicon; and a polymer made of imide monomers, wherein part of the imide monomers are in a cross-linked form, and part of the material and part of the polymer are bonded to each other through hydrogen bonds.
[0027] In one aspect, a mixture is provided, comprising: a polymer; and an organic compound, comprising a plurality of molecules having a chemical formula of C x O y H z , wherein: the organic compound is in crystalline form; x ranges from 2 to 12; y ranges from 2 to 8; and z ranges from 2 to 14.
[0028] In some embodiments, the organic compound is a nanocrystal.
[0029] In some embodiments, the composite has a grain size ranging from 1 nm to 100 nm.
[0030] In some embodiments, the composite has a grain size ranging from 20 nm to 80 nm.
[0031] In some embodiments, the composite has a grain size ranging from 30 nm to 70 nm.
[0032] In some embodiments, the components of the composite are less than 100 nm in at least one dimension.
[0033] In some embodiments, the components of the composite are smaller than 50 nm in at least one dimension.
[0034] In some embodiments, the components of the composite are smaller than 10 nm in at least one dimension.
[0035] In some embodiments, the nanostructured organic compound has at least one dimension less than 2 nm.
[0036] In some embodiments, the mixture further comprises at least one selected from the group consisting of metal oxides, metals, metal organic frameworks, silicon-containing materials, and graphene-containing materials embedded in the nanostructured organic compound.
[0037] In some embodiments, the mixture further comprises a crystalline metal oxide embedded within the nanostructured organic compound.
[0038] In some embodiments, the X-ray diffraction test results of the mixture have diffraction (XRD) peaks. In some embodiments, the 2θ (± 0.2 degrees) value of the XRD spectrum of the composite includes at least one selected from 16.99 degrees, 24.83 degrees and 27.54 degrees. In some embodiments, the XRD spectrum of the composite includes at least two peaks (2θ, ± 0.2 degrees), selected from 16.99 degrees, 24.83 degrees and 27.54 degrees. In some embodiments, the 2θ (± 0.2 degrees) value of the XRD spectrum of the composite includes 16.99 degrees, 24.83 degrees and 27.54 degrees. In some embodiments, the composite has an XRD spectrum with characteristic peaks, such as Fig.36 As shown in d.
[0039] In some embodiments, the metal oxide crystals are uniformly distributed within the organic compound.
[0040] In some embodiments: there is a first concentration of crystalline metal oxide in the interior region of the mixture; in the surface region of the mixture, the mixture has a second concentration of crystalline metal oxide; and / or the first concentration is greater than the second concentration. In some embodiments, the first concentration in the interior region of the mixture ranges from 1wt.% to 95wt.%. In some embodiments, the first concentration in the interior region of the mixture ranges from 5wt.% to 80wt.%. In some embodiments, the first concentration in the interior region of the mixture ranges from 10wt.% to 70wt.%. In some embodiments, the second concentration in the surface region of the mixture ranges from 0.1wt.% to 80wt.%. In some embodiments, the second concentration in the surface region of the mixture ranges from 1wt.% to 70wt.%. In some embodiments, the second concentration in the surface region of the mixture ranges from 5wt.% to 60wt.%.
[0041] In some embodiments, the organic compound and the crystalline metal oxide are bonded via hydrogen bonding.
[0042] In some embodiments, the mixture includes nanoparticles having a size between 1 nm and 200 nm.
[0043] In some embodiments, the mixture includes nanoparticles having a size between 1 nm and 100 nm, such as 0.01 μm and 100 μm.
[0044] In some embodiments, the mixture has a particle size of 10 μm to 100 μm, such as particles of 1 nm to 200 nm.
[0045] In some embodiments, the particles include plate-like particles having a size of 1 nm to 1 μm, such as 10 nm to 500 nm.
[0046] In some embodiments, the organic compound includes an amorphous phase.
[0047] In some embodiments, a portion of the organic compound is a crystalline structure.
[0048] In some embodiments, the organic compound is crystalline.
[0049] In some embodiments, the organic compound is a nanostructure.
[0050] In some embodiments, the organic compound has a molecular formula of C x O y H z In some embodiments: x is from 2 to 12; y is from 2 to 8; z is from 2 to 14. In some embodiments: x is 8; y is from 4 to 6; z is 4.
[0051] In some embodiments, the organic compound comprises terephthalic acid, terephthalate esters, dimethyl terephthalate, bis(2-hydroxyethyl)terephthalate, ethylene glycol, phthalic acid, protocatechuic acid, and / or isophthalic acid. In some embodiments, the organic compound comprises terephthalic acid.
[0052] In some embodiments, the organic compound comprises an orthorhombic crystal system.
[0053] In some embodiments, the mixture includes 1 wt.% to 99 wt.% of the organic compound, such as 5 wt.% to 95 wt.% of the organic compound, or 10 wt.% to 90 wt.% of the organic compound.
[0054] In some embodiments, the metal oxide crystals include crystalline metal oxide nanoparticles.
[0055] In some embodiments, the mixture includes 1 wt.% to 95 wt.% metal oxide crystals, such as from 5 wt.% to 90 wt.% metal oxide crystals, or from 10 wt.% to 85 wt.% metal oxide crystals.
[0056] In some embodiments, the particle size of the metal oxide crystals is from 1 nm to 100 nm, such as from 1 nm to 50 nm, from 1 nm to 10 nm, or from 1 nm to 5 nm.
[0057] In some embodiments, the metal oxide crystals include tin (IV) oxide (SnO2), tin (II) oxide (SnO), zinc oxide (ZnO), zinc peroxide (ZnO2), calcium oxide, lithium oxide, potassium oxide, lead oxide and / or iron oxide. In some embodiments, the metal oxide crystals include tin (IV) oxide (SnO2).
[0058] In some embodiments, the metal oxide crystals have a tetragonal system.
[0059] In some embodiments, the X-ray diffraction (XRD) pattern of the organic compound has a diffraction peak, and the metal oxide crystal has an XRD peak. In some embodiments, the 2θ (±0.2 degrees) value of the XRD peak of the organic compound includes at least one value from 17.41°, 25.21°, and 27.95°.
[0060] In some embodiments, the 2θ (± 0.2 degrees) value of the XRD diffraction pattern of the organic compound includes at least two peaks, and these diffraction peaks are selected from 17.41°, 25.21° and 27.95°. In some embodiments, the 2θ (± 0.2 degrees) value of the XRD peak of the organic compound includes 17.41°, 25.21° and 27.95°. In some embodiments, the 2θ (± 0.2 degrees) value of the XRD peak of the metal oxide crystal includes at least one of 26.60°, 33.90°, 37.97°, 39.00°, 51.81°, 54.79°, 57.87°, 61.92°, 64.79°, 66.01°, 71.33°, 78.76°, 81.19°, 83.78° and 87.29°.
[0061] In some embodiments, the 2θ (±0.2 degrees) values of the XRD diffraction peaks of the metal oxide crystals include at least two from 26.60°, 33.90°, 37.97°, 39.00°, 51.81°, 54.79°, 57.87°, 61.92°, 64.79°, 66.01°, 71.33°, 78.76°, 81.19°, 83.78°, and 87.29°. In some embodiments, the 2θ (±0.2 degrees) values of the XRD peaks of the metal oxide crystals include at least three of 26.60°, 33.90°, 37.97°, 39.00°, 51.81°, 54.79°, 57.87°, 61.92°, 64.79°, 66.01°, 71.33°, 78.76°, 81.19°, 83.78°, and 87.29°. In some embodiments, the 2θ (±0.2 degrees) values of the XRD peaks of the crystalline metal oxide include four of 26.60°, 33.90°, 37.97°, 39.00°, 51.81°, 54.79°, 57.87°, 61.92°, 64.79°, 66.01°, 71.33°, 78.76°, 81.19°, 83.78°, and 87.29°.
[0062] In some embodiments, the mixture has an XRD pattern with characteristic peaks, such as Figure 6 As shown in c.
[0063] In some embodiments, according to the differential scanning calorimetry (DSC) thermogram, the mixture has at least one endothermic peak, and its maximum temperature (±3°C) is from 328°C, 461°C or 528°C. In some embodiments, according to the DSC thermogram, the mixture has at least two endothermic peaks, and the maximum temperature (±3°C) is from 328°C, 461°C and 528°C. In some embodiments, according to the DSC thermogram, the mixture has endothermic peaks, and the maximum temperature (±3°C) includes 328°C, 461°C and 528°C.
[0064] In some embodiments, the mixture has Fig.11 DSC graph shown.
[0065] In some embodiments, the mixture has a thermogravimetric analysis (TGA) spectrum such as Fig.11 shown.
[0066] In some embodiments, the mixture has substantially Fig.15 e is the X-ray photoelectron spectroscopy (XPS) spectrum shown in Figure 5.
[0067] In some embodiments, the specific surface area of the mixture is 10 square meters per gram (m 2 g -1 ) to 50m 2 g -1 , for example, from 15m 2 g -1 Up to 30m 2 g -1 or from 17m 2 g -1 Up to 21m 2 g -1 .
[0068] In some embodiments, the conductivity of the mixture ranges from 5 Siemens per meter (S m -1 ) to 5000S m -1 (6.3MPa), for example, at 6.3MPa, from 100S m -1 Up to 1500S m -1 , or from 400S m at 6.3MPa -1 Up to 600S m -1 .
[0069] In some embodiments, the mixture comprises silicon material. In some embodiments, the silicon-containing material is embedded in the organic compound. In some embodiments, the mixture comprises from 0.1wt% to 95wt% of silicon-containing material, for example, from 5wt% to 90wt% of silicon-containing material, or from 10wt.% to 85wt.% of silicon-containing material. In some embodiments, the silicon-containing material comprises silicon element. In some embodiments, the silicon-containing material comprises nano silicon particles. In some embodiments, the particle size range of the nano silicon material is from 1 nanometer (nm) to 1000 nanometers, for example, from 1nm to 500nm, from 1nm to 20nm, or from 1nm to 5nm.
[0070] In some embodiments, the mixture includes graphene nanosheets. In some embodiments, the graphene nanosheets cover at least a portion of the metal oxide crystals. In some embodiments, the composite includes from 0.1wt.% to 50wt.% of graphene nanosheets, for example, from 5wt.% to 45wt.% of graphene nanosheets, or from 10wt.% to 40wt.% of graphene nanosheets. In some embodiments, the graphene nanosheets include flakes with a size from 1nm to 5μm, for example, from 50nm to 5μm, or from 100nm to 1μm. In some embodiments, the graphene nanosheets include from 1 layer to 100 layers, for example, from 1 layer to 50 layers, or from 1 layer to 10 layers. In some embodiments, the graphene nanosheets contain at least 90% carbon, for example, at least 95%. In some embodiments, the graphene nanosheets contain functional groups on their surfaces. In some embodiments, the functional groups include hydroxyl, carbonyl, carboxyl and / or amino groups. In some embodiments, the mixture further includes a silicon-containing material, and the graphene nanosheets cover at least a portion of the silicon-containing material.
[0071] In some embodiments, the composite further comprises a metal organic framework embedded within the organic compound.
[0072] In some embodiments, the metal organic framework is partially crystalline.
[0073] In some embodiments, the metal organic framework is a crystalline structure.
[0074] In some embodiments, the metal organic framework is a nanostructure.
[0075] In some embodiments, the metal organic framework comprises the organic compound and the metal. In some embodiments, the metal is Zn, Fe, Cu, Al, Zr, Cr, Co, Li, Na or K. In some embodiments, the metal is Zn.
[0076] In some embodiments, the metal organic framework has the molecular formula MC x Hy O z nH2O, wherein M is a metal and n ranges from 0 to 5 (e.g., 0, 1, 2, or 3.5). In some embodiments, the metal organic framework has a molecular formula MC x H y O z ·3.5H2O, wherein M is a metal. In some embodiments, the metal organic framework has a molecular formula MC x H y O z , wherein M is a metal. In some embodiments: x ranges from 2 to 12; y ranges from 2 to 8; and z ranges from 2 to 14. In some embodiments: x is 8; y is 4; and z is 4.
[0077] In some embodiments, the metal organic framework comprises terephthalate.
[0078] In some embodiments, the mixture has a particle size of 500nm to 700μm. In some embodiments, the particle size is flaky particles of 10nm to 10μm. In some embodiments, the thickness of the flaky particles is 1nm to 10nm. In some embodiments, the flaky particles include nanoparticles with a size of 1nm to 60nm. In some embodiments, the particles include agglomerated nanoparticles with a size of 1nm to 60nm. In some embodiments, the particles contain metal organic framework crystals with a size of 10nm to 10μm.
[0079] In some embodiments, the metal organic framework has an average domain size of 30 nm to 60 nm.
[0080] In some embodiments, the 2θ (± 0.2 degrees) values of the XRD peaks of the composite include at least one peak from 11.75 degrees, 14.74 degrees, 16.60 degrees, and 16.98 degrees. In some embodiments, the 2θ (± 0.2 degrees) values of the XRD peaks of the composite include at least two from 11.75 degrees, 14.74 degrees, 16.60 degrees, and 16.98 degrees. In some embodiments, the 2-θ (± 0.2 degrees) values of the XRD peaks of the composite include 11.75 degrees, 14.74 degrees, 16.60 degrees, and 16.98 degrees.
[0081] In some embodiments, the composite has an XRD pattern with characteristic peaks, such as Fig.60 As shown in a.
[0082] In some embodiments, the 2θ (± 0.2 degrees) values of the XRD peaks of the composite include at least one peak from 9.89 degrees, 19.33 degrees, 25.27 degrees, and 40.11 degrees. In some embodiments, the 2θ (± 0.2 degrees) values of the XRD peaks of the composite include at least two from 9.89 degrees, 19.33 degrees, 25.27 degrees, and 40.11 degrees. In some embodiments, the 2θ (± 0.2 degrees) values of the XRD peaks of the composite include 9.89 degrees, 19.33 degrees, 25.27 degrees, and 40.11 degrees.
[0083] In some embodiments, the 2θ (± 0.2 degrees) value of the XRD peak of the mixture includes at least one of 17.45 degrees, 25.27 degrees, 28.017 degrees, and 42.99 degrees. In some embodiments, the 2θ (± 0.2 degrees) value of the XRD peak of the mixture includes at least two, from 17.45 degrees, 25.27 degrees, 28.017 degrees, and 42.99 degrees. In some embodiments, the 2θ (± 0.2 degrees) value of the XRD peak of the mixture includes 17.45 degrees, 25.27 degrees, 28.017 degrees, and 42.99 degrees. In some embodiments, the mixture has an XRD pattern with characteristic peaks, such as Fig.60 As shown in b.
[0084] In some embodiments, the mixture further comprises a tin-containing component selected from metallic tin, tin chloride, tin chloride hydrate, tin hydroxide, and tin hydroxide oxide chloride (e.g., a tin oxide having a molecular formula of Sn 21 Cl 16 OH) 14 In some embodiments, the tin-containing component comprises particles having a size of 1 nm to 100 nm. In some embodiments, the tin-containing component is at least partially crystalline. In some embodiments, the tin-containing component is crystalline. In some embodiments, the tin-containing component has a nanostructure.
[0085] In some embodiments, the mixture is a dark powder.
[0086] In some embodiments, the mixture is a black powder.
[0087] In some embodiments, the mixture is at a concentration of 0.5 g L -1 When the absorbance is at least 1 a.u. (e.g., at least 1.5 au) at 242 nm.
[0088] In some embodiments, the mixture is at a concentration of 0.5 g L -1 When the absorbance is at least 0.4 au at 450 nm.
[0089] In some embodiments, the mixture is at a concentration of 0.5 g L-1 When the absorbance is at least 0.4 au at 500 nm.
[0090] In some embodiments, the mixture is at a concentration of 0.5 g L -1 When the absorbance is at least 0.5 au at 317 nm.
[0091] In some embodiments, the mixture further comprises a metal embedded in the organic compound. In some embodiments, the metal is selected from Na, Li, K and Zn. In some embodiments, the mixture comprises a metal selected from Na2C8H4O4, Li2C8H4O4, K2C8H4O4 or ZnC8H6O4.
[0092] In some embodiments, the mixture consists of nanostructured organic compounds.
[0093] In some embodiments, the mixture consists of nanostructured terephthalic acid.
[0094] In one aspect, the present disclosure provides an electrode based on the mixture of the present disclosure. In some embodiments, the mixture further comprises at least one component selected from conductive carbon, a binder copper foil and graphene nanosheets. In some embodiments, the binder comprises polyimide.
[0095] In some embodiments, the electrode is at 200 mA g -1 After 500 cycles at a current density of 10 mAh g -1 ) to 1500mAh g -1 The lithium ion discharge capacity (e.g., from 100 mAh g -1 Up to 1000mAh g -1 , from 200mAh g -1 Up to 800mAh g -1 ).
[0096] In some embodiments, the electrode has a Coulombic efficiency of 70% to 120% (eg, 80% to 110%, 90% to 100%) after 500 cycles.
[0097] In some embodiments, after 150 cycles of a half-cell assembled from the electrode material, the electrolyte resistance increases from 1.0Ω to 6.0Ω (eg, from 2.0Ω to 5.0Ω, from 3.0Ω to 4.0Ω).
[0098] In some embodiments, after 300 cycles of a half-cell assembled from the electrode material, the resistance of the electrolyte increases from 2.0Ω to 8.0Ω (eg, 2.0Ω to 7.0Ω, from 3.0Ω to 6.0Ω).
[0099] In some embodiments, the lithium ion diffusion rate of the electrode after 150 cycles is from 10 -11 cm 2 s -1 to 9×10 -9 cm 2 s -1 (For example, from 5×10 -11 cm 2 s -1 to 5×10 -9 cm 2 s -1 , from 9×10 -11 cm 2 s -1 to 10 -9 cm 2 s -1 ). In some embodiments, the electrode has a capacitance from 2×10 -11 cm 2 s -1 To 10-8cm 2 s -1 (For example, from 7×10 -11 cm 2 s -1 to 7×10 -9 cm 2 s -1 , from 10-10cm 2 s -1 to 9×10 -9 cm 2 s -1 ) of the lithium ion diffusion rate.
[0100] In some embodiments, the electrode is at 100 mA g -1 After 10 cycles at a current density of 300 mAh g -1 Up to 1500mAh g -1 In some embodiments, the electrode is at 500 mA g -1 After 30 cycles at a current density of -1 Up to 1500mAh g -1 In some embodiments, the electrode is at 1000 mA g -1 After 50 cycles at a current density of-1 Up to 1500mAh g -1 In some embodiments, the electrode is at 5000 mA g -1 After 60 cycles at a current density of -1 Up to 1300mAh g -1 .
[0101] In some embodiments, Na + The voltage of the ion insertion electrode is 0.1V to 0.9V (vs Na / Na + ). In some embodiments, Na + Ion insertion into the electrode occurs at voltages between 0.15 V and 0.8 V (vs Na / Na + ). In some embodiments, Na + Ion insertion into the electrode occurs at voltages between 0.17 V and 0.3 V (vs Na / Na + ).
[0102] In some embodiments, Na + The voltage range for ion extraction from the electrode is 0.3 V to 0.7 V (vs Na / Na + ). In some embodiments, Na + The voltage range for ion extraction from the electrode is 0.4 V to 0.6 V (vs Na / Na + ).
[0103] In some embodiments, the electrode has a current from 100 mA hg after 500 cycles. -1 Up to 1800mA hg -1 of lithium-ion discharge capacity.
[0104] In some embodiments, the electrode has a lithium ion discharge capacity of 100 milliamp hours (mAh) per gram of metal oxide crystals to 1800 mAh per gram of metal oxide crystals after 500 cycles. In some embodiments, the electrode has a lithium ion discharge capacity of from 200 mAh per gram of metal oxide crystals to 1800 mAh per gram of metal oxide crystals after 500 cycles. In some embodiments, the electrode has a lithium ion discharge capacity of from 500 mAh per gram of metal oxide crystals to 1800 mAh per gram of crystalline metal oxide after 500 cycles.
[0105] In one aspect, the present disclosure provides a battery comprising an electrode according to the present disclosure. In some embodiments, the electrode is an anode. In some embodiments, the battery further comprises a cathode. In some embodiments, the battery further comprises an electrolyte between the anode and the cathode. In some embodiments, there is an electrical connection between the anode and the cathode. In some embodiments, the battery is a lithium ion battery, a sodium ion battery, a calcium ion battery, or a potassium ion battery.
[0106] In one aspect, according to the disclosure, a vehicle including a battery is provided.
[0107] In a certain aspect, the present disclosure provides a structure comprising a battery according to the disclosure.
[0108] In one aspect, the present disclosure provides a system capable of generating electricity. Wherein, according to the disclosure, the system is configured to be connected to a battery. In some embodiments, the system includes a system capable of generating electricity from electromagnetic radiation, a system capable of generating electricity from the rotation of a turbine, and / or a system capable of generating electricity from a combustion reaction. In some embodiments, the system includes at least one selected from photovoltaics, wind turbines, hydroelectric generators, hydroelectric power plants, nuclear power plants, coal-fired power plants, oil power plants, and gas power plants. In some embodiments, the battery is used to store the electricity generated by the system.
[0109] In some embodiments, the complex comprises a transition metal disulfide. In some embodiments, the transition metal disulfide has a molecular formula MX2. In some embodiments, M is a transition metal atom and X is a chalcogen atom. In some embodiments, M comprises Mo or W. In some embodiments, the chalcogen atom comprises a component of S, Se and Te. In some embodiments, the transition metal disulfide comprises a two-dimensional transition metal disulfide. In some embodiments, the transition metal disulfide is embedded in an organic compound. In some embodiments, the mixture comprises a metal oxide crystal, and the transition metal disulfide is embedded in the metal oxide crystal.
[0110] In some embodiments, the mixture includes a polymer and a material including silicon. In some embodiments, the polymer is made of monomers, and at least a portion of the monomers are cross-linked with each other. In some embodiments, the monomers include imide monomers. In some embodiments, a portion of the material and a portion of the polymer are bonded by hydrogen bonds. In some embodiments, the material includes silicon particles embedded in an organic compound. In some embodiments, the material includes silicon particles. In some embodiments, the size of the silicon particles is 1 nm to 5 μm, the size range can be 10 nm to 1 μm, the size range can be 20 nm to 500 nm, and the size range can be 20 nm to 200 nm. In some embodiments, the organic compound crystals are nanostructured and nanocrystalline. In some embodiments, based on the mass of silicon element in the material, when the current density is 200 mA g -1 When the specific capacity of lithium ion storage energy is 1000mA hg -1 , after 30 cycles it becomes 3500mA hg -1 In some embodiments, at 200 mA g -1 The lithium-ion battery assembled by the mixture is charged with a current density of 3000Whkg at the 30th cycle. -1 Up to 8000Wh kg -1 In some embodiments, the composite has a lithium ion diffusion impedance of from 10Ω to 60Ω, and may be from 20Ω to 40Ω. In some embodiments, the infrared spectrum of the polymer is at 1723cm -1 There is a peak at 1362 cm -1 In some embodiments, the infrared spectrum of the composite is at 3739 cm -1 In some embodiments, the polymer is a polyimide.
[0111] In one aspect, the present disclosure provides a method, comprising: treating a mixture raw material based on the present disclosure into a first solution having a first concentration of pollutants; reducing the concentration of pollutants in the first solution to form a second solution, wherein the concentration of pollutants in the second solution is less than the concentration of pollutants in the first solution. In some embodiments, at least a portion of the pollutants in the first solution are adsorbed onto the surface of the composite. In some embodiments, the composite photocatalytically degrades at least a portion of the pollutants in the first solution.
[0112] In some embodiments, reducing the concentration of the contaminant in the first solution further comprises exposing the first solution to visible light. In some embodiments, the contaminant comprises a member selected from the group consisting of hydrocarbon components, azo dyes, and xanthate-based compounds.
[0113] In one aspect, the present disclosure provides a method comprising: heating a mixture comprising a first polymer, a second polymer, and a depolymerizing agent to a first temperature; depolymerizing the first polymer to form an organic compound; forming a complex comprising the organic compound, wherein the second polymer is not substantially depolymerized. In some embodiments, the first polymer is a polymer that can be depolymerized in the presence of water. In some embodiments, the first polymer comprises polyethylene terephthalate (PET), polystyrene, polyvinyl chloride, nylon, polyurethane, phenolic resin, and / or epoxy resin. In some embodiments, the second polymer comprises polyethylene and / or polypropylene. In some embodiments, the method further comprises separating the complex from the second polymer.
[0114] In one aspect, the present disclosure provides a method comprising: heating a mixture of reactants to a first temperature; forming an organic compound complex of a nanocrystalline structure, wherein the reactants include a polymer and a depolymerizing agent. In some embodiments, the reactants also include a molten salt, and heating the mixture to make the molten salt molten.
[0115] In one aspect, the present disclosure provides a method comprising: heating a mixture comprising reactants to a first temperature; forming a composite comprising an organic compound and metal oxide crystals, wherein: a portion of the organic compound is crystalline; the reactants comprise a molten salt, a polymer, and a depolymerizing agent; and heating the molten salt to become a molten salt.
[0116] In one aspect, the present disclosure provides a method of preparing a composite, wherein the method comprises heating a mixture including the polymer to a temperature of 150° C. to 400° C. In some embodiments, the method comprises heating for a time of 1 second to 5 hours. In some embodiments, the heating is performed in an inert atmosphere or a nitrogen atmosphere. In some embodiments, the atmosphere comprises hydrogen in a range of 0.1% to 99.9%.
[0117] In some embodiments, the mixture is heated to depolymerize the polymer to provide monomers, and the monomers form organic compounds. The reactants contain 1 wt.% to 99 wt.% of the polymer.
[0118] In some embodiments, the reactants include from 5 wt.% to 95 wt.% (eg, from wt.% to 90 wt.%) of the polymer.
[0119] In some embodiments, the polymer includes polyethylene terephthalate (PET), poly(acrylonitrile), poly(6-aminocaproic acid), polycaprolactam, nylon, polyetheretherketone (PEEK), poly(ethylene) (PE), poly(hexamethylenehexanamide), poly(methyl methacrylate), poly(methylene oxide), poly(4-methylpentene), poly(propylene), poly(styrene), poly(trans-1,4-butadiene), poly(vinyl alcohol), poly(vinyl chloride) (PVC), poly(vinyl fluoride), poly(vinylidene chloride), and / or poly(vinylidene fluoride).
[0120] In some embodiments, the polymer comprises polyethylene terephthalate (PET).
[0121] In some embodiments, the polymer is derived from waste plastic.
[0122] In some embodiments, the difference in melting temperatures of the polymer and the depolymerizing agent is less than 100°C (eg, less than 75°C; less than 50°C).
[0123] In some embodiments, the reactants include 1 wt.% to 95 wt.% (eg, from 5 wt.% to 90 wt.%, from 10 wt.% to 85 wt.%) of a depolymerizing agent.
[0124] In some embodiments, the depolymerizing agent comprises an inorganic salt. In some embodiments, the inorganic salt (cation) comprises the same metal as the metal oxide. In some embodiments, the inorganic salt undergoes an oxidation reaction during heating.
[0125] In some embodiments, the depolymerizing agent comprises tin (II) chloride (SnCl2), zinc chloride (ZnCl2), calcium chloride (CaCl2), lead chloride (PbCl2), sodium chloride (NaCl), potassium chloride (KCl) and / or ferric chloride (FeCl2). In some embodiments, the depolymerizing agent comprises tin (II) chloride (SnCl2). In some embodiments, the depolymerizing agent comprises zinc chloride (ZnCl2).
[0126] In some embodiments, the depolymerizing agent comprises an ionic liquid. In some embodiments, the ionic liquid comprises [bmpy][Tf2N] and [BMIM][Tf2N] and / or an imidazolium ionic liquid. In some embodiments, the ionic liquid includes an ionic liquid selected from 1-octyl-3-methyl-imidazolium ([OMIM]), 1-methyl-imidazolium ([MIM]), 1-ethyl-3-methyl-imidazolium ([EMIM]), 1,3-dimethylimidazolium ([M13IM]), 1-(2-hydroxyethyl)-3-methylimidazolium ([HOEMIm]), 1-ethyl-2,3-dimethylimidazolium ([EMMIM]), 1-butyl-3-methylimidazolium ([BMIM]), 1-hexyl-3-methylimidazolium (HMIM]), 1,2,3-trimethylimidazolium ([MMMIM]), 1-decyl-3-methylimidazolium ([DMIM]), 1-allyl-3-butylimidazolium ([ABIM]), 1,2-dimethylimidazolium ([M 12 IM]), 1-butyl-2,3-dimethylimidazolium ([BMMIM]), 1-allyl-3-methylimidazolium ([AMIM]), 1-allyl-3-vinylimidazolium ([AVIM]), tetradecyltrihexylphosphine ([P 66614 ]), N-ethylpyridine ([EPy]), and N-butylpyridine ([BPy]). In some embodiments, the ionic liquid is selected from bis(trifluoromethylsulfonyl)imide ([Tf2N]), bromide ([Br]), dicyandiamide ([DCA]), hexafluorophosphate ([PF6]), perchlorate ([ClO4]), toluenesulfonate ([TS]), acetate ([Ac]), chloride ([Cl]), glycine ester ([Gly]), iodide ([I]), triflate ([TFO]), sulfite ([Pro]), alanine salt ([Ala]), lysine salt ([Lys]), dihydrogen phosphate ([H2PO4]), nitrate ([NO3]), serine salt ([Ser]), glutamate ([Glu]), and hydrogen sulfate ([H2SO4]), and tetrafluoroborate ([BF4]).
[0127] In some embodiments, the salt comprises a chloride molten salt. In some embodiments, the molten salt comprises LiCl and / or KCl. In some embodiments, the salt comprises LiCl and KCl. In some embodiments, the molten salt comprises from 40wt.%LiCl to 80wt.%LiCl (e.g., 50wt.%LiCl to 70wt.%, 55wt.%LiCl to 65wt.%). In some embodiments, the molten salt comprises 20wt.% to 70wt.%KCl (e.g., 30wt.% to 55wt.%KCl, 35wt.% to 40wt.%KCl).
[0128] In some embodiments, the melting point of the molten salt is from 250°C to 700°C (eg, from 300°C to 600°C, from 320°C to 500°C).
[0129] In some embodiments, the heating is performed under an atmosphere selected from the group consisting of air, nitrogen, argon, and hydrogen.
[0130] In some embodiments, heating is performed under an inert atmosphere.
[0131] In some embodiments, heating is performed under argon.
[0132] In some embodiments, the heating is performed under an argon and hydrogen atmosphere. In some embodiments, the heating is performed under an argon and a mixed gas containing 1% to 99% hydrogen.
[0133] In some embodiments, the heating is performed at a temperature above the melting point of the polymer and the melting point of the depolymerizing agent.
[0134] In some embodiments, the heating is performed at a temperature above the melting point of the polymer, the melting point of the molten salt, and the melting point of the depolymerizing agent.
[0135] In some embodiments, the heating is performed below the carbonization temperature of the polymer and the decomposition temperature of the organic compound.
[0136] In some embodiments, the first temperature range is 200°C to 600°C.
[0137] In some embodiments, the first temperature is up to 600°C.
[0138] In some embodiments, the first temperature range is 200°C to 450°C.
[0139] In some embodiments, the first temperature is at least 250°C.
[0140] In some embodiments, the first temperature is at least 300°C.
[0141] In some embodiments, the first temperature is at most 500°C.
[0142] In some embodiments, the first temperature is up to 400°C.
[0143] In some embodiments, the first temperature is at most 310°C.
[0144] In some embodiments, the mixture is maintained at the first temperature for 0.01 minutes to 120 minutes (eg, 1 minute to 60 minutes, 5 minutes to 30 minutes, 1 second).
[0145] In some embodiments, the heating rate of the mixture is in the range of 1°C min-1 to 100℃ min -1 (For example, from 2℃ min -1 to 50℃ min -1 ,3℃ min -1 to 20℃ min -1 ).
[0146] In some embodiments, the method further includes contacting the complex with a solvent. In some embodiments, the solvent includes at least one selected from an aqueous solution, an alkaline aqueous solution, an acidic aqueous solution, and a polar organic liquid. In some embodiments, the pH value of the solvent is 0.1 to 7 (e.g., from 1 to 6, from 2 to 5). In some embodiments, the solvent includes an acid selected from hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid. In some embodiments, the acid concentration in the solvent ranges from 1% (volume %) to 98vol.% (e.g., from 2vol.% to 95vol.%, from 5vol.% to 90vol.%). In some embodiments, the pH value of the solvent is 7 to 14 (e.g., from 8 to 13, from 9 to 12). In some embodiments, the solvent contains a hydroxide. In some embodiments, the hydroxide includes sodium hydroxide and potassium hydroxide. In some embodiments, the polar organic liquid includes ethanol.
[0147] In some embodiments, the complex includes a depolymerizing agent, and contacting the complex with a solvent removes at least a portion of the depolymerizing agent. In some embodiments, the complex includes a depolymerizing agent, and contacting the complex with the solvent hydrolyzes a portion of the depolymerizing agent.
[0148] In some embodiments, the depolymerizing agent comprises SnCl2; SnCl2 is hydrolyzed to form a second product comprising tin, chlorine, hydrogen and oxygen elements; and the second material product is formed by contacting and forming a composite and an organic compound dispersed in the composite. In some embodiments, the second material comprises tin hydroxide chloride. In some embodiments, the chemical composition of the second material is Sn 21 Cl 16 (OH) 14 O6. In some embodiments, the second material portion is a crystalline phase.
[0149] In some embodiments, the method further comprises separating the complex from the solvent. In some embodiments, separation comprises a method of vacuum filtration or centrifugation. In some embodiments, the method further comprises drying the complex after separation of the complex. In some embodiments, the complex is dried under an atmosphere of air, an inert atmosphere, or a vacuum atmosphere. In some embodiments, the complex is dried at a temperature of -196°C to 100°C (e.g., from -196°C to 0°C, from 20°C to 100°C).
[0150] In some embodiments, the solvent includes a precursor of the silicon-containing material, and the composite is contacted with the solvent to introduce the silicon-containing material into the composite.
[0151] In some embodiments, the mixture also includes a precursor of a silicon-containing material, and the composite further includes the silicon-containing material.
[0152] In some embodiments, the reactants include 0.1 wt.% to 98 wt.% (eg, 5 wt.% to 90 wt.%, 10 wt.% to 85 wt.%) of a precursor of a silicon-containing material.
[0153] In some embodiments, the precursor of the silicon-containing material is nanostructured particles.
[0154] In some embodiments, the precursor of the silicon-containing material includes elemental silicon, Ca2Si, Ca5Si3, CaSi, Ca3Si4, CaSi2 and / or Mg2Si.
[0155] In some embodiments, the particle size of the precursor of the silicon-containing material ranges from 1 nm to 1000 nm (eg, from 1 nm to 500 nm, from 1 nm to 20 nm, from 1 nm to 5 nm).
[0156] In some embodiments, the precursor of the silicon-containing material contains surface functional groups.
[0157] In some embodiments, the method further comprises ball milling the precursor of the silicon-containing material. In some embodiments, the silicon-containing precursor is ball milled in the presence of a solvent. In some embodiments, the solvent comprises n-hexane. In some embodiments, the solvent comprises graphene nanosheets, and the composite is contacted with the solvent to introduce the graphene nanosheets into the composite.
[0158] In some embodiments, the mixture before the reaction also includes graphene nanosheets, and the composite product further includes graphene nanosheets. In some embodiments, the mixture includes 0.1wt.% to 80wt.% (e.g., 2wt.% to 45wt.%, 5wt.% to 40wt.%) of graphene nanosheets. In some embodiments, the size range of graphene nanosheets is from 1nm to 5μm (e.g., from 50nm to 5μm, from 100nm to 1μm). In some embodiments, the number of graphene nanosheet layers is from 1 layer to 100 layers (e.g., from 1 layer to 50 layers, from 1 layer to 10 layers). In some embodiments, the graphene nanosheets have a carbon purity of at least 90% (e.g., at least 95%). In some embodiments, the surface of the graphene nanosheets includes functional groups. In some embodiments, the functional groups include hydroxyl, carbonyl, carboxyl and amino groups. In some embodiments, the graphene nanosheets are produced by cathode electrochemical stripping of a graphite electrode. In some embodiments, cathode electrochemical stripping is carried out in a molten salt. In some embodiments, the molten salt comprises at least one component selected from lithium chloride and sodium chloride. In some embodiments, the cathode electrochemical stripping is performed at a temperature of 500°C to 900°C.
[0159] In some embodiments, the organic compound contains an amorphous phase component.
[0160] In some embodiments, the organic compound is in a crystalline phase.
[0161] In some embodiments, the organic compound is a nanostructure. In some embodiments, the organic compound has a molecular formula of C x O y Hz. In some embodiments: x is from 2 to 12; y is from 2 to 8; z is from 2 to 14. In some embodiments: x is 8; y is from 4 to 6; z is 4.
[0162] In some embodiments, the organic compound comprises terephthalic acid, terephthalate, dimethyl terephthalate, bis(2-hydroxyethyl) terephthalate, ethylene glycol, phthalic acid, protocatechuic acid and / or isophthalic acid. In some embodiments, the organic compound comprises terephthalic acid. In some embodiments, terephthalic acid is nanostructured, with at least one dimension being less than 100 nm.
[0163] In some embodiments, heating is performed in a range of 0.01 to 100 atmospheres (eg, from 0.1 to 10 atmospheres, from 0.5 to 5 atmospheres, from 0.8 to 1.5 atmospheres).
[0164] In some embodiments, the heating is performed at atmospheric pressure.
[0165] In some embodiments, the method further comprises: forming a suspension comprising the composite and the graphene nanosheets; subjecting the suspension to ultrasonic treatment; and recovering a product from the suspension. Wherein, the product comprises the composite and the graphene nanosheets. In some embodiments, the suspension further comprises an acid. In some embodiments, the product comprises 50 wt.% to 99.9 wt.% of the composite. In some embodiments, the product comprises from 0.1 wt.% to 50 wt.% of the graphene nanosheets.
[0166] In some embodiments, the reactants further include water.
[0167] In some embodiments, at least a portion of the deagglomerating agent is hydrated.
[0168] In some embodiments, the deagglomerating agent is hydrated.
[0169] In some embodiments, the deagglomeration agent includes 0.1 wt. % to 20 wt. % water.
[0170] In some embodiments, the method further comprises: removing at least a portion of the composite; and adding additional polymer.
[0171] In some embodiments, the composite further comprises a metal organic framework embedded in the organic compound. In some embodiments, the metal organic framework comprises the organic compound and the metal.
[0172] In some embodiments, the metal is selected from Zn, Fe, Cu, Al, Zr, Cr, Co, Li, Na, and K. In some embodiments, the metal is Zn.
[0173] In some embodiments, the metal organic framework has the molecular formula MC x H y O z nH2O, where M is a metal and n ranges from 0 to 5 (eg, 0, 1, 2, or 3.5).
[0174] In some embodiments, the metal organic framework has the molecular formula MC x H y O z ·3.5H2O, where M is a metal.
[0175] In some embodiments, the metal organic framework has the formula MC x H y O z , wherein M is a metal. In some embodiments: x is from 2 to 12; y is from 2 to 8; z is from 2 to 14. In some embodiments: x is 8; y is 4; z is 4.
[0176] In some embodiments, the metal organic framework comprises terephthalate.
[0177] In some embodiments: the metal-organic framework includes hydrated water; and the method further includes: heating the composite to a second temperature, wherein the heating removes at least a portion of the hydrated water from the metal-organic framework. In some embodiments, the metal-organic framework includes a first crystal structure before heating to the second temperature, and the metal-organic framework includes a second crystal structure after heating to the second temperature, wherein the second crystal structure is different from the first crystal structure. In some embodiments, the second temperature is 50°C to 400°C. In some embodiments, the composite is maintained at the second temperature for 1 millisecond to 10 hours. In some embodiments, the method further includes cooling the mixture after heating the mixture. In some embodiments, the cooling is performed in the same atmosphere as the heating.
[0178] In some embodiments, the reactants are free of acids, bases, and enzymes.
[0179] In some embodiments, the method has no separation step.
[0180] In some embodiments, heating is performed to form the second organic compound, and the second organic compound evaporates.
[0181] In some embodiments, the second organic compound is ethylene glycol.
[0182] In some embodiments, the composite consists of a nanostructured organic compound.
[0183] In some embodiments, the composite consists of nanostructured terephthalic acid.
[0184] In some embodiments, the method further comprises reacting the complex with a metal hydroxide to form a complex comprising the hydroxide and a metal product, wherein the reaction time is up to 18 hours. In some embodiments, the product comprises a molecular formula of Na2C8H4O4, Li2C8H4O4, K2C8H4O4 or ZnC8H6O4.
[0185] In some embodiments, the reaction time is up to 12 hours (eg, up to 6 hours).
[0186] In some embodiments, the hydroxide is selected from among NaOH, LiOH, KOH and Zn(OH)2.
[0187] In some embodiments, the reactants and the complex include transition metal dichalcogenides. In some embodiments, the chemical formula of the transition metal dichalcogenide is MX2, wherein M is a transition metal atom and X is a chalcogen atom. In some embodiments, M includes molybdenum (Mo) or tungsten (W). In some embodiments, the chalcogen atom includes selected from sulfur (S), selenium (Se) and tellurium (Te). In some embodiments, the transition metal dichalcogenide includes a two-dimensional transition metal dichalcogenide. In some embodiments, the transition metal dichalcogenide is embedded in an organic compound. In some embodiments: the complex includes a crystalline metal oxide; and the transition metal dichalcogenide is embedded in the crystalline metal oxide.
[0188] Brief description of the diagram
[0189] Figure 1 Examples of composites are illustrated.
[0190] Figure 2 Examples of composites are illustrated.
[0191] Figure 3 Embodiments of electrodes are schematically depicted.
[0192] Figure 4 Embodiments of battery cells are schematically depicted.
[0193] Figure 5a is an example of a reaction.
[0194] Figure 5b is an example of a reaction.
[0195] Figure 5c is an example of a reaction.
[0196] Figure 5d is an example of a reaction.
[0197] Figure 6 af shows the X-ray diffraction (XRD) patterns.
[0198] Figure 7 ab show the X-ray diffraction patterns.
[0199] Figure 8 ac show the X-ray diffraction patterns.
[0200] Fig. 9 A graph of Raman spectroscopy data is shown.
[0201] Fig.10 Fourier transform infrared spectroscopy (FTIR) spectra are shown.
[0202] Fig.11Differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) graphs are shown.
[0203] Fig.12 ad shows scanning electron microscope (SEM) images.
[0204] Fig.13a -b shows the energy dispersive spectroscopy (EDS) spectrum.
[0205] Fig.14 ad shows transmission electron microscopy (TEM) images.
[0206] Fig.15 ah showed an X-ray photoelectron spectroscopy graph.
[0207] Fig.16 A bar graph showing conductivity data.
[0208] Fig.17 ag shows the electrochemical performance characterization diagram.
[0209] Fig.18 Plots of electrochemical characterization data are shown.
[0210] Fig.19 ab show scanning electron micrographs.
[0211] Fig. 20 ad shows the electrochemical performance characterization diagrams.
[0212] Fig.21 X-ray diffraction patterns are shown.
[0213] Fig. 22 Transmission electron micrographs are shown.
[0214] Fig.23 Scanning electron micrographs are shown.
[0215] Fig.24 Scanning electron microscope images are shown.
[0216] Fig.25 X-ray diffraction data are shown.
[0217] Fig.26 ab shows scanning electron microscope images.
[0218] Fig. 27 The ad shows a scanning electron microscope image.
[0219] Fig.28 a shows the photograph of heat-treated PET+(SnCl2-LiCl-KCl).
[0220] Fig.28b shows a photograph of commercial terephthalic acid.
[0221] Fig.29 a shows a photo of discarded PET.
[0222] Fig.29 b shows a photograph of PET fragments.
[0223] Fig.29 c shows the photograph of the PET+SnCl2+LiCl+KCl mixture before heat treatment.
[0224] Fig.29 d shows the photograph of the PET+SnCl2+LiCl+KCl mixture after heat treatment.
[0225] Fig.29 EF shows a photo of a molten salt sheet after solidification.
[0226] Fig.30 X-ray diffraction patterns are shown.
[0227] Fig.31 X-ray diffraction patterns are shown.
[0228] Fig.32 ac shows transmission electron microscopy images.
[0229] Fig.33 ab show the variation of dye concentration over time.
[0230] Fig.34 Electrochemical performance characterization diagrams are shown.
[0231] Fig.35 a is a schematic diagram of the experimental setup.
[0232] Fig.35 bc shows the temperature variation with time during the heating process.
[0233] Fig.36 ad shows the X-ray diffraction pattern.
[0234] Fig.37 af show differential scanning calorimetry images.
[0235] Fig.38 ac shows scanning electron microscope micrographs.
[0236] Fig.39 ab shows scanning electron microscope micrographs.
[0237] Fig.40 ab show the electrochemical characterization data.
[0238] Fig.41 X-ray diffraction patterns are shown.
[0239] Fig.42 Scanning electron micrographs are shown.
[0240] Fig.43 Scanning electron micrographs are shown.
[0241] Fig.44 X-ray diffraction patterns are shown.
[0242] Fig.45 Plots of electrochemical characterization data are shown.
[0243] Fig.46 X-ray diffraction patterns are shown.
[0244] Fig.47 A graph showing thermogravimetric analysis data is shown.
[0245] Fig.48 A graph of differential scanning calorimetry data is shown.
[0246] Fig.49 X-ray diffraction patterns are shown.
[0247] Fig.50 Backscattered electron micrographs are shown.
[0248] Fig.51 ac show the energy dispersive X-ray spectra.
[0249] Fig.52 Energy dispersion spectral mapping is shown.
[0250] Fig.53 a shows a backscattered electron micrograph.
[0251] Fig.53 b shows a histogram of crystal size.
[0252] Fig.54 ad show backscattered electron micrographs.
[0253] Fig.55 ad show secondary electron scanning electron micrographs.
[0254] Fig.56 Transmission electron microscopy micrographs are shown.
[0255] Fig.57 a shows a transmission electron microscopy micrograph.
[0256] Fig.57 b shows the histogram of particle size distribution.
[0257] Fig.58 a shows a transmission electron microscopy micrograph.
[0258] Fig.58 b shows the histogram of particle size distribution.
[0259] Fig.59 Plots of electrochemical characterization data are shown.
[0260] Fig.60 ab show the X-ray diffraction patterns.
[0261] Fig.61 ad show graphs of electrochemical characterization data.
[0262] Fig.62 Plots of electrochemical characterization data are shown.
[0263] Fig.63 Plots of electrochemical characterization data are shown.
[0264] Fig.64 ab show photos of HDPE before and after heat treatment, respectively.
[0265] Fig.65 ab show the X-ray diffraction patterns.
[0266] Fig.66 ab show the UV-Vis data plots.
[0267] Fig.67 Ag shows the X-ray diffraction pattern.
[0268] Fig.68 A schematic diagram of fabricating an electrode is shown.
[0269] Fig.69 ac show photographs of polyimide (PI).
[0270] Fig.70 X-ray diffraction patterns are shown.
[0271] Fig.71 A schematic diagram of the charge transfer complex between PI chains is shown.
[0272] Fig.72 ad shows the FTIR data graphs.
[0273] Fig.73 A plot of UV-Vis data is shown.
[0274] Fig.74 ab show graphs of the FTIR data.
[0275] Fig.74c shows a schematic diagram of hydrogen bonding between Si nanoparticles (“SiNPs”) and PI.
[0276] Fig.75a -b shows the electrochemical characterization data graph.
[0277] Fig.76 Plots of electrochemical characterization data are shown.
[0278] Figure 77a -b shows the electrochemical characterization data graph.
[0279] Fig.78 ad show SEM micrographs.
[0280] Fig.79 ae show the X-ray diffraction patterns.
[0281] Fig.80 Plots of electrochemical characterization data are shown.
[0282] Fig.81 The cycling performance of the electrode is shown.
[0283] Detailed description
[0284] Compound
[0285] In some embodiments, a composite according to the present disclosure may include a nanostructured organic compound including a plurality of molecules. A composite is referred to as a nanostructure if it contains one or more components having a nanometer size (e.g., 1 nm to 100 nm). In some embodiments, a component of the composite (e.g., a nanostructured organic compound) includes at least one dimension less than 100 (e.g., less than 95, less than 90, less than 85, less than 80, less than 75, less than 70, less than 65, less than 60, less than 55, less than 50, less than 45, less than 40, less than 35, less than 30, less than 25, less than 20, less than 15, less than 10, less than 5, less than 4, less than 3, less than 2, less than 1) nm. In some embodiments, x is 2 to 12 (e.g., 2 to 3, 2 to 4, 2 to 5, 2 to 6, 2 to 7, 2 to 8, 2 to 9, 2 to 10, 2 to 11, 3 to 4, 3 to 5, 3 to 6, 3 to 7, 3 to 8, 3 to 9, 3 to 10, 3 to 11, 3 to 12, 4 to 5, 4 to 6, 4 to 7, 4 to 8, 4 to 9, 4 to 10, 4 to 11, 4 to 12, 5 to 6, 5 to 7, 5 to 8, 5 to 9, 5 to 10, 5 to 11, 5 to 12, 6 to 7, 6 to 8, 6 to 9, 6 to 10, 6 to 11, 6 to 12, 7 to 8, 7 to 9, 7 to 10, 7 to In some embodiments, y is 2 to 8 (e.g., 2 to 3, 2 to 4, 2 to 5, 2 to 6, 2 to 7, 3 to 4, 3 to 5, 3 to 6, 3 to 7, 3 to 8, 4 to 5, 4 to 6, 4 to 7, 4 to 8, 5 to 6, 5 to 7, 5 to 8, 6 to 7, 6 to 8, 7 to 8, 2, 3, 4, 5, 6, 7, 8).In some embodiments, z is 2 to 14 (e.g., 2 to 3, 2 to 4, 2 to 5, 2 to 6, 2 to 7, 2 to 8, 2 to 9, 2 to 10, 2 to 11, 2 to 12, 2 to 13, 3 to 4, 3 to 5, 3 to 6, 3 to 7, 3 to 8, 3 to 9, 3 to 10, 3 to 11, 3 to 12, 3 to 13, 3 to 14, 4 to 5, 4 to 6, 4 to 7, 4 to 8, 4 to 9, 4 to 10, 4 to 11, 4 to 12, 4 to 13, 4 to 14, 5 to 6, 5 to 7, 5 to 8, 5 to 9, 5 to 10, 5 to 11, 5 to 12, 5 to 13, 5 to 14, 6 to 7, 6 to 8, 6 to 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71
[0286] In some embodiments, the composite includes nanostructured terephthalic acid. Without being bound by theory, nanostructured terephthalic acid differs from other forms of terephthalic acid due to its unique nanostructure morphology (see discussion and examples below).
[0287] In certain embodiments, the composite consists of a nanostructured organic compound. In certain embodiments, the composite consists of nanostructured terephthalic acid.
[0288] In some embodiments, the composite is a nanostructure and a nanocrystal. If the composite comprises a domain size less than 100 nm (e.g., less than 95, less than 90, less than 85, less than 80, less than 75, less than 70, less than 65, less than 60, less than 55, less than 50, less than 45, less than 40, less than 35, less than 30, less than 30, less than 25, less than 20, less than 15, less than 10, less than 5, less than 4, less than 3, less than 2, less than 1) nm. In some embodiments, the organic compound is a nanocrystalline phase.
[0289] In certain embodiments, the composite includes a metal oxide, a metal, a metal-organic framework, a silicon-containing material, and / or a graphene-containing material (discussed below) embedded in a nanostructured organic compound.
[0290] Figure 1An embodiment of the disclosed composite 1000 is illustrated. The composite 1000 includes an at least partially crystalline organic compound (e.g., terephthalic acid) 1100 and metal oxide crystals (e.g., tin oxide (SnO2) 1200) dispersed in the organic compound 1100. In some embodiments, the composite 1000 is a nanostructure and / or nanocrystalline phase.
[0291] Typically, the chemical formula of an organic compound (eg, a nanostructured organic compound, organic compound 1100) is C x O y H zIn some embodiments, x is 2 to 12 (e.g., 2 to 3, 2 to 4, 2 to 5, 2 to 6, 2 to 7, 2 to 8, 2 to 9, 2 to 10, 2 to 11, 3 to 4, 3 to 5, 3 to 6, 3 to 7, 3 to 8, 3 to 9, 3 to 10, 3 to 11, 3 to 12, 4 to 5, 4 to 6, 4 to 7, 4 to 8, 4 to 9, 4 to 10, 4 to 11, 4 to 12, 5 to 6, 5 to 7, 5 to 8, 5 to 9, 5 10, 5 to 11, 5 to 12, 6 to 7, 6 to 8, 6 to 9, 6 to 10, 6 to 11, 6 to 12, 7 to 8, 7 to 9, 7 to 10, 7 to 11, 7 to 12, 8 to 9, 8 to 10, 8 to 11, 8 to 12, 9 to 10, 9 to 11, 9 to 12, 10 to 11, 10 to 12, 11 to 12, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12). In some embodiments, y is 2 to 8 (e.g., 2 to 3, 2 to 4, 2 to 5, 2 to 6, 2 to 7, 3 to 4, 3 to 5, 3 to 6, 3 to 7, 3 to 8, 4 to 5, 4 to 6, 4 to 7, 4 to 8, 5 to 6, 5 to 7, 5 to 8, 6 to 7, 6 to 8, 7 to 8, 2, 3, 4, 5, 6, 7, 8). In some embodiments, z is 2 to 14 (e.g., 2 to 3, 2 to 4, 2 to 5, 2 to 6, 2 to 7, 2 to 8, 2 to 9, 2 to 10, 2 to 11, 2 to 12, 2 to 13, 3 to 4, 3 to 5, 3 to 6, 3 to 7, 3 to 8, 3 to 9, 3 to 10, 3 to 11, 3 to 12, 3 to 13, 3 to 14, 4 to 5, 4 to 6, 4 to 7, 4 to 8, 4 to 9, 4 to 10, 4 to 11, 4 to 12, 4 to 13, 4 to 14, 5 to 6, 5 to 7, 5 to 8, 5 to 9, 5 to 10, 5 to 11, 5 to 12, 5 to 13, 5 to 14, 6 to 7, 6 to 8, 6 to 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71
[0292] Examples of organic compounds (eg, nanostructured organic compounds, organic compound 1100) include terephthalic acid, terephthalate esters, dimethyl terephthalate, bis(2-hydroxyethyl)terephthalate, ethylene glycol, phthalic acid, phenolic acid, and isophthalic acid.
[0293] In certain embodiments, the organic compound 1100 is partially crystalline, ie, comprises an amorphous phase and a crystalline phase.
[0294] In certain embodiments, the organic compound 1100 is in a crystalline phase and is free of an amorphous phase.
[0295] In certain embodiments, the organic compound 1100 has a nanostructure. Typically, in such embodiments, the organic compound 1100 forms nanoclusters having a size of at least 1 nanometer (e.g., at least 2, at least 5, at least 10, at least 10, at least 20, at least 50) nanometers (nm) and / or at most 200 (e.g., at most 150, at most 100) nm.
[0296] In some embodiments, a composite according to the present disclosure (e.g., a nanostructured organic compound, composite 1000) includes at least 1 (e.g., at least 2, at least 3, at least 4, at least 5) individual organic compounds (see Examples 17 and 18). In some embodiments, at least a portion (e.g., all) of the individual organic compounds are partially crystalline. In some embodiments, at least a portion (e.g., all) of the different organic compounds are crystalline. In some embodiments, at least a portion (e.g., all) of the different organic compounds are nanostructured.
[0297] In certain embodiments, the composite 1000 comprises at least 5 wt.% (e.g., at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 40, at least 45, at least 50) and / or at most 99 wt.% (e.g., at most 95, at most 90, at most 85, at most 80, at most 75, at most 70, at most 65, at most 60, at most 55, at most 50) of an organic compound (e.g., terephthalic acid) 1100.
[0298] Examples of metal oxide crystals 1200 include tin oxides (e.g., tin (IV) oxide (SnO2), tin (II) oxide (SnO)), zinc oxides (e.g., zinc oxide (ZnO), zinc peroxide (ZnO2)), calcium oxides, lithium oxides, potassium oxides, lead oxides, iron oxides, molybdenum oxides, cobalt oxides, chromium oxides, niobium oxides, and manganese oxides. In some embodiments, metal oxide crystals 1200 include semiconductor metals such as germanium oxide or silicon oxide. In some embodiments, metal oxide crystals 1200 include Sn, Fe, Mo, Co, Cr, Nb, Mn, Zn, Ge, and / or Si.
[0299] In some embodiments, the composite 1000 comprises at least 1 (e.g., at least 5, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 40, at least 45, at least 50) wt.% and / or at most 95 wt.% (e.g., at most 90, at most 85, at most 80), at most 75, at most 70, at most 65, at most 60, at most 55, at most 50) metal oxide crystals (e.g., SnO2) 1200.
[0300] In some embodiments, the metal oxide crystals 1200 form nanoparticles. In such embodiments, the metal oxide crystals 1200 have a nanometer size of at least 1 nm (e.g., at least 2, at least 3, at least 4, at least 5) and / or up to 100 nm (e.g., at most 50, at most 20, at most 10, at most 5).
[0301] In some embodiments, the amount of crystalline metal oxide 1200 in the interior region (in the bulk) of the composite 1000 is greater than the amount of crystalline metal oxide 1200 of the material 1000 at the surface. In such embodiments, the amount of crystalline metal oxide 1200 in the interior region of the composite 1000 (i.e., the bulk amount) is at least 1 wt.% (e.g., at least 5, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 40, at least 45, at least 50) and / or at most 95 wt.% (e.g., at most 90, at most 85, at most 80, at most 75, at most 70, at most 60, at most 50), and / or the amount of crystalline metal oxide 1200 at the surface of the composite 1000 is at least 0.1 wt.% (e.g., at least 0.5, at least 1, at least 2, at least 5, at least 10, at least 15, at least 20) and / or at most 80 wt.% (e.g., at most 70, at most 60, at most 50). Without being bound by theory, the crystalline metal oxide (e.g., SnO2) 1200 particles are covered by a layer of organic compound (e.g., terephthalic acid) 1100, resulting in the crystalline metal oxide 1200 particles being incorporated into the bulk organic compound 1100, so that there is more crystalline metal oxide 1200 in the bulk relative to the surface of the composite 1000.
[0302] In certain embodiments, a composite of the invention (e.g., a composite comprising a nanostructured organic compound, composite 1000) has a diameter of at least 1 nm (e.g., at least 2, at least 3, at least 4, at least 5, at least 6, at least 7, at least 8, at least 9, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 40, at least 45, at least 50, at least 55, at least 60, at least 65, at least 70, at least 75, at least 80, at least 85, at least 90, at least 95) and / or at most 100 nm (e.g., at most 95, at most 90, at most 85, at most 80, at most 75, at most 70, at most 65, at most 60, at most 55, at most 50, at most 45, at most 40, at most 35, at most 30, at most 25, at most 20, at most 15, at most 10, at most 9, at most 8, at most 7, at most 6, at most 5, at most 4, at most 3, at most 2).
[0303] The composites of the present disclosure (e.g., composites containing nanostructured organic compounds, composite 1000) have sizes ranging from 1 nanometer (e.g., at least 10, at least 20, at least 50, at least 100, at least 150) nanometers and / or up to 200 nanometers (e.g., up to 100, up to 50, up to 20, up to 10).
[0304] The composites of the present disclosure (e.g., composites containing nanostructured organic compounds, composite 1000) can form a size of at least 0.01 micrometers (e.g., at least 0.1, at least 1, at least 5, at least 10, at least 50, at least 100) μm and / or at most 100 micrometers (e.g., at most 50, at most 10, at most 5, at most 1). In certain embodiments, the particles include particles with a size range of at least 1 nanometer (e.g., at least 10, at least 20, at least 50, at least 100, at least 150) and / or at most 200 nanometers (e.g., at most 100, at most 50, at most 20, at most 10) nm. In certain embodiments, the particle size is 1 nanometer (e.g., at least 5, at least 10, at least 50, at least 100, at least 200, at least 500) and / or at most 1000 nanometers (e.g., at most 500, at most 200, at most 100, at most 50, at most 10, at most 5).
[0305] In certain embodiments, the composite of the present disclosure (e.g., composite containing nanostructured organic compounds, composite 1000) has a specific surface area ranging from at least 10 m2 / g (e.g., at least 15, at least 17, at least 20) and / or at most 50 m2 / g (e.g., at most 45, at most 40, at most 35, at most 30, at most 25, at most 21, at most 20). The measurement of specific surface area is described in detail in Example 8.
[0306] In some embodiments, the disclosed composite (e.g., composite comprising a nanostructured organic compound, composite 1000) has a bulk conductivity in the range of at least 5 S m / s at a pressure of 6.3 MPa. -1 (e.g., at least 10, at least 20, at least 50, at least 100, at least 150, at least 200, at least 250, at least 300, at least 350, at least 40, at least 450, at least 500) and / or up to 5000 S m -1 (e.g., at most 4000, at most 3000, at most 2000, at most 1500, at most 1000, at most 900, at most 800, at most 700, at most 600, at most 500). The measurement of bulk conductivity is described in detail in Example 10 below. Without being bound by theory, the relatively high conductivity of the composite 1000 is attributed to the presence of the metal oxide crystals (e.g., SnO2) 1200 particles. For example, although the crystalline metal oxide (e.g., SnO2) 1200 is a semiconductor, it still exhibits metallic conductivity due to various reasons including the presence of oxygen vacancies.
[0307] Figure 2 An embodiment of a composite 2000 of the present disclosure is shown. The composite 2000 includes Figure 1 Components of the composite 1000 and the silicon-containing material 2300 and graphene nanosheets 2400 dispersed in the organic compound 1100. Without being bound by theoretical values, the silicon-containing material 2300 is embedded in the organic compound 1100.
[0308] In some embodiments, the nanostructured organic compound (eg, nanostructured terephthalic acid) comprises a silicon-containing material and graphene nanosheets dispersed in the nanostructured organic compound.
[0309] In certain embodiments, the disclosed composite (e.g., nanostructured organic compound, composite 2000) contains at least 0.1 wt.% (e.g., at least 0.5, at least 1, at least 5, at least 10) and / or at most 95 wt.% (e.g., at most 90, at most 85) of silicon-containing material 2300. In certain embodiments, the silicon-containing material 2300 is elemental silicon. In certain embodiments, the silicon-containing material 2300 is silicon nanoparticles. In certain embodiments, the silicon-containing material 2300 has a size range of at least 1 nm (e.g., at least 2, at least 3, at least 4, at least 5) and / or at most 1000 nm (e.g., at most 500, at most 200, at most 100, at most 50, at most 20, at most 10, at most 5).
[0310] In some embodiments, the composite (e.g., nanostructured organic compound, composite 2000) according to the present disclosure contains at least 0.1 wt.% (e.g., at least 0.5, at least 1, at least 5, at least 10) and / or at most 50 wt.% (e.g., at most 45, at most 40) of graphene nanosheets 2400. In some embodiments, the graphene nanosheets 2400 include sheets having at least 1 nm (e.g., at least 2, at least 5, at least 10, at least 20, at least 50, at least 100) and / or at most 5 μm (e.g., at most 4, at most 3, at most 2, at most 1). In some embodiments, the graphene nanosheets 2400 have at least 1 layer (e.g., at least 2 layers, at least 3 layers, at least 4 layers, at least 5 layers) and / or at most 100 layers (e.g., at most 90 layers, at most 80 layers, at most 70 layers, at most 60 layers, at most 50 layers, at most 40 layers, at most 30 layers, at most 20 layers, at most 10 layers). In some embodiments, the carbon purity of the graphene nanosheet 2400 is at least 90% (e.g., at least 91, at least 92, at least 93, at least 94, at least 95). In some embodiments, the graphene nanosheet 2400 contains functional groups (e.g., hydroxyl, carbonyl, carboxyl and / or amino) on its surface.
[0311] In certain embodiments, the graphene nanosheets 2400 cover at least a portion of the crystalline metal oxide 1200 and / or the silicon-containing material 2300 .
[0312] Figure 2 Embodiments are shown, but in some embodiments, the composite 2000 includes a silicon-containing material 2300 in addition to the organic compound 1100 and the crystalline metal oxide 1200, but does not include the graphene nanosheet 2400. Furthermore, in some embodiments, the composite 2000 includes a graphene nanosheet 2400 in addition to the organic compound 1100 and the crystalline metal oxide 1200, but does not include the silicon-containing material 2300.
[0313] The disclosed composites may include an organic compound and a metal organic framework embedded in the organic compound. In some embodiments, the organic compound is in a partially crystalline state. In some embodiments, the organic compound is crystalline. In some embodiments, the organic compound is nanostructured. In some embodiments, the metal organic framework is at least partially crystalline. In some embodiments, the metal organic framework is crystalline. In some embodiments, the metal organic framework has a nanostructure. In some embodiments, the metal organic framework is nanocrystalline.
[0314] In certain embodiments, the composites of the present disclosure (eg, nanostructured organic compounds, composite 1000 , composite 2000 ) may include a metal organic framework embedded in an organic compound.
[0315] In certain embodiments, the metal-organic framework includes the organic compound and the metal.
[0316] In some embodiments, the metal organic framework chemical molecule has the general formula MC x H y O z nH2O, wherein M is a metal and n ranges from 0 to 5. In some embodiments, n is 0, 1, 2 or 3.5. In some embodiments, the molecular formula of the metal organic framework is MC x H y O z ·3.5H2O. In some embodiments, the metal organic framework has the general formula MC x H y O zIn some embodiments, x is 2 to 12 (e.g., 2 to 3, 2 to 4, 2 to 5, 2 to 6, 2 to 7, 2 to 8, 2 to 9, 2 to 10, 2 to 11, 3 to 4, 3 to 5, 3 to 6, 3 to 7, 3 to 8, 3 to 9, 3 to 10, 3 to 11, 3 to 12, 4 to 5, 4 to 6, 4 to 7, 4 to 8, 4 to 9, 4 to 10, 4 to 11, 4 to 12, 5 to 6, 5 to 7, 5 to 8, 5 to 9, 5 to 10, 5 to 11, 5 to 12, 6 to 7, 6 to 8, 6 to 9, 6 to 10, 6 to 11, 6 to 12, 7 to 8, 7 to 9, 7 to 10, 7 to 11, 7 to 12, 8 to 9, 8 to 10, 8 to 11, 8 to 12, 9 to 10, 9 to 11, 9 to 12, 10 to 11, 10 to 12, 11 to 12, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12). In some embodiments, y is 2 to 8 (e.g., 2 to 3, 2 to 4, 2 to 5, 2 to 6, 2 to 7, 3 to 4, 3 to 5, 3 to 6, 3 to 7, 3 to 8, 4 to 5, 4 to 6, 4 to 7, 4 to 8, 5 to 6, 5 to 7, 5 to 8, 6 to 7, 6 to 8, 7 to 8, 2, 3, 4, 5, 6, 7, 8). In some embodiments, z is 2 to 14 (e.g., 2 to 3, 2 to 4, 2 to 5, 2 to 6, 2 to 7, 2 to 8, 2 to 9, 2 to 10, 2 to 11, 2 to 12, 2 to 13, 3 to 4, 3 to 5, 3 to 6, 3 to 7, 3 to 8, 3 to 9, 3 to 10, 3 to 11, 3 to 12, 3 to 13, 3 to 14, 4 to 5, 4 to 6, 4 to 7, 4 to 8, 4 to 9, 4 to 10, 4 to 11, 4 to 12, 4 to 13, 4 to 14, 5 to 6, 5 to 7, 5 to 8, 5 to 9, 5 to 10, 5 to 11, 5 to 12, 5 to 13, 5 to 14, 6 to 7, 6 to 8, 6 to 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71
[0317] The metals include Zn, Fe, Cu, Al, Zr, Cr, Co, Li, Na and K.
[0318] In some embodiments, the size range of the resulting composite particles includes a minimum of 0.5 μm (e.g., minimum 1, minimum 5, minimum 10, minimum 15, minimum 20, minimum 30, minimum 40, minimum 50, minimum 60, minimum 70, minimum 80, minimum 90, minimum 100, minimum 150, minimum 200, minimum 250, minimum 300, minimum 350, minimum 400, minimum 450, minimum 500, minimum 550) and / or a maximum of 600 μm (e.g., maximum 550, maximum 500, maximum 450, maximum 400, maximum 350, maximum 300, maximum 250, maximum 200, maximum 150, maximum 100, maximum 90, maximum 80, maximum 70, maximum 60, maximum 50, maximum 40, maximum 30, maximum 20, maximum 15, maximum 10, maximum 5, maximum 1) μm. In some embodiments, the particle size range includes plate-like particles of at least 10 nm (e.g., at least 20, at least 50, at least 100, at least 500, at least 1000, at least 5000) and / or at most 10000 nm (e.g., at most 5000, at most 1000, at most 500, at most 20). In some embodiments, the plate-like particles have a thickness of at least 1 nm (e.g., at least 2, at least 3, at least 4, at least 5, at least 6, at least 7, at least 8, at least 9) and / or at most 10 nm (e.g., at most 9, at most 8, at most 7, at most 6, at most 5, at most 4, at most 3, at most 2). In some embodiments, the platelet particle size range includes at least 1 nm (e.g., at least 2, at least 3, at least 4, at least 5, at least 6, at least 7, at least 8, at least 9, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 35, at least 40, at least 45, at least 50, at least 55) and / or up to 60 nm (e.g., up to 55, up to 50, up to 45, up to 40, up to 35, up to 30, up to 25, up to 20, up to 15, up to 10, up to 9, up to 8, up to 7, up to 6, up to 5, up to 4, up to 3, up to 2). In some embodiments, the particles have a size range of at least 1 nm (e.g., at least 2, at least 3, at least 4, at least 5, at least 6, at least 7, at least 8, at least 9, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 35, at least 40, at least 45, at least 50, at least 55) and / or at most 60 nm (e.g., at most 55, at most 50, at most 45, at most 40, at most 35, at most 30, at most 25, at most 20, at most 15, at most 10, at most 9, at most 8, at most 7, at most 6, at most 5, at most 4, at most 3, at most 2).In some embodiments, the particle size range includes metal-organic framework crystals of at least 10 nm (e.g., at least 50, at least 100, at least 500, at least 1000, at least 5000) and / or up to 10000 nm (e.g., at most 5000, at most 1000, at most 500, at most 100, at most 50).
[0319] In some embodiments, the metal organic framework has an average domain size ranging from at least 30 nm (e.g., at least 35, at least 40, at least 45, at least 50, at least 55) and / or at most 60 nm (e.g., at least 55, at least 50, at least 45, at least 40, at least 35).
[0320] In certain embodiments, the disclosed composites (e.g., nanostructured organic compounds, composite 1000, composite 2000) may include a tin-containing component. Examples of tin-containing components include metallic tin, tin chloride, tin chloride hydrate, tin hydroxide, and tin hydroxide oxide chloride. In certain embodiments, the molecular formula of tin hydroxide is Sn. 21 Cl 16 (OH) 14 Without being bound by theory, tin chloride hydroxide may be formed during the hydrolysis of SnCl in the solvent contacting step (see discussion below), for example, by washing with distilled water, as shown in the following reaction:
[0321] 21SnCl2+20H2O=Sn 21 Cl 16 (OH) 14 O6+26HCl (1)
[0322] Since tin hydroxide chloride has a relatively low solubility in water, it remains in the organic compound (eg, nanostructures of terephthalic acid) after washing and filtering.
[0323] In some embodiments, at least a portion of the tin-containing component is crystalline. In some embodiments, the tin-containing component is crystalline. In some embodiments, the tin-containing member has a nanostructure. In some embodiments, the tin-containing member forms a particle size of at least 1 nm (e.g., at least 2, at least 3, at least 4, at least 5, at least 6, at least 7, at least 8, at least 9, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 40, at least 45, at least 50, at least 55, at least 60, at least 65, at least 70, at least 75, at least 80, at least 85, at least 90, at least 95) and / or at most 100 nm (e.g., at most 95, at most 90, at most 85, at most 80, at most 75, at most 70, at most 65, at most 60, at most 55, at most 50, at most 45, at most 40, at most 35, at most 30, at most 25, at most 20, at most 15, at most 10, at most 9, at most 8, at most 7, at most 6, at most 5, at most 4, at most 3, at most 2).
[0324] In certain embodiments, the disclosed composites (eg, nanostructured organic compounds, composite 1000, composite 2000) may include metals. Examples of metals include Sn, Zn, Fe, Cu, Ni, Cr, Al, and Co.
[0325] In some embodiments, the disclosed composites (e.g., composite 1000 of nanostructured organic compounds, composite 2000) are prepared at a concentration of 0.5 g L -1 Under the conditions, it has an absorbance of at least 1 a.u. (e.g., at least 1.1, at least 1.2, at least 1.3, at least 1.4, at least 1.5, at least 1.6, at least 1.7, at least 1.8, at least 1.9) and / or a maximum of 2 a.u. absorbance (e.g., maximum 1.9, maximum 1.8, maximum 1.7, maximum 1.6, maximum 1.5, maximum 1.4, maximum 1.3, maximum 1.2, maximum 1.1) at 242 nm. In some embodiments, the disclosed composites (e.g., composite 1000 of nanostructured organic compounds, composite 2000) have an absorbance of at least 0.1 au (e.g., at least 0.2, at least 0.3, at least 0.4, at least 0.5, at least 0.6, at least 0.7) and / or an absorbance of at most 0.8 au (e.g., at most 0.7, at most 0.6, at most 0.5, at most 0.4, at most 0.3, at most 0.2), wherein the absorbance at 450 nm is 0.5 g L -1In some embodiments, the disclosed composites (e.g., composite 1000 of nanostructured organic compounds, composite 2000) have an absorbance of at least 0.1 au (e.g., at least 0.2, at least 0.3, at least 0.4, at least 0.5, at least 0.6, at least 0.7) and / or up to 0.8 au absorbance (e.g., up to 0.7, up to 0.6, up to 0.5, up to 0.4, up to 0.3, up to 0.2), wherein the absorbance at 500 nm is 0.5 g L -1 In some embodiments, the disclosed composites (e.g., composite 1000 of nanostructured organic compounds, composite 2000) have an absorbance of at least 0.1 au (e.g., at least 0.2, at least 0.3, at least 0.4, at least 0.5, at least 0.6, at least 0.7) and / or up to 0.8 (e.g., up to 0.7, up to 0.6, up to 0.5, up to 0.4, up to 0.3, up to 0.2) au, wherein the absorbance is at 317 nm and 0.5 g L -1 Measured at a concentration of .
[0326] In some embodiments, the disclosed composites (e.g., composites comprising at least a portion of a crystalline organic compound metal oxide; composites comprising a nanostructured organic compound, the composite comprising a composite having a molecular formula of C x O y H z Multiple molecules; the complex includes a complex of an organic compound and a metal organic framework embedded in an organic compound; or a complex including an organic compound and a crystalline metal oxide) also includes transition metal disulfides. Such transition metal disulfides include compounds with the empirical formula MX2, where M is a transition metal atom (such as Mo or W) and X is a chalcogen atom (such as S, Se or Te). Without being bound by theoretical values, in some embodiments, molten salts (see discussion below) can prevent transition metal disulfides from being oxidized at temperatures above 300°C, at which temperatures these compounds would normally undergo oxidation reactions. In some embodiments, the transition metal disulfide is a two-dimensional transition metal disulfide. In some embodiments, the transition metal disulfide is embedded in an organic compound and / or a metal oxide (if present), and without being bound by theoretical values, it is believed that it can enhance the structural integrity and conductivity of the composite. Without being bound by theoretical values, the kinetic reaction rate of metal ions in the insertion and deintercalation of electrodes containing such composites can be enhanced. In some embodiments, the presence of one or more transition metal disulfides in accordance with the disclosed content can improve the rate capability of the resulting electrode for metal ion secondary battery applications, such as electrodes for lithium ion batteries, sodium ion batteries, and potassium ion batteries (see discussion below).
[0327] Electrodes and energy storage devices
[0328] like Figure 3 As shown in the schematic diagram of FIG. 1 , the composite 1000 can be used to manufacture an electrode 3000, such as an anode. Figure 3 One embodiment is shown, but in some embodiments, the electrode 3000 includes the composite 2000, the nanostructured organic compound, and / or the composite including an organic compound embedded in the organic compound and a metal organic framework, instead of the composite 1000. In some embodiments, in addition to the composite 1000, the composite 2000, the nanostructured organic compound, and / or the composite including an organic compound embedded in the organic compound and a metal organic framework, the electrode 3000 also contains a binder (e.g., polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polytetrafluoroethylene, polyvinyl alcohol (PVA), polyglutamic acid (PGA), sodium alginate (SA), chitosan (CS), polyacrylonitrile (PAN), polyimide (PI), colloid), a solvent (e.g., N-methyl-2-pyrrolidone (NMP), water), conductive carbon, copper foil and / or graphene nanosheets. Optionally, the electrode 3000 may include one or more additional components as appropriate.
[0329] Typically, electrode 3000 can be used in an energy storage device, such as a battery or a supercapacitor. As an example, Figure 4 A single cell of battery 4000 is shown, including electrode 3000 as an anode, cathode 4100, electrolyte 4200, and separator 4300 between anode 3000 and cathode 4100. The described battery 4000 system also includes a wire 4500 and a load 4600 connecting anode 3000 and cathode 4100. Battery 4000 includes a variety of batteries. Examples of battery applications include lithium ion batteries, sodium ion batteries, calcium ion batteries, and potassium ion batteries.
[0330] Without being bound by theory, the crystalline metal oxide (e.g., SnO2) 1200 can become an active material in the electrode 3000. In addition, without being bound by theory, it is believed that the presence of the organic compound (e.g., terephthalic acid) 1100 can reduce (e.g., prevent) the decomposition of the crystalline metal oxide (e.g., SnO2) 1200 relative to the organic compound (e.g., terephthalic acid) 1100 because the organic compound (e.g., terephthalic acid) 1100 can support the integrity of the electrode 3000, can reduce (e.g., prevent) the degradation of the crystalline metal oxide (e.g., SnO2) 1200, and / or can maintain good contact between the crystalline metal oxide (e.g., SnO2) 1200 particles and the electrode integrity.
[0331] Without being bound by theory, these properties may result at least in part from hydrogen bonding between the crystalline metal oxide 1200 and the organic compound 1100 (eg, hydrogen bonding between the oxygen of SnO 2 and the hydrogen of terephthalic acid).
[0332] Without being bound by theory, the disclosed composites (e.g., composite 1000 and / or composite 2000), for example when in the form of electrode 3000, can have desirable properties resulting from a lower charge transfer resistance due to the uniform distribution of the crystalline metal oxide (e.g., SnO2) 1200 particles within the organic compound (e.g., terephthalic acid) 1100 matrix.
[0333] In certain embodiments, the electrode 3000 has a discharge capacity of at least 10 mA h / g ("Li-ion") (e.g., at least 20, at least 50, at least 100, at least 150, at least 200, at least 250, at least 300, at least 350, at least 400, at least 450, at least 500) mA h / g -1 ) and / or up to 1500mA hg -1 Specific capacity (e.g., at 200 mA g -1 After 500 cycles at a current density of up to 1400, up to 1300, up to 1200, up to 1100, up to 1000, up to 950, up to 900, up to 850, up to 800, up to 750, up to 700, up to 650, up to 600, up to 550, up to 500mA hg -1 ). In certain embodiments, the electrode has a lithium ion discharge capacity of at least 100 (e.g., 200, at least 500) milliampere hours (mAh) per gram of metal oxide crystals, and a lithium ion discharge capacity of up to 1800 (e.g., up to 1700, up to 1600) mAh per gram of metal oxide crystals after 500 cycles. The results of the measurement of the lithium ion discharge capacity are described in Example 11.
[0334] In some embodiments, the electrode 3000 is subjected to 100 mA g -1 After 10 cycles at a current density of at least 300 (e.g., at least 400, at least 500, at least 600, at least 700, at least 800, at least 900, at least 1000) mA h g -1 and / or up to 1500mA hg -1 (e.g., up to 1400, up to 1300, up to 1200, up to 1100, up to 1000). In some embodiments, the electrode 3000 is at 500 mA g -1After 30 cycles at a current density of at least 200 (e.g., at least 300, at least 400, at least 500, at least 600, at least 700, at least 800, at least 900, at least 1000) mA h g -1 and / or up to 1500mAh g -1 (e.g., up to 1400, up to 1300, up to 1200, up to 1000) specific capacity. In certain embodiments, the electrode 3000 has a specific capacity of 1000 mA g -1 After 50 cycles at a current density of at least 200 (e.g., at least 300, at least 400, at least 500, at least 600, at least 700, at least 800, at least 900, at least 1000) mA h g -1 and / or up to 1500 (e.g., up to 1400, up to 1300, up to 1200, up to 1000) mAh g -1 In some embodiments, the electrode 3000 has a specific capacity of 1100 mA g -1 After 60 cycles at a current density of at least 50 (e.g., at least 100, at least 200, at least 300, at least 400, at least 500, at least 600, at least 700, at least 800, at least 900, at least 1000) mAh g -1 and / or up to 1300 (e.g., up to 1200, up to 1000) mAh g -1 In some embodiments, the electrode has a specific capacity of at least 100 mAh g after 500 cycles. -1 The lithium ion discharge capacity (e.g., at least 200, at least 300, at least 400, at least 500, at least 600, at least 700, at least 800, at least 900, at least 1000, at least 1100, at least 1200, at least 1300, at least 1400, at least 1500, at least 1600, at least 1700) mAhg -1 and / or up to 1800 (e.g., up to 1700, up to 1600, up to 1500, up to 1400, up to 1300, up to 1200, up to 1100, up to 1000, up to 900, up to 800, up to 700, up to 600, up to 500, up to 400, up to 300, up to 200) milliampere-hours per gram.
[0335] Without being bound by theory, the lithium ion discharge capability of electrode 3000 is due at least in part to the relatively small average size of the crystalline metal oxide (e.g., SnO2) 1200 particles and the presence of the organic compound (e.g., terephthalic acid) 1100, which affects the performance of the electrode as described above.
[0336] In some embodiments, the electrode has a coulombic efficiency of at least 70% (e.g., at least 75, at least 80, at least 85, at least 90, at least 95) and / or up to 120 (e.g., up to 115, up to 100, up to 105, up to 100) after 500 cycles. Measurement of coulombic efficiency is described in Example 11 below.
[0337] Without being constrained by theoretical values, the reactions that occur during the lithiation-delithiation cycle are:
[0338] SnO2+4Li + +4e→Sn+2Li2O (2a)
[0339]
[0340] In some embodiments, after 150 cycles of a half-cell comprising an electrode 3000 and an electrolyte, the electrolyte resistance increases by at least 1.0 Ω (e.g., at least 1.5, at least 2.0, at least 2.5, at least 3.0, at least 3.0, at least 4.0) Ω and / or up to 6.0 Ω (e.g., up to 5.5, up to 5.0, up to 4.5, up to 4.0, up to 3.5, up to 3.0). In some embodiments, after 300 cycles of a half-cell comprising an electrode 3000 and an electrolyte, the resistance increases by at least 2.0 (e.g., at least 2.5, at least 3.0, at least 3.5, at least 4.0) Ω and / or up to 8.0 (e.g., up to 7.5, up to 7.0, up to 6.5, up to 6.0, up to 5.5, up to 5.0, up to 4.5, up to 4.0, up to 3.5, up to 3.0) Ω. The measurement of electrolyte resistance is described in Example 11 below.
[0341] In some embodiments, the electrode 3000 has at least 10 -11 (For example, at least 2×10 -11 , at least 3×10 -11 , at least 4×10 -11 , at least 5×10 -11 , at least 6×10 -11 , at least 7×10 -11 , at least 8×10 -11 , at least 9×10 -11 )cm 2 s -1 and / or up to 9×10 -9 (For example, after 150 cycles, the maximum -9 , up to 7×10 -9 , up to 6×10 -9 , up to 5×10 -9 , up to 4×10 -9 , up to 3×10-9 , up to 2×10 -9 , up to 10 -9 )cm 2 s -1 In some embodiments, the electrode 3000 has at least 2×10 -11 cm 2 s -1 The lithium ion diffusion rate (e.g., at least 3×10 -11 , at least 4×10 -11 , at least 5×10 -11 , at least 6×10 -11 , at least 7×10 -11 , at least 8×10 -11 , at least 9×10 -11 , at least 10-10) and / or up to 10 -8 (For example, after 300 cycles, the maximum -9 , up to 8×10 -9 , up to 7×10 -9 , up to 6×10 -9 , up to 5×10 -9 , up to 4×10 -9 , up to 3×10 -9 , up to 2×10 -9 , up to 10 -9 )cm 2 s -1 The measurement of lithium ion diffusion rate is described in Example 11 below.
[0342] Without being bound by theoretical values, the enhancement of the lithium ion diffusion rate of the electrode 3000 can be attributed to the morphology of the composite 1000 and / or 2000, in which particles of the crystalline metal oxide (e.g., SnO2) 1200 are embedded in the organic compound (e.g., terephthalic acid) 1100. The electrode 3000 can exhibit good ionic conductivity and healing ability because the organic compound (e.g., terephthalic acid) 1100 can effectively form an ion transport channel. The organic compound (e.g., terephthalic acid) 1100 matrix can effectively accommodate the volume change caused by the lithiation / delithiation of the crystalline metal oxide (e.g., SnO2) 1200 during long-term cycles, which promotes the lithium ion diffusion rate due to the hydrogen bonds formed between the two components.
[0343] Without being bound by theoretical values, the lithium ion diffusion rate in the cycled electrode containing composites 1000 and / or 2000 is increased relative to the non-cycled electrode containing composites 1000 and / or 2000 because the volume changes involved in the cycle cause the pulverization of the crystalline metal oxide (e.g., SnO2) 1200 particles to be converted into particles with smaller particle sizes, and then the fine particles in the organic compound 1100 matrix are rearranged and new hydrogen bonds are formed between the fine crystalline metal oxide (e.g., SnO2) 1200 particles and the organic compound (e.g., terephthalic acid) 1100. These interactions and structural reconstructions can lead to an increase in the surface area of the active material, a shortened lithium ion diffusion distance, and / or a decrease in the electron and lithium ion Li at the active material / electrolyte interface. + Transmission enhancement.
[0344] In some embodiments, sodium ions (“Na + The voltage of the ion insertion electrode 3000 is at least 0.1 (e.g., at least 0.11, at least 0.12, at least 0.13, at least 0.14, at least 0.15, at least 0.16, at least 0.17, at least 0.18, at least 0.19, at least 0.2, at least 0.25, at least 0.3, at least 0.35, at least 0.4, at least 0.45, at least 0.5, at least 0.55, at least 0.6, at least 0.65, at least 0.7, At least 0.75, at least 0.8, at least 0.85) V and / or up to 0.9 (e.g., up to 0.85, up to 0.8, up to 0.75, up to 0.7, up to 0.65, up to 0.6, up to 0.55, up to 0.5, up to 0.45, up to 0.4, up to 0.35, up to 0.3, up to 0.25, up to 0.2, up to 0.15) V. In some embodiments, the sodium ions (“Na + ions") voltage is at a voltage of at least 0.3 (e.g., at least 0.4, at least 0.5, at least 0.6) V and / or at most 0.7 (e.g., at most 0.6, at most 0.5, at most 0.4) V.
[0345] In some embodiments, the binder includes PI. Without being bound by theory, an electrode including a disclosed composite with SiNPs, PI, and heat-treating the electrode can provide an electrode with enhanced electrochemical performance. The heat treatment can include heating to a temperature of at least 150°C (e.g., at least 200, at least 250)°C and / or up to 400°C (e.g., up to 350, up to 300, up to 250, up to 200)°C in an inert gas atmosphere containing H2. Without being bound by theory, hydrogen bonding between PI and oxygen on the surface of SiNPs can reduce (e.g., inhibit) electrode disintegration caused by expansion and contraction of SiNPs. Without being bound by theory, the formation of charge transfer composite structures within the PI chain during the heat treatment process enhances the toughness of the electrode. In some embodiments, the improved electrochemical performance includes an increased lithium ion specific capacity stability during several cycles of lithium ion insertion and removal, relative to certain other electrode materials.
[0346] In some embodiments, a disclosed electrode including Si (e.g., Si nanoparticles, Si-containing composites of the present disclosure) is heat treated with PI as a binder (referred to herein as "Si@PI") to produce a charge transfer complex (CTC) structure. Without being bound by theory, this CTC structure can improve the electrochemical lithium storage performance of the electrode by forming a dense structure that reduces the charge transfer impedance. Similarly, without being bound by theory, the cycle performance of the silicon negative electrode can be significantly improved. For example, in some embodiments, an electrode containing Si with PI as a binder is heat treated at 350°C (Si@PI-350) and the charge transfer rate is 200 mA g -1 After 30 cycles at the same current density, it exhibited a charge transfer impedance of 37.67Ω and a current density of 2334mAh g -1 Reversible Li + storage capacity, while the pristine (unheat-treated) Si@PI electrode exhibited a charge transfer impedance of 130.4Ω and a storage capacity of 737mAhg -1 The relatively lower lithium storage capacity. -1 At high current density, Si@PI-350 (1001mAh g -1 ) has a much higher specific capacity than Si@PI (455 mAh g -1 ), indicating the efficiency of the CTC structure formed during the heat treatment process. In some embodiments, the Si@PI electrode heat treatment step can significantly affect the lithium ion insertion / extraction cycle performance of SiNPs.
[0347] In some embodiments, the electrode of the present disclosure includes silicon particles and a polymer binder containing an imide monomer. In some embodiments, the electrode of the present disclosure includes SiNPs and PI. For example, such an electrode can be used as an anode of a metal ion battery, such as a lithium ion battery, a sodium ion battery, or a potassium ion battery.
[0348] In some embodiments, the polymer (e.g., PI) comprises an imide group (-CO-N-CO-) on its main molecular chain. In some embodiments, the PI material is a thermoplastic polymer. In some embodiments, the PI material is formed by polycondensation and imidization of 1-(4-aminophenyl)-1,3,3-trimethyl-2H-indene-5-amine (DAPI) and benzophenone-3,3',4,4'-tetracarboxylic dianhydride (BTDA).
[0349] In some embodiments, the particle size of the Si particles is at least 1 (e.g., at least 5, at least 10, at least 50, at least 100, at least 200, at least 400, at least 700, at least 1000, at least 3000, at least 5000) nanometers and / or at most 5000 (e.g., at most 3000, at most 1000, at most 700, at most 400, at most 200, at most 100, at most 50, at most 10, at most 5) nanometers. In some embodiments, the surface of the silicon particles is partially oxidized to form SiO x(x=0.1-2.0). In some embodiments, silicon particles and polymers containing imide monomers are mixed with other additives such as conductive carbon. In some embodiments, silicon particles and polymers containing imide monomers are mixed with other additives such as conductive carbon and at least partially crystalline organic compounds (e.g., crystalline organic compounds). In some embodiments, the partially crystalline organic compound is terephthalic acid. In some embodiments, Si particles are embedded in the crystalline organic compound. In some embodiments, the mixture is heat treated at a target temperature for a certain time under an inert atmosphere. In some embodiments, the target temperature is at least 140°C (e.g., at least 150°C, at least 160°C, at least 180°C, at least 200°C, at least 230°C, at least 250°C, at least 280°C, at least 300°C, at least 318°C, at least 350°C, at least 400°C) and / or up to 400°C (e.g., up to 350°C, up to 318°C, up to 300°C, up to 280°C, up to 250°C, up to 230°C, up to 200°C, up to 180°C, up to 160°C, up to 150°C). In some embodiments, heating is performed at the target temperature for at least 1 second (e.g., at least 5 seconds, at least 10 seconds, at least 10 minutes, at least 30 minutes, at least 1 hour, at least 5 hours) and / or up to 10 hours (e.g., up to 5 hours, up to 1 hour, up to 30 minutes, up to 10 minutes, up to 10 seconds, up to 5 seconds). In some embodiments, the heating atmosphere contains at least 0.1 vol.% and / or up to 100.0 vol.% hydrogen. In some embodiments, the heating atmosphere contains, in addition to hydrogen, argon, nitrogen and / or helium, at least 0.1 vol.% and / or up to 99.9 vol.%.
[0350] Without being bound by theory, the heat treatment process generates hydrogen bonds between the polymer and the oxide present on the surface of the Si particles, which can improve the stability of metal ions during the insertion and extraction cycles compared to some other electrodes. In addition, without being bound by theory, the heat treatment process forms charge transfer complexes within the polymer chain, which can improve the stability of metal ions during the insertion and extraction cycles compared to some other electrodes. Therefore, the increase in electrode cycling stability is related to the cross-linking of the PI polymer.
[0351] In some embodiments, in the presence of the nanostructured organic compound, the PI reacts with the nanostructured organic compound during the heat treatment process to form organic compound crystals whose XRD patterns are different from the XRD patterns of the PI and the nanostructured organic compound. In some embodiments, the reaction occurs at a temperature range of 250 to 400°C.
[0352] Without being bound by theory, in some embodiments, the interaction between the polymer binder and the at least partially crystalline organic compound increases the toughness of the electrode compared to certain other electrodes.
[0353] In some embodiments, the electrode is formed from a mixture containing Si particles and a binder. In some embodiments, the Si particles are incorporated into a composite of the present disclosure (e.g., composite 2000). In some embodiments, the binder is a polymer containing an imide monomer, and the binder is at least 0.1 wt.% (e.g., at least 1, at least 5, at least 10, at least 15, at least 20, at least 25, at least 25, at least 30, at least 35) and / or at most 40 wt.% (e.g., at most 35, at most 30, at most 25, at most 20, at most 15, at most 10, at most 5) wt.%. In some embodiments, the silicon particles are at least 5 wt.% (e.g., at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 40, at least 45, at least 50, at least 55, at least 60, at least 65, at least 70, at least 75, at least 80) at least 85, at least 90) and / or at most 95 wt.% (e.g., at most 90, at most 85, at most 80, at most 75, at most 70, at most 65, at most 60, at most 55, at most 50, at most 45, at most 40, at most 35, at most 30, at most 25, at most 20, at most 15, at most 10 wt.%). In some embodiments, the organic compound (e.g., terephthalic acid) comprises at least 0.1 (e.g., at least 1, at least 5, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 40, at least 45, at least 50, at least 55, at least 60, at least 65, at least 70, at least 75, at least 80, at least 85, at least 90) weight percent and / or up to 95 (e.g., up to 90, up to 85, up to 80, up to 75, up to 70, up to 65, up to 60, up to 55, up to 50, up to 45, up to 40, up to 35, up to 30, up to 25, up to 20, up to 15, up to 10, up to 5, up to 1) weight percent.
[0354] In some embodiments, the PI is insoluble in polar solvents such as NMP after heat treatment. In some embodiments, the electrode is made by mixing materials containing silicon particles, PI and conductive carbon, and the mixture is heat treated at a temperature of at least 200°C (e.g., at least 250°C, at least 300°C, at least 350°C) and / or up to 400°C (e.g., up to 350°C, up to 300°C, up to 250°C). In some embodiments, the electrode has at least 700 (e.g., up to 1000, up to 1500, up to 2000, up to 2500) mA h g after 100 cycles of lithium ion insertion and extraction.-1 and / or up to 3000 (e.g., up to 2500, up to 2000, up to 1500, up to 1000) mA hg -1 In some embodiments, the lithium ion diffusion impedance (R s ) is greater than the lithium ion diffusion resistance (R s ). In some embodiments, the mixture is heat treated at 350°C, and the charge transfer resistance of the electrode is reduced from 130.4Ω to 37.7Ω. In some embodiments, the electrode is made by heat treating a mixture containing a metal ion active material such as Si particles and a polymer containing an imide monomer. The mixture is heat treated at a maximum temperature of 150-400°C for 1 second to 10 hours. The metal ion diffusion impedance (R s ) is at least 10 (e.g., at least 20, at least 30, at least 40, at least 50) Ω and / or at most 60 (e.g., at most 50, at most 40, at most 30, at most 20) Ω.
[0355] Water purification
[0356] The composites disclosed herein (e.g., nanostructured organic compounds, composite 1000, or composite 2000) can be used for water purification (e.g., see Example 19). In some embodiments, the composite includes SnO and / or Sn. SnO and / or Sn can be crystalline. The composites disclosed herein can reduce the concentration of pollutants (e.g., organic pollutants) in aqueous solutions. Without being bound by theory, pollutants can be adsorbed onto the surface of the composite. In addition, without being bound by theory, the composite can photocatalytically degrade pollutants under visible light exposure (e.g., 400-650nm excitation). Application examples of pollutants include hydrocarbons, such as azo dyes, such as methyl yellow, methyl orange, methyl red, Congo red, alizarin yellow, methyl blue, methylene blue, and rhodamine; and xanthate-based compounds, such as potassium ethyl xanthate, sodium isopropyl xanthate, sodium isobutyl xanthate, sodium butyl xanthate, and butyl xanthate. The hydrocarbons may include components of produced petroleum or natural gas, components of crude oil, alkanes (eg, methane, ethane, propane, butane, pentane, hexane), alkenes, alkynes, halogenated compounds, and / or aromatic compounds (eg, benzene, toluene, xylenes).
[0357] In certain embodiments, the composites of the present disclosure have an adsorption capacity of at least 5 (e.g., at least 10, at least 15, at least 20, at least 25) mg / g and / or at most 30 (e.g., at most 25, at most 20, at most 15, at most 10) mg / g as defined by equation (12) in Example 19. In certain embodiments, the composites of the present disclosure have an organic compound removal performance of at least 1 (e.g., at least 2, at least 3, at least 4, at least 5, at least 6, at least 7, at least 8, at least 9) mg / (g×h) and / or at most 10 (e.g., at most 9, at most 8, at most 7, at most 6, at most 5, at most 4, at most 3, at most 2) mg / (g×h) as defined by equation (13) in Example 19.
[0358] Depolymerization of polymers and synthesis of compounds
[0359] Figure 5a A synthesis scheme for nanostructured terephthalic acid is shown. A mixture comprising reactants polyethylene terephthalate (PET) and tin dichloride (SnCl2) is heated to form nanostructured terephthalic acid. The polymer (PET) is depolymerized to form terephthalic acid. In some embodiments, the reactants also include a salt, and heating the mixture causes the salt to become a molten salt.
[0360] Figure 5b A reaction scheme for synthesizing compound 1000 comprising terephthalic acid and SnO2 is shown. A mixture comprising reactants polyethylene terephthalate (PET), tin dichloride (SnCl2), and KCl-LiCl is heated to form compound 1000 (terephthalic acid + SnO2). The polymer (PET) is depolymerized to form terephthalic acid, which forms organic compound 1100 in compound 1000.
[0361] Without being limited by theory, PET depolymerizes in the presence of SnCl2 to form terephthalic acid, with SnCl2 acting as a depolymerizing agent. In the solid phase, SnCl2 exists as a polymer chain. When melted, SnCl2 maintains its polymer structure (SnCl2) n , where Sn 2+ It is tri-coordinated. Further increasing the temperature can reduce the degree of polymerization and thus the viscosity. Without being bound by theory, PET and SnCl2 melt at about 250°C to form two polymer melts. When the temperature is increased to 350°C, free Sn may be generated. 2+ and Cl-, which can break the chain of PET and generate terephthalic acid.
[0362] Typically, the reactants include a polymer (e.g., PET) and a depolymerizing agent (e.g., SnCl2). In some embodiments, the reactants also include a molten salt (e.g., LiCl-KCl). Without being limited by theory, heating the mixture causes the salt to become a molten salt.
[0363] In some embodiments, the depolymerization reaction of the polymer can produce a first organic compound (e.g., terephthalic acid) and a second organic compound (e.g., ethylene glycol), the second organic compound having a lower boiling point than the first organic compound. Without wishing to be bound by theory, if the first organic compound is incorporated into the product of the present disclosure (e.g., the organic compound 1100 in the nanostructured organic compound, composite 1000 or 2000), the second organic compound can be relatively easily separated, for example, by evaporating the second organic compound. In some embodiments, the second organic compound completes evaporation during its formation. In such embodiments, the second organic compound can condense and be collected as a liquid.
[0364] Without being bound by theory, water associated with the depolymerizing agent (e.g., SnCl2, ZnCl2) plays a role in the depolymerization of the polymer as shown in reaction (3):
[0365]
[0366] Hydrated SnCl2 melts at around 258°C, and SnCl2 retains at least a portion (e.g., most) of its water content (see Example 22). In certain embodiments, at least a portion (e.g., all) of the depolymerizing agent is hydrated. In certain embodiments, at least a portion (e.g., all) of the depolymerizing agent retains water until the depolymerizing agent acts to depolymerize the polymer. In certain embodiments, the depolymerizing agent includes at least 0.1 (e.g., at least 0.2, at least 0.3, at least 0.4, at least 0.5, at least 0.6, at least 0.7, at least 0.8, at least 0.9, at least 1, at least 1.5, at least 2, at least 3, at least 4, at least 5, at least 6, at least 7, at least 8, at least 9, at least 10, at least 11, at least 12, at least 13, at least 14, at least 15, at least 16, at least 17, at least 18, at least 19) weight percent water and / or up to 20 (e.g., up to 19, up to 18, up to 17, 17, up to 16, up to 15, up to 14, up to 13, up to 12, up to 11, up to 10, up to 9, up to 8, up to 7, up to 6, up to 5, up to 4, up to 3, up to 2, up to 1.5, up to 1, up to 0.9, up to 0.8, up to 0.7, up to 0.6, up to 0.5, up to 0.4, up to 0.3, up to 0.2) weight percent water. Without being bound by theory, hydration of the reactants (e.g., depolymerizing agent) may be due to moisture in the atmosphere. In certain embodiments, at least a portion (e.g., all) of the depolymerizing agent absorbs moisture from the environment, such as the surrounding atmosphere.
[0367] In certain embodiments, the reactants contain at least 1 (e.g., at least 2, at least 5, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 40, at least 45, at least 50) weight percent and / or at most 95 (e.g., at most 90, at most 85, at most 80, at most 75, at most 70, at most 65, at most 60, at most 55, at most 50) weight percent of the depolymerizing agent.
[0368] In some embodiments, the depolymerizing agent is an inorganic salt. Examples of inorganic salts include tin (II) chloride (SnCl2), zinc chloride (ZnCl2), calcium chloride (CaCl2), lead chloride (PbCl2), sodium chloride (NaCl), potassium chloride (KCl) and ferric chloride (FeCl2).
[0369] In some embodiments, the inorganic salt comprises the metal of the crystalline metal oxide 1200. In some embodiments, the inorganic salt undergoes an oxidation reaction during heating. For example, SnCl2 is oxidized by the action of oxygen in the atmosphere to generate SnO2.
[0370] Without being limited by theory, the phase transformation reaction of SnCl2 to SnO2 nanoparticles is:
[0371] SnCl2+O2(g)→SnO2+Cl2(g) ΔG°=-186.6kJ (4a)
[0372] O2 is consumed to form SnO2, and Cl2 gas product is released.
[0373] Typically, the melting point of the depolymerizing agent is close to the melting point of the polymer material. In certain embodiments, the difference between the melting points of the polymer and the depolymerizing agent is less than 100°C (e.g., less than 95°C, less than 90°C, less than 85°C, less than 80°C, less than 75°C, less than 70°C, less than 65°C, less than 60°C, less than 55°C, less than 50°C).
[0374] Typically, the polymer (e.g., PET) depolymerizes to form an organic compound (e.g., terephthalic acid). In some embodiments, the reactants contain at least 1 (e.g., at least 2, at least 5, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 40, at least 45, at least 50) weight percent and / or at most 99 (e.g., at most 95, at most 90, at least 85, at least 80, at least 75, at least 70, at least 65, at least 60, at least 55, at least 50) weight percent of the polymer. Examples of polymers include polyethylene terephthalate (PET), polyacrylonitrile, poly(6-aminocaproic acid), poly(caprolactam), nylon, polyetheretherketone (PEEK), polyethylene (PE), polyhexamethylene adipamide, polymethyl methacrylate, polyethylene oxide, poly(4-methylpentene), polypropylene, polystyrene, poly(trans-1,4-butadiene), polyvinyl alcohol, polyvinyl chloride (PVC), polyvinyl fluoride, polyvinylidene chloride, and polyvinylidene fluoride. In some embodiments, the polymer is derived from waste plastics.
[0375] Without being bound by theory, it is believed that organic compounds (e.g., terephthalic acid) can sublime and / or decompose at relatively high temperatures (e.g., greater than 500° C., greater than 600° C., greater than 700° C., greater than 800° C.). Without being bound by theory, the phase transition reaction is as follows:
[0376]
[0377] In some embodiments, the salt comprises a chloride molten salt (e.g., LiCl and / or KCl). In some embodiments, the salt contains at least 40 (e.g., at least 45, at least 50, at least 55, at least 60) wt.% and / or at most 80 (e.g., 75, at most 70, at most 65, at most 60, at most 55, at most 50) wt.% of LiCl. In some embodiments, the molten salt contains at least 20 (e.g., at least 25, at least 30, at least 35, at least 40, at least 45, at least 50) wt.% and / or at most 70 (e.g., at most 65, at most 60, at most 55, at most 50, at most 45, at most 40) wt.% of KCl. In some embodiments, the salt contains at least 40 (e.g., at least 45, at least 50, at least 55, at least 60) wt% and / or at most 80 (e.g., 75, at most 70, at most 65, at most 60, at most 55, at most 50) wt% LiCl and / or at least 20 (e.g., at least 25, at least 30, at least 35, at least 40, at least 45, at least 50) wt% and / or at most 70 (e.g., at most 65, at most 60, at most 55, at most 50, at most 45, at most 40) wt% KCl. In some embodiments, the salt contains a eutectic melt mixture of LiCl-KCl. In some embodiments, the melting point of the salt is at least 250 (e.g., at least 300, at least 320) ° C and / or at most 700 (e.g., at most 650, at most 600, at most 550, at most 500) ° C.
[0378] Without being bound by theory, the salt (e.g., a eutectic mixture of KCl-LiCl) provides an ionic environment to enhance the formation of partially crystalline (e.g., crystalline) organic compound (e.g., terephthalic acid) monomers, plays an important role in the formation of porosity within the resulting composite, and supports the phase transformation of the depolymerizing agent to crystalline metal oxide (e.g., molten SnCl2 to SnO2 particles), thereby resulting in the formation of at least partially crystalline organic compound (e.g., terephthalic acid) having crystalline metal oxide (e.g., SnO2) distributed therein.
[0379] In general, the reactions disclosed herein (e.g., Figure 5a -c) can be carried out in any suitable atmosphere. In some embodiments, the reaction of the present disclosure (e.g., Figure 5a -c) is carried out in an atmosphere containing oxygen (e.g., air). In some embodiments, the atmosphere contains at least 1% (e.g., at least 2%, at least 5%, at least 10%, at least 15%, at least 20%, at least 21%) oxygen by volume. In some embodiments, the reactions of the present disclosure (e.g., Figure 5a-c) is carried out under an inert atmosphere (e.g., argon atmosphere, nitrogen atmosphere) and / or hydrogen (as described in Examples 14, 17, and 18 below). In some embodiments, the disclosed reactions (e.g., Figure 5a -c) in an atmosphere containing argon and at least 1 (e.g., at least 2, at least 4, at least 5, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 40, at least 45, at least 50, at least 55, at least 60, at least 65, at least 70, at least 75, at least 80, at least 85, at least 90, at least 95) volume % and / or up to 99 (e.g., at most 95, at most 90, at most 85, at most 80, at most 75, at most 70, at most 65, at most 60, at most 55, at most 50, at most 45, at most 40, at most 35, at most 30, at most 25, at most 20, at most 15, at most 10, at most 5, at most 4, at most 2) volume % hydrogen.
[0380] Without being bound by theory, carrying out the reaction under an inert atmosphere and / or hydrogen can reduce (e.g., prevent) SnCl2 from being oxidized to SnO2 by oxygen in the atmosphere, thereby forming a complex without SnO2, or a complex with less SnO2 amount relative to a reaction carried out in the presence of oxygen, or an oxide with a reduced amount of oxygen. In such embodiments, the complex may include SnO and / or Sn in addition to SnO2 or in place of SnO2. Without being bound by theory, carrying out the reaction under an inert atmosphere and / or hydrogen can change the organic compound product formed by the depolymerization of the polymer. In general, the mixture is heated to a temperature higher than the melting point of the polymer, the melting point of the salt, and the melting point of the depolymerizing agent and / or lower than the carbonization temperature of the polymer and the decomposition temperature of the organic compound. In certain embodiments, the mixture is heated to a maximum temperature of at least 250 (e.g., at least 300, at least 310, at least 350, at least 400, at least 450, at least 500) ° C and / or at most 600 (e.g., at most 550, at most 500, at most 450, at most 400, at most 350, at most 310, at most 300) ° C. In some embodiments, the mixture is maintained at the maximum temperature for at least 0.01 (e.g., at least 0.017, at least 0.1, at least 1, at least 2, at least 5, at least 10, at least 20, at least 30, at least 40, at least 50, at least 60) minutes and / or at most 120 (e.g., at most 110, at most 100, at most 90, at most 80, at most 70, at most 60, at most 50, at most 40, at most 30, at most 20, at most 10) minutes. In some embodiments, the mixture is maintained at the maximum temperature for 1 second. In some embodiments, the mixture is heated at a temperature of at least 1 (e.g., at least 2, at least 3, at least 4, at least 5, at least 10, at least 15, at least 20, at least 30, at least 40, at least 50) °C min.-1 and / or at most 100 (e.g. at most 90, at most 80, at most 70, at most 60, at most 50, at most 40, at most 30, at most 20, at most 10, at most 5) °C min -1 Heating rate.
[0381] In some embodiments, the reaction process of the present disclosure (e.g., Figure 5a -c) comprises cooling the mixture after heating the mixture. In some embodiments, both the cooling and heating steps are performed under the same atmosphere (see discussion above).
[0382] Typically, the reactions disclosed herein (e.g., Figure 5a -c) can be carried out at any suitable pressure. In certain embodiments, the reaction of the present disclosure (e.g., Figure 5a-c) is at least 0.01 (e.g., at least 0.05, at least 0.1, at least 0.2, at least 0.25, at least 0.3, at least 0.4, at least 0.5, at least 0.6, at least 0.7, at least 0.75, at least 0.8, at least 0.9, at least 1, at least 1.5, at least 2, at least 5, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 40, at least 45, at least 50, at least 55, at least 60, at least 65, at least 70, at least 7 ... at least 75, at least 80, at least 90, at least 100, at least 110, at least 120, at least 130, at least 140, at least 150, at least 160, at least 180, at least 190, at least 210, at least 220, at least 230, at least 250, at least 260, at least 270, at least 280, at least 290, at least 310, at least 320, at least 330, at least 350, at least 450, at least 550, at least 60, at least 650, at least 70, at least 750, at least 80, at least 850, at least 90 at least 950, at least 1000, at least 1150, at least 1250, at least 1300, at least 1450, at least 1500, at least 1650, at least 1750, at least 1850, at least 1950, at least 2000, at least 2500, at least 3500, at least 450, at least 550, at least 60, at least 650, at least 70, at least 750, at least 800, at least 1 ... at least 85, at least 90, at least 95) standard atmospheres and / or at most 100 (e.g., at most 95, at least 100, at least 115, at least 1250, at least 1300, at least 1450, at least 1500, at least 1650, at least 1750, at least 1850, at least 1950, at least 2000, at least 2500, at least 3500, at least 450 At most 90, at most 85, at most 80, at most 75, at most 70, at most 65, at most 60, at most 55, at most 50, at most 45, at most 40, at most 35, at most 30, at most 25, at most 20, at most 15, at most 10, at most 5, at most 2, at most 1, at most 0.9, at most 0.8, at most 0.75, at most 0.7, at most 0.6, at most 0.5, at most 0.4, at most 0.3, at most 0.25, at most 0.2, at most 0.1, at most 0.05) standard atmospheric pressure. In certain embodiments, the reactions of the present disclosure (e.g., Figure 5a The reaction shown in -c) was carried out under atmospheric pressure.
[0383] In some embodiments, the reactants and / or complexes are contacted with a solvent during the synthesis process. In some embodiments, the solvent is an aqueous solution (e.g., an alkaline aqueous solution, an acidic aqueous solution) and / or contains a polar organic liquid. In some embodiments, the polar organic liquid is an alcohol (e.g., methanol, ethanol, propanol, butanol).
[0384] In some embodiments, the pH of the solvent is at least 0 (e.g., at least 0.1, at least 1, at least 2, at least 3, at least 4, at least 5, at least 6) and / or at most 7 (e.g., at most 6, at most 5, at most 4, at most 3, at most 2, at most 1). In some embodiments, the solvent contains hydrochloric acid, sulfuric acid, nitric acid, and / or phosphoric acid. In some embodiments, the solvent contains the acid at a concentration of at least 1 (e.g., at least 2, at least 5, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 40, at least 45, at least 50, at least 55, at least 60, at least 65, at least 70, at least 75, at least 80, at least 85, at least 90) volume percent (vol. %) and / or at most 98 (e.g., at most 95, at most 90, at most 85, at most 80, at most 75, at most 70, at most 65, at most 60, at most 55, at most 50, at most 45, at most 40, at most 35, at most 30, at most 25, at most 20, at most 15, at most 10, at most 5) volume percent.
[0385] In some embodiments, the pH of the solvent is at least 7 (e.g., at least 8, at least 9, at least 10, at least 11, at least 12, at least 13) and / or at most 14 (e.g., at most 13, at most 12, at most 11, at most 10, at most 9, at most 8). In some embodiments, the solvent contains a hydroxide (e.g., sodium hydroxide, potassium hydroxide). In some embodiments, the solvent contains an acid at a concentration of at least 1 (e.g., at least 2, at least 5, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 40, at least 45, at least 50, at least 55, at least 60, at least 65, at least 70, at least 75, at least 80, at least 85, at least 90) volume. %, and / or at most 98 (e.g., at most 95, at most 90, at most 85, at most 80, at most 75, at most 70, at most 65, at most 60, at most 55, at most 50, at most 45, at most 40, at most 35, at most 30, at most 25, at most 20, at most 15, at most 10, at most 5) volume %.
[0386] In certain embodiments, the composite of the present disclosure (e.g., nanostructured organic compound, composite 1000, composite 2000) includes a depolymerizing agent, and contacting the composite with a solvent (e.g., a leaching agent, such as acidic water, HCl, H2SO4, or HNO3) can remove at least a portion of the depolymerizing agent. In certain embodiments, the composite of the present disclosure (e.g., nanostructured organic compound, composite 1000, composite 2000) includes a depolymerizing agent, and contacting the composite with a solvent can hydrolyze at least a portion of the depolymerizing agent.
[0387] In some embodiments, the depolymerizing agent is SnCl2, and the hydrolysis of SnCl2 forms a second material having tin, chlorine, hydrogen, and oxygen, wherein the second material is dispersed in the organic compound of the composite. In some embodiments, the second material is tin oxide chloride hydroxide. In some embodiments, the second material stoichiometry is Sn 21 Cl 16 (OH) 14 06. In some embodiments, the second material is at least partially crystalline (eg, crystalline).
[0388] In some embodiments, Sn-containing materials (e.g., SnO, SnO, Sn, SnCl) can be removed from the composite by contacting the composite with a solvent (e.g., a leaching agent such as acidic water, hydrochloric acid, sulfuric acid, or nitric acid). In some embodiments, a composite containing Si, SnO, and terephthalic acid (e.g., as described in Example 15) can be contacted with a solvent (e.g., sulfuric acid, hydrochloric acid) to remove SnO. Without being limited by theory, the hydrolysis reaction (1) can be avoided (see discussion above).
[0389] In embodiments where a solvent is used, the method may further include separating the complex from the solvent and / or drying the complex. Separation methods are well known in the art and include vacuum filtration and centrifugation. In some embodiments, the complex is dried under air, an inert atmosphere, or a vacuum. In certain embodiments, the complex is dried at a temperature of at least -196 (e.g., -100, -50, 0, 20) ° C and / or at most 100 (e.g., at most 50, at most 20, at most 0) ° C.
[0390] As described above, in some embodiments, the composite contains silicon-containing materials and / or graphene nanosheets. In some embodiments, the mixture contains a precursor of a silicon-containing material, and the resulting composite contains a silicon-containing material. In some embodiments, the mixture contains graphene nanosheets, and the resulting composite contains graphene nanosheets. In some embodiments, the solvent contains a precursor of a silicon-containing material, and the resulting composite contains a silicon-containing material. In some embodiments, the solvent contains graphene nanosheets, and the resulting composite contains graphene nanosheets.
[0391] In certain embodiments, the reactants contain at least 0.1 (e.g., at least 0.2, at least 0.5, at least 1, at least 2, at least 5, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 40, at least 45, at least 50) weight % and / or up to 98 (e.g., up to 95, up to 90, up to 85, up to 80, up to 75, up to 70, up to 65, up to 60, up to 55, up to 50) weight % of a silicon-containing precursor. Examples of applications of precursors of silicon-containing materials include elemental silicon, Ca2Si, Ca5Si3, CaSi, Ca3Si4, CaSi2, and Mg2Si. In certain embodiments, the precursor of the silicon-containing material comprises nanoparticles. In certain embodiments, the particle size of the precursor of the silicon-containing material is at least 1 (e.g., at least 2, at least 3, at least 4, at least 5) nm and / or at most 1000 (e.g., at most 500, at most 200, at most 100, at most 50, at most 20, at most 10, at most 5) nm.
[0392] In some embodiments, the precursor of the silicon-containing material is ball milled. In some embodiments, the precursor of the silicon-containing material is ball milled after being mixed with a solvent. In some embodiments, the solvent is n-hexane. Without being bound by theory, it is believed that the solvent (e.g., n-hexane) can prevent oxidation of the silicon particles during the ball milling process. In addition, without being bound by theory, it is believed that the solvent (e.g., n-hexane) can functionalize the silicon surface during the mechanical ball milling process, which can provide desired properties to the final composite.
[0393] In some embodiments, the reactants contain at least 0.1 (e.g., at least 0.2, at least 0.5, at least 1, at least 2, at least 5, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 40, at least 45, at least 50) weight % and / or up to 80 (e.g., up to 75, up to 70, up to 65, up to 60, up to 55, up to 50, up to 45, up to 40, up to 35, up to 30, up to 25, up to 20, up to 15, up to 10, up to 5) weight % graphene nanoplatelets. In some embodiments, the graphene nanoplatelets comprise graphene flakes having a flake size of at least 1 (e.g., at least 2, at least 5, at least 10, at least 20, at least 50, at least 100) nm and / or at most 5 (e.g., at most 4, at most 3, at most 2, at most 1) μm. In certain embodiments, the graphene nanosheets have at least 1 (e.g., at least 2, at least 3, at least 4, at least 5) layers and / or at most 100 (e.g., at most 90, at most 80, at most 70, at most 60, at most 50, at most 40, at most 30, at most 20, at most 10) layers of graphene structure. In certain embodiments, the carbon purity of the graphene nanosheets is at least 90% (e.g., at least 91%, at least 92%, at least 93%, at least 94%, at least 95%). In certain embodiments, the surface of the graphene nanosheets contains functional groups (e.g., hydroxyl, carbonyl, carboxyl and / or amino groups).
[0394] In some embodiments, graphene nanosheets are produced by cathode electrochemical stripping of a graphite electrode. In some embodiments, cathode electrochemical stripping is performed in a molten salt (e.g., lithium chloride and / or sodium chloride). In some embodiments, cathode electrochemical stripping is performed at a temperature of at least 500 (e.g., at least 600, at least 700, at least 800) ° C and / or at most 900 (e.g., at most 800, at most 700, at most 600) ° C.
[0395] In certain embodiments, graphene nanosheets can be introduced into the composite of the present disclosure by forming a suspension with the composite and graphene nanosheets and ultrasonically treating the suspension to form a product comprising the composite and graphene nanosheets. In certain embodiments, the suspension comprises an acid. In certain embodiments, the product contains at least 50 (e.g., at least 55, at least 60, at least 65, at least 70, at least 75, at least 80, at least 85, at least 90, at least 95, at least 99, at least 99.5) weight percent and / or at most 99.9 (e.g., at most 99.5, at most 99, at most 90, at most 85, at most 80, at most 75, at most 70, at most 65, at most 60, at most 55) weight percent of the composite. In certain embodiments, the product contains at least 0.1 (e.g., at least 0.2, at least 0.5, at least 1, at least 2, at least 5, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 40, at least 45) weight percent and / or at most 50 (e.g., at most 45, at most 40, at most 35, at most 30, at most 25, at most 20, at most 15, at most 10, at most 5, at most 2, at most 1) weight percent graphene nanoplatelets.
[0396] Figure 5c A reaction scheme for synthesizing the disclosed composites containing metal organic frameworks is shown (see discussion above). A mixture containing reactants polyethylene terephthalate (PET) and ZnCl2 is heated to form terephthalic acid (C8H6O4) by depolymerizing the PET. Terephthalic acid (C8H6O4) and ZnCl2 form zinc terephthalate (ZnC8H4O4) and HCl. HCl can be removed from the zinc terephthalate (ZnC8H4O4). Figure 5c The zinc terephthalate (ZnC8H4O4) formed by the reaction shown in is a zinc-based metal organic framework. Zinc terephthalate (ZnC8H4O4) is embedded in an organic compound (see discussion above). In some embodiments, the zinc terephthalate is hydrated. In some embodiments, the molecular formula of zinc terephthalate is ZnC8H4O4·nH2O, and n ranges from 0 to 5. In some embodiments, n is 0, 1, 2, or 3.5.
[0397] In some embodiments, zinc hydroxide chloride is used as a depolymerizing agent. Without being bound by theory, zinc hydroxide chloride can decompose to form ZnCl2 when heated.
[0398] In certain embodiments, the composite of the present disclosure includes a metal organic framework containing hydration water, and the composite is heated to a second temperature, thereby removing at least a portion of the hydration water from the metal organic framework. In certain embodiments, the metal organic framework has a first crystal structure before being heated to the second temperature, and the metal organic framework has a second crystal structure different from the first crystal structure after being heated to the second temperature (see Example 32). In certain embodiments, the second temperature is at least 50 (e.g., at least 100, at least 150, at least 200, at least 250, at least 300, at least 350) ° C and / or at most 400 (e.g., at most 350, at most 300, at most 250, at most 200, at most 150, at most 100) ° C. In certain embodiments, the complex is maintained at the second temperature for at least 1 millisecond (e.g., at least 0.1 seconds, at least 1 second, at least 10 seconds, at least 1 minute, at least 10 minutes, at least 1 hour) and / or at most 10 hours (e.g., at most 1 hour, at most 10 minutes, at most 1 minute, at most 10 seconds, at most 1 second).
[0399] In some embodiments, Figure 5a and 5b The reaction shown in can include removing at least a portion of the composite (eg, nanostructured terephthalic acid, terephthalic acid+SnO2) and adding additional polymer (eg, PET).
[0400] In some embodiments, the method of the present invention further comprises preparing Na2TP (Na2C8H4O4), Li2TP (Li2C8H4O4), K2TP (K2C8H4O4) or ZnTP (ZnC8H6O4) from the compound of the present invention. For example, Na2TP can be prepared by acid-base reaction:
[0401] C8H6O4+2NaOH=Na2C8H4O4+2H2O (15)
[0402] Without being bound by theory, the compounds of the present disclosure react with faster kinetic rates than certain other organic compounds (e.g., non-nanostructured and / or nanocrystalline commercial terephthalic acid). The greater reaction kinetics in nanostructured organic compounds (e.g., terephthalic acid) may be related to their nanoscale size and nanocrystalline structure, which allows the material to react with greater kinetics than certain other organic compounds (e.g., non-nanostructured and / or nanocrystalline commercial terephthalic acid). Rapid preparation of functional materials such as Na2TP can reduce preparation costs, thereby promoting its application, for example, in the negative electrode of sodium ion batteries.
[0403] Without being bound by theory, compounds such as Li2TP (Li2C8H4O4), K2TP (K2C8H4O4), and ZnTP (ZnC8H6O4) can be generated by treating nanostructured organic compounds (e.g., nanostructured terephthalic acid) with appropriate solutions (e.g., LiOH, KOH, and Zn(OH)2 solutions) in relatively short reaction times. Such compounds can be used as electrodes for metal ion batteries (e.g., lithium ion, potassium ion, and zinc ion batteries, respectively).
[0404] In some embodiments, reaction (15) is performed for up to 18 (e.g., up to 16, up to 14, up to 12, up to 10, up to 8, up to 6, up to 5, up to 4, up to 3, up to 2, up to 1) hours.
[0405] Plastic separation
[0406] Figure 5d A reaction scheme is shown. A mixture containing reactants polyethylene terephthalate (PET), SnCl2, and HDPE is heated to form nanostructured terephthalic acid. The polymer (PET) depolymerizes to form terephthalic acid, while the HDPE does not depolymerize. The HDPE can melt and sink to the bottom of the container, making it relatively easy to separate the HDPE from the nanostructured terephthalic acid. Without being limited by theory, the crystal structure of HDPE is not affected by heating with a depolymerizing agent (e.g., SnCl2) (see Example 34).
[0407] Although Figure 5d The reaction shown shows SnCl2 as the depolymerizing agent, but any depolymerizing agent of the present disclosure may be used. Figure 5d The reaction shown shows the formation of nanostructured terephthalic acid, but any of the composites of the present disclosure can be prepared using appropriate reagents and reaction conditions.
[0408] Without being bound by theory, crystalline polymers are not easily depolymerized due to their highly ordered structure and strong intermolecular forces, while semi-amorphous or amorphous polymers can be depolymerized more effectively due to their lower structural order. In addition, polymers with relatively high thermal stability (such as polyimide) may not be effectively depolymerized.
[0409] In addition to PET, examples of depolymerizable polymers include polystyrene, polyvinyl chloride, nylon, polyurethane, phenolic resins, and epoxy resins.
[0410] In addition to HDPE, examples of non-depolymerizable (eg, highly crystalline) polymers include polyethylene and polypropylene.
[0411] Example
[0412] Example 1 – Synthesis
[0413] Use scissors to cut polyethylene terephthalate (PET) into pieces of about 10×5 mm. Place 20 g of PET pieces in an alumina crucible with an inner diameter of about 5 mm and a height of about 100 mm. Add 10.10 g SnCl2 (99.9%, Aladdin), 27.54 g KCl (99.9%, Aladdin) and 23.06 g LiCl (98%, Aladdin) to the crucible. LiCl–KCl binary eutectic molten salt (KCl: 54.8wt.%-45.2wt.% LiCl) has a melting point of about 360°C. The mixed molten salt is heated at 5°C min in a vertical resistance furnace equipped with an alumina tube. -1 The heating rate was 500, 600, 700 and 800 °C (PDN-500, -600, -700 and -800, respectively) from room temperature to the target temperature. The holding time was 20 min. The resistance furnace was then heated at 5 °C min -1 The sample was washed with deionized water, vacuum filtered and dried at about 100°C for 2 hours.
[0414] Example 2 – X-ray diffraction measurements
[0415] The X-ray diffraction pattern of the sample was measured using a powder diffractometer (Panalytical X'pert Pro) with a Cu Kα radiation source (λ=0.1542 nm) in the range of 10 to 90° (2θ).
[0416] PET was heat treated with SnCl2 at 300 and 350°C for 20 min, and then the samples were washed and filtered.
[0417] Figure 6 ac show the X-ray diffraction patterns of PET heat-treated with LiCl-KCl (PET+(LiCl-KCl) / 500°C), PET heat-treated with SnCl2 to 350°C (PET+SnCl2 / 350°C), and PDN-500 (PET heat-treated with SnCl2 and LiCl-KCl with a target temperature of 500°C, as described in Example 1) (PET+(SnCl2-LiCL-KCl) / 500°C), respectively. Figure 6 df also shows the XRD pattern of commercial terephthalic acid (C8H6O4) and the standard diffraction patterns of SnO2 and terephthalic acid, respectively.
[0418] The XRD spectrum of (PET+SnCl2 / 350℃) showed the formation of terephthalic acid.
[0419] The XRD pattern of PET heat treated with SnCl2 at 350°C showed evidence of the formation of terephthalic acid.
[0420] For PDN-500 (PET + (SnCl2-LiCL-KCl) / 500℃), the diffraction peaks appeared at 2θ values around 26.60°, 33.90°, 37.97°, 39.00°, 51.81°, 54.79°, 57.87°, 61.92°, 64.79°, 66.01°, 71.33°, 78.76°, 81.19°, 8 3.78° and 87.29°, and index the (110), (101), (200), (111), (211), (220), (002), (310), (112), (301), (202), (321), (400), (222) and (330) tetragonal SnO2 diffraction planes of the standard card (JCPDS≠01-070-4177), respectively. In addition to SnO2, the diffraction pattern also confirms the presence of terephthalic acid (C8H6O4, JCPDS≠031-1916) with a heterocrystalline structure. The diffraction peaks observed at 2θ=17.41°, 25.21°, and 27.95° are attributed to the (110), (0-10) and (200) diffraction planes of terephthalic acid. For comparison, Figure 6 The XRD pattern of commercial terephthalic acid (C8H6O4, Shanghai Macklin, 400-623-8666, 99%) is also shown, confirming that terephthalic acid is produced by the molten salt method.
[0421] Figure 7 Shown are the XRD patterns of (a) PDN-500 (PET heat treated with SnCl2 and LiCl-KCl as described in Example 1, with a target temperature of 500°C (PET + (SnCl2-LiCL-KCl) / 500°C)) and (b) commercially available micron-sized terephthalic acid (C8H6O4, Shanghai Macklin, 400-623-8666, 99%).
[0422] Figure 7 The formation of terephthalic acid by the method described in Example 1 was further confirmed.
[0423] Example 3 – Effect of Temperature
[0424] Figure 8 a shows the X-ray diffraction patterns of PDN-500, -600, -700 and -800 (compounds synthesized from PET, SnCl2 and LiCl-KCl as described in Example 1 with target temperatures of 500, 600, 700 and 800°C) in the range of 10-90°. Figure 8b shows the high-resolution XRD pattern of the sample in the scanning range of 14–30°. Figure 8 c shows the high-resolution XRD pattern of the sample in the 2θ range of 60–68°. Figure 8 a Also contains JCPDS standard card.
[0425] Figure 8 Figures 8a and 8b show that the X-ray peaks corresponding to SnO2 can be observed in all samples. However, the peaks of terephthalic acid are not observed in the samples prepared at the target temperatures of 600, 700, and 800 °C.
[0426] Figure 8 a further indicates the presence of graphite carbon with a hexagonal crystal structure (JCPDS≠00-025-0284). The (002) crystal plane of the carbon phase has a maximum peak at a 2θ value of 26.603°, overlapping with the strongest peak of the SnO2 phase, corresponding to the (110) crystal plane at 2θ=26.597°.
[0427] Figure 8 c shows that due to K α1 / K α2 The XRD peak splitting leads to the shoulder peak of the SnO2 diffraction peak at the higher angle side, which is caused by the copper-based X-ray tube used in the XRD equipment, which produces radiation with a wavelength of 0.1541nm (K α1 line) and 0.1544nm(K α2 Wire). Figure 8 The well-separated double peaks in c can be attributed to the highly crystalline SnO2 phase formed at higher temperature due to the growth of SnO2 crystallites into faceted crystals.
[0428] XRD data show that PET in the binary eutectic melt LiCl-KCl and SnCl2 is converted to at least partially crystalline terephthalic acid and SnO2 at 500°C and to carbon and SnO2 at 600, 700 and 800°C.
[0429] Example 4 – Raman Characterization
[0430] Raman spectra were recorded by a Jobin-Yvon LabRam HR800 spectrometer equipped with a 488 nm laser source.
[0431] Fig. 9 Raman spectra of PDN-500, -600, -700 and -800 (compounds synthesized from PET, SnCl2 and LiCl-KCl at target temperatures of 500, 600, 700 and 800°C as described in Example 1) are shown.
[0432] Fig. 91337-1361cm -1 The Raman D peak at 1591-1594 cm -1 The G band observed in the spectrum is sp 2 Raman characteristics of carbon, corresponding to the presence of graphite defects. The intensity ratio of the D band to the G band (I D / I G ) is an indicator of the degree of graphite defects. Fig. 9 As shown, I D / I G The ratio increases with increasing temperature, indicating the evolution of product structural disorder.
[0433] Example 5 – FTIR Characterization
[0434] The VERTEX 70 spectrometer was used at 400-4000 cm -1 Fourier transform infrared (FTIR) spectroscopy was performed in the wavelength range. Fig.10 FTIR spectra of PDN-500 and -800 (compounds synthesized from PET, SnCl2 and LiCl-KCl with target temperatures of 500 and 800°C as described in Example 1) are shown.
[0435] The spectrum of PDN-800 is at 636 and 918 cm -1 There are SnO2 frame vibration and Sn-O stretching at 1201, 1603 and 3454 cm -1 It comes from adsorbed water molecules.
[0436] The spectrum of PDN-500 is at 551, 571 and 681 cm -1 There is Sn-O stretching at 785cm -1 There is Sn-O-Sn vibration at 3468cm -1 The spectrum of PDN-500 also contains the FTIR characteristic peak of terephthalic acid. -1 The peak at 1419 cm is attributed to the asymmetric stretching vibration of the carbonyl group (C=O). -1 、1298cm -1 、947cm -1 and 735cm -1 The peaks at 1022, 1846, 1971, 2557, 2673, 2891, 2907, 2993, and 3072 cm-1 are attributed to C=C stretching, C-C stretching, OH bending, and out-of-plane aromatic ring bending, which are common in the FTIR spectrum of terephthalic acid. Other FTIR peaks are at 1022, 1846, 1971, 2557, 2673, 2891, 2907, 2993, and 3072 cm-1. -1The terephthalic acid is also present at 889 and 1128 cm -1 The FTIR peaks observed at 400 nm were attributed to hydrogen bonding between SnO2 oxygen and terephthalate hydrogen (Sn-OH). Table 1 summarizes the peaks observed in the FTIR spectra.
[0437] Table 1. Summary of peaks observed in FTIR spectra of samples prepared at 500 °C and 800 °C.
[0438]
[0439]
[0440] FTIR results showed the presence of terephthalic acid and SnO2 in the samples prepared at the target temperature of 500 °C.
[0441] Example 6 – Thermal Analysis
[0442] An SDT Q600 thermal analyzer equipped with an alumina crucible was used for differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA).
[0443] Typically, the thermogram of terephthalic acid has an endothermic peak at 300-400 ° C corresponding to partial sublimation of the reactants, followed by decomposition of the remaining material at higher temperatures without melting. The decomposition process is an exothermic reaction that leads to the formation of a gas phase (benzene, biphenyl, toluene, hydrogen and carbon monoxide) and residual carbon.
[0444] At 100 mL min -1 About 8 mg of PDN-500 (a compound synthesized from PET, SnCl2 and LiCl-KCl, with a target temperature of 500°C, as described in Example 1) was analyzed by DSC and TGA techniques at an air flow rate of 1.5 %. The results are as follows Fig.11 shown.
[0445] The TGA curve shows a mass loss of 4.4% during heating from room temperature to 250°C, corresponding to the removal of surface hydroxyl groups and / or adsorbed water. The TGA curve contains a sharp mass loss of 42.1% in the temperature range of 250-335°C, and an endothermic peak appears in the DSC curve at 328°C. This endothermic peak corresponds to the partial sublimation of terephthalic acid. Further heating in the temperature range of 334-465°C in the TGA curve results in a mass loss of 15.1%, and an exothermic peak appears in the DSC thermograph at 461°C. This peak is attributed to the decomposition of the remaining terephthalic acid into gaseous byproducts and residual carbon. The residual carbon is oxidized at higher temperatures, as evidenced by the exothermic peak in the TGA curve with a maximum in the temperature range of 462-573°C, corresponding to a mass loss of 11.3%. The remaining 27.1% mass remains stable after heating to 900°C, corresponding to SnO2 in the sample. With an initial moisture content of 4.4%, the SnO2 content of the sample was estimated to be 28.3 wt.%.
[0446] Thermal analysis results showed the presence of terephthalic acid and SnO2 in the sample.
[0447] Example 7 – Microstructural Characterization
[0448] Scanning electron microscopy (SEM, Ultra-Plus ZEISS) and transmission electron microscopy (TEM, Tecnai F20) were used for micromorphology characterization.
[0449] Fig.12 12a and 12b show SEM micrographs of PDN-500 (a compound synthesized from PET, SnCl2 and LiCl-KCl with a target temperature of 500°C as described in Example 1). The micrographs show that the compound contains nanostructure clusters with a total size of less than 2 μm. These clusters mainly contain terephthalic acid and SnO2, based on the XRD pattern of Example 2.
[0450] Fig.12 c and 12d show SEM micrographs of PDN-800 (a compound synthesized from PET, SnCl2 and LiCl-KCl with a target temperature of 800°C as described in Example 1). The morphology of the PDN-800 sample is different from that of the PDN-500 sample, with large faceted crystals of SnO2 with a size of 10 μm. A large number of SnO2 particles remain in submicron size.
[0451] Fig.13a The EDS spectrum of PDN-500 is shown. The relatively uniform distribution of C, O, and Sn indicates the formation of SnO2-terephthalic acid hybrid structure. EDS cannot detect hydrogen.
[0452] Fig.13b The EDS spectrum of PDN-800 is shown. Fig.12 SEM micrographs of d and Fig.13b The EDS spectrum shows that there is SnO2 with a size of about 600nm in the carbon substrate formed by carbonization of terephthalic acid.
[0453] Fig.14 ad shows the TEM analysis of PDN-500. Fig.14 SnO2 nanoparticles with a size less than 5 nm are shown in a. Fig.14 b shows Fig.14 Fast Fourier transform (FFT) graph recorded on a. Fig.14 Rings corresponding to the tetragonal SnO2 crystalline phase are observed in b. Fig.14 c shows a high-magnification TEM micrograph of a nanocrystal with a length of 4.23 nm. The FFT recorded on this nanocrystal is shown in Figure 2. Fig.14 d, and shows the presence of spots corresponding to crystal planes with an interlayer spacing of 0.33 nm, which is characteristic of (110) SnO2. Due to the instability of terephthalic acid under high-voltage electron beam, TEM characterization of terephthalic acid was not possible.
[0454] Example 8 – Surface Area Characterization
[0455] The Brunauer-Emmett-Teller (BET) method was used to measure the specific surface area of the samples.
[0456] The BET specific surface area of PDN-500 was determined to be 19.2 m2 g -1 .
[0457] Example 9 – XPS Characterization
[0458] X-ray photoelectron spectroscopy (XPS, ESCALAB250, Thermo Fisher Scientific) measurements were performed on PET and molten LiCl-KCl and the products synthesized from PET, SnCl2 and LiCl-KCl at a temperature of 500°C, as described in Example 1 (PDN-500).
[0459] The XPS spectrum of the PET+LiCl-KCl sample is as follows: Fig.15 ac shown. Fig.15 The spectrum results of a show that there are C and O elements in the sample. Fig.15As shown in (b), the C 1s fine spectrum is dominated by a peak at 284.1 eV, indicating the presence of C-C bonded graphitic carbon in the sample. The presence of two broad peaks centered at 285.4 and 288.4 eV represents lattice defects caused by random orientation of dangling bonds relative to carbon atoms and defective carbon, respectively. The XPS test results match the XRD results of Example 2, further confirming that the PET+LiCl-KCl sample contains amorphous carbon. The curve fitting associated with the O1s peak of the sample XPS spectrum ( Fig.15 c) shows that there are three types of surface oxygen bonds, namely C=O (530.3 eV), CO, carbonyl (532.5 eV), C-OH and OC=O (533.4 eV). The amount of surface oxygen in the sample accounts for 16.49 atomic percent (at%), which is comparable to the atomic percentage of amorphous carbon.
[0460] The XPS spectrum of the PDN-500 sample is as follows Fig.15 eh. Fig.15 Compared with a, Fig.15 The spectrum of e includes the Sn peak and a much lower carbon-oxygen ratio due to the formation of terephthalic acid and SnO2. The C1s spectrum of PDN-500 is shown in Fig.15 As shown in Figure 5, its peak can be divided into four peaks at 284.2, 284.9, 286.3 and 288.5 eV, corresponding to the four different types of non-equivalent carbon atoms observed in terephthalic acid, corresponding to the excitation of phenyl carbon into the π* molecular orbital. Fig.15 The important O1s fine spectrum shown in g can be fitted to obtain three peaks at 530.6, 531.6 and 532.7 eV, corresponding to O-Sn, CO-Sn and chemically adsorbed oxygen, respectively. The peak at 532.7 eV is attributed to the excitation of the carbonyl bond in terephthalic acid. The Sn 3d spectrum of the sample is shown in Fig.15 h shows that there are peaks at 486.7 eV and 486.7 eV, respectively, indicating the presence of Sn 3d 5 / 2 and Sn 3d 3 / 2 These peaks correspond to Sn 4+ The characteristics of the samples indicate the formation of SnO2, which is consistent with the XRD results of Example 2. The Sn content on the sample surface is 6.71 at%.
[0461] Fig.15 d shows the elemental analysis results of each sample.
[0462] Example 10 – Bulk Conductivity
[0463] The room temperature conductivity was measured by a four-probe system (DCY-3F, Hunan Zhenhua Analysis Co., Ltd.) equipped with a vertical unidirectional hydraulic press. By using a copper piston (D = 20.05 mm, H = 85.36 mm) on a copper holder, 2.0 g of sample was compressed inside an acrylic tube (ID = 20.05 mm, H = 45.37 mm) at different pressure values, and the hydraulic press was used for measurement at different pressure values (up to 6 MPa). At different pressures, various current values in the range of 0.10–0.30 A were conducted between the copper piston and the holder, and the corresponding potentials were recorded at 20 °C using the four-probe DC method. The voltage and current resolutions of the display screen of the control system were 0.1 mV and 0.1 mA, respectively. The powder density value can then be calculated by applying different pressure values to the sample. The resistance can be calculated based on the slope of the VI curve. The resistivity (ρ) of the sample is then calculated as follows:
[0464]
[0465] Where R is the resistance obtained from the slope of voltage and current, S is the cross-sectional area of the sample particle (D = 2 cm), and h is the height of the sample. By taking the reciprocal of the resistivity of the sample, the conductivity (σ) can be calculated as follows:
[0466]
[0467] To measure the conductivity value, PDN-500 was thoroughly mixed with synthetic graphite powder (G) at a mass ratio of 25:75, and the obtained mixture was used for conductivity measurement. To perform the measurement, 2.0 g of sample (G or G + PDN-500 mixture) was introduced into the cavity of the conductivity measuring device, and G (C G ) and G+PDN-500 mixture (C G+PDN-500 The presence of graphite powder allows the measurement of PDN-500 (C PDN-500 ) of the bulk conductivity, the results are as follows Fig.16 shown.
[0468] C G+PDN-500 =C G ×Gmass%+C PDN-500 ×PDN-500mass% (7)
[0469] from Fig.16 It was observed that the bulk conductivity of PDN-500 increased with increasing applied pressure, from 74.8 S m at 2.7 MPa to -1 447.3S m when increased to 6.3MPa -1In addition, the bulk density of PDN-500 was calculated by measuring the height of the compressed powder (and then its volume), considering that the value of the cross-sectional area of the compressed powder and its mass value remained unchanged during the uniaxial compression test. The bulk density of PDN-500 is 1.2 g cm -3 , the pressure is 6.3MPa.
[0470] Example 11 – Lithium-ion storage performance and electrochemical characterization
[0471] The prepared sample (80 wt.%) was mixed with conductive carbon (C65, 10 wt.%) and PVDF binder (10 wt.%) to make a slurry suspension by applying NMP solvent. The slurry suspension was coated on a copper foil and then dried in vacuum at 100 °C overnight. Then, the copper foil loaded with active materials was cut into discs with a diameter of 1.2 cm and assembled into a CR2025 half-cell. In this electrochemical cell, the coated copper foil was used as the working electrode, while the lithium sheet was used as both the reference electrode and the counter electrode. At the same time, a glass microfiber separator (Whatman, 1823025) was placed between the above electrodes to prevent physical contact between the positive and negative electrodes from causing a short circuit, while promoting the transport of ions in the battery. The battery assembly was carried out in a gas-controlled glove box (Mikrouna) filled with high-purity argon, and the O2 and H2O contents in the glove box were less than 0.1 ppm. The mass loading of the active material was 1.3 mg cm -2 . The same mass loading was used to evaluate the constant current charge-discharge cycle performance and also for cyclic voltammetry tests. The electrolyte was LiPF6 (1 M) dissolved in solvents of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl carbonate (EMC) (volume ratio of 1:1:1). Button cells were made using a sealing machine (YLJ-24T, MTI Company). The half-cells were allowed to stabilize at room temperature for 10 h and then connected to a battery testing system (Land CT2001A) and tested at constant and variable current densities at 0.01-3.0 V (vs Li + The charge and discharge cycle tests were carried out in the voltage range of 200V / Li. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) tests were performed using a CHI-660E electrochemical workstation.
[0472] In 0.01-3V (vs Li + / Li), constant current charge-discharge experiments and cyclic voltammetry tests were performed to evaluate the performance of PDN-500, PDN-600, PDN-700, and PDN-800 in the range of 0.01-3 V (vs Li + / Li) voltage range for 500 cycles.
[0473] Fig.17a shows the current at 200mA g -1 The discharge capacity values of PDN-500, -600, -700 and -800 during lithium ion insertion / extraction cycles at current densities of 2.3 % and 1.3 % respectively. PDN-500 exhibited 498 mAh g-1 after 500 cycles. -1 The discharge capacity is much larger than that of PDN-600 (169mAh g -1 , 428th cycle), PDN-700 (138 mAh g -1 , 360th cycle) and PDN-800 (125mAh g -1 , 500th cycle).
[0474] Fig.17 b shows the electrode made of PDN-500 at 200 mA g -1 Coulombic efficiency at current density. The capacity value of the first discharge / charge cycle is 1183 / 545 mAh g -1 , corresponding to a Coulombic efficiency of 46.1%. The capacity loss is mainly attributed to the irreversible decomposition of the electrolyte on the electrode surface, forming a solid electrolyte interface (SEI). The capacity value of the second discharge / charge cycle is 612 / 535 mAh g -1 The Coulombic efficiency was higher at 87.5%, indicating limited interaction between the electrolyte and the electrode during the second cycle. The specific capacity values for the third discharge / charge were 572 / 524 mAh g -1 , with a Coulombic efficiency of 91.5%. The Coulombic efficiency gradually increased with the cycles, reaching 97.3% after 22 cycles and 99.2% after 78 cycles. The Coulombic efficiency fluctuated slightly until the discharge / charge specific capacity value of 498 / 492 mAh g was recorded after 500 cycles. -1 , corresponding to a Coulombic efficiency of 98.8%.
[0475] The lithium ion storage capacity of PDN-500 derived from waste plastics is between 100-2000mA g -1 Tested at current densities between Figure 17g At 100, 200, 500, 1000 and 2000mA g -1 At the current density of 1.377 W / m, the electrodes have 605.7 (10th cycle), 527.2 (20th cycle), 449.4 (30th cycle), 363.3 (40th cycle) and 260.5 mAh g -1 After that, the current density was restored to 100 mA g -1 , 628 mAh g was recorded at the 70th cycle -1 This result confirms that the PDN-500 electrode has a reversible specific capacity of up to 2000 mA g-1 It still has ideal rate performance at current density of 2.5 W.
[0476] The lithium ion storage capacity of PDN-500 electrode is 100-5000mA g -1 Measured at current densities between Fig.17 c. At 100, 200, 500, 1000 and 2000 mA g -1 After cycling at different current densities, the electrode showed a good conductivity at 5000 mA g -1 101.3mAh g -1 The specific capacity of the battery was restored to 100 mA g -1 After that, the reversible specific capacity recorded at the 70th cycle was 436.8 mAh g -1 , which is less than the 600.7 mA g recorded in the 10th cycle at the same current density. -1 After 70 cycles and 5000mA g -1 After a high current density of 436.8 mAh g -1 The relatively high specific capacity of this material indicates that it can be used at up to 5000 mA g -1 It has a relatively high lithium storage rate performance at a current density of .
[0477] The cyclic voltammetry (CV) curves of PDN-500 recorded at different cycles are shown in Figure 2. Fig.17 d. The peaks observed in the CV curves represent the electrochemical reactions involved in the battery cycling process. In the first cathode direction scan, 1.7 V (vs Li / Li + ) position, which is not seen in subsequent cycles. This peak is attributed to the SEI layer formed by the reduction reaction of the solvent (EC-DEC-DMC) on the electrode, reaction (8).
[0478] Li + +e - + electrolyte → SEI (8)
[0479] The long cycling capability of the electrode requires a stable SEI layer.
[0480] Further, the cathodic peaks observed around 0.83 and 0.22 V are attributed to the phase transformation of SnO2 to Sn, reaction (2a), and the alloying reaction between lithium and tin, leading to the formation of Li-Sn intermetallic compounds, as shown in reaction (2b). During the first anodic cycle, the oxidation peak around 0.54 V is attributed to Li xDealloying reaction of Sn (2b). The anodic peaks around 0.97 V and 1.24 V correspond to the reversible phase transition from Sn to SnO2, as shown in reaction (2a).
[0481] like Fig.17 As shown in Figure d, the second cathodic cycle is different from the first one in that there is no obvious cathodic peak at around 1.7 V in the second cycle, which indicates that the SEI layer formed in the first cycle has relatively good stability. In addition, peaks related to the reduction and oxidation of tin compounds were observed in the CV graphs recorded in subsequent cycles, demonstrating the reversibility of lithiation / delithiation of SnO2 nanocrystals embedded in terephthalic acid. In this case, terephthalic acid acts as a carrier to regulate and accommodate the volume changes during the electrochemical reactions (2a) and (2b), ensuring the cycling stability of the electrode.
[0482] Electrochemical impedance spectroscopy (EIS) measurements were performed on the PDN-500 electrode before cycling and at 200 mA g -1 150 and 300 constant current discharge / charge cycles were performed at a current density of . Fig.17 e shows the electrochemical impedance spectrum recorded at 5 mV amplitude in the frequency range of 10 mHz to 100 kHz, and the equivalent circuit of the Nyquist plot. The impedance spectrum is a semicircle in the high-frequency region and a sloping straight line in the low-frequency range. The electrochemical behavior of PDN-500 in the high-frequency region represents the transfer resistance (R f ), while the electrochemical behavior in the medium frequency region is attributed to the charge transfer resistance (R ct ). On the other hand, the low-frequency impedance of the electrode is attributed to the Warburg impedance (Zw), which represents the migration of lithium ions. Fig.17 The equivalent circuit shown in e also contains a constant phase element (CPE) element to simulate the behavior of a non-ideal capacitor. From the impedance spectrum, it can be observed that the diameter of the semicircular arc obtained after 150 cycles is smaller than that of the new electrode, confirming that R ct Reduction during cycling. The reduction in cell resistance is attributed to the rearrangement of SnO2 nanoparticles in the terephthalate matrix during cycling.
[0483] Table 2 shows the Fig.17 The electrochemical parameters obtained from the EIS spectra in e and 17f. Based on the measured values, the lithium ion diffusion coefficient was calculated using formula (9) and the results are shown in Table 2.
[0484]
[0485] Where R is the gas constant (8.314 J mol -1 K -1); T is the temperature (298K); A is the surface area of the electrode (~1.13cm 2 ); n is the number of moles of electrons transferred (1 for lithium); F is the Faraday constant (96,485 C mol -1 ), C is the lithium ion concentration derived from the tap density of the active material, and σ is the result of the actual Z and ω -1 / 2 The slope of the Warburg factor is determined by Fig.17 As shown in e.
[0486] Table 2. Electrode kinetic parameters from equivalent circuit fitting of Nyquist plot
[0487]
[0488]
[0489] It can be seen from Table 2 that the electrolyte resistance (R e ) slightly increased from 3.47Ω in the uncycled electrode to 3.58Ω after 150 cycles. After 300 cycles, the value increased significantly to 5.40Ω. On the other hand, the charge transfer resistance (R ct ) dropped significantly from 34.06Ω to 22.83Ω after 150 cycles. After 300 cycles, the value increased slightly to 25.54Ω. In addition, the SEI film (R f ) increased slightly from 6.41Ω to 8.81Ω after 150 cycles and further increased to 15.21Ω after 300 cycles. The Warburg coefficient σ is determined based on the slope of the actual impedance and the inverse of the square root of the angular frequency ( Fig.17 f). This value is 600.30s from the uncirculated electrode -1 / 2 The time drops to 283.44 and 108.83 s for the 150 and 300 cycle electrodes, respectively. -1 / 2 The lower the Warburg coefficient value, the higher the ion diffusion coefficient (D Li ) value, as shown in Table 2. After 150 cycles, the lithium diffusion coefficient increased from the initial value of 2.80×10 -11 Increased to 1.26×10 -10 cm 2 S -1 .
[0490] Fig.18 The extended cycling performance of the electrode made from the sample (PET+(SnCl2-LiCl-KCl) / 500℃) is shown based on the -1The mass of SnO2 (oxidized phase) of the electrode measured at the current density. The thermal analysis of PDN-500 in Example 6 showed that PDN-500 contained about 28.3 wt.% SnO2. The capacity of the SnO2 component of the electrode can be calculated based on the specific capacity of terephthalic acid (14 mAh g -1 ) and conductive carbon for preparing electrodes (184 mAh g -1 ). Therefore, the capacity of the electrode was converted to 1657 mAh per gram of SnO2, which is approximately the theoretical capacity of SnO2, indicating that SnO2 nanocrystals exhibited their maximum specific capacity even after 500 cycles when incorporated into the terephthalic acid matrix.
[0491] Example 12 – Morphological Characterization of Electrodes after Cycling
[0492] The method of Example 7 was used to characterize the morphology of the electrode after cycling in Example 11.
[0493] Fig.19 a shows the SEM micrograph of the PDN-500 electrode after 200 Li insertion / extraction cycles. The absence of obvious cracks shows the structural integrity of the material during the cycling process.
[0494] Fig.19 b shows a TEM micrograph of a PDN-500 electrode. Fine SnO2 particles are dispersed in a terephthalic acid matrix. Although pores are present, the material maintains its structural integrity. The SnO2 particles are completely covered by the matrix, which enhances the integrity of the electrode.
[0495] Fig.19 a and 19b confirm that the presence of terephthalic acid in PDN-500 can effectively prevent the disintegration of the electrode material during long-term battery cycling.
[0496] Example 13 – Pseudocapacitive Performance
[0497] To evaluate the contribution of pseudocapacitive lithium storage to the cycling performance of PDN-500, the 240 nm Li-ion battery was tested at 0.2, 0.4, 0.6, 0.8, and 1.0 mV s after 100 cycles. -1 The battery was subjected to scanning voltammetry at different scan rates as described in Example 11. The results are shown in Fig. 20 As shown in a. Two anodic peaks can be detected in the CV curve, corresponding to the delithiation process of the electrode. As the scan rate increases from 0.2 to 1.0 mV s -1 , these peaks shift to higher potential values, which indicates the control of ion diffusion. In addition, the intensity of the peaks increases with the increase of scan rate. The current intensity (i) and scan rate (v) can be related by equation (10) and its logarithmic form equation (11):
[0498] i=a×v b (10)
[0499] log i=log a+b×log v (11)
[0500] where a and b are dimensionless variables. For redox reactions governed by semi-infinite diffusion-controlled processes, the value of b will be close to 0.5, while for capacitive processes the value will be close to 1. By plotting the logarithmic peak current versus the logarithmic scan rate ( Fig. 20 b), Fig. 20 The b-values of peaks 1 and 2 in a are calculated to be 0.65 and 0.75, respectively. 0.65 is closer to 0.5, so the reaction occurring at peak 1 is dominated by diffusion-based processes, except for a limited contribution from capacitive charge storage processes. The b-value of the second peak is 0.75, corresponding to a capacitive contribution with a limited contribution from diffusion behavior. Based on the results obtained, Fig. 20 c shows the relative contributions of capacitance and diffusion-controlled processes at different scan rates, indicating that the pseudocapacitive contribution gradually increases with increasing scan rate. Fig. 20 d shows 1.0mV s -1 The contribution of capacitance to the total current.
[0501] Example 14 – Anaerobic Synthesis
[0502] PET plastic flakes (10 g, polymer material) were mixed with SnCl2 (5.05 g, depolymerizing agent) and KCl (13.79 g) and LiCl (11.53 g). The mixture was heated to a maximum of 500 °C at a heating rate of 10 °C min -1 , maintained at the highest temperature for 10 min, and then the temperature was lowered to room temperature. The heat treatment process was carried out in a tube furnace under Ar (95%) and H2 (5%) gas flow. The resulting material was then washed with deionized water, and the resulting suspension was vacuum filtered with a polymer filter paper to collect the filtered product, and then dried at 100°C for several hours.
[0503] The XRD pattern of the obtained product is as follows Fig.21 As shown, the XRD pattern shows the presence of terephthalic acid (C6H8O6). During the thermal treatment, SnO2, SnO and Sn phases may also be generated by the depolymerizing agent (SnCl2).
[0504] TEM micrographs of organic compounds such as Fig. 22 As shown, the TEM micrographs demonstrate the nanostructural nature of the material, where particles with sizes of 18 nm and 3 nm were observed.
[0505] Example 15 – Silicon-Containing Materials
[0506] Silicon particles smaller than 500 μm (21.7 g), zirconium oxide balls (15 mm diameter, 650 g) and n-hexane were ball milled together using a planetary ball mill at a speed of 300 rpm for 50 h.
[0507] Fig.23 An SEM micrograph of the silicon raw material is shown. After ball milling, the ball milled Si was dried to remove the n-hexane. Fig.24 SEM micrographs of the resulting silicon are shown, indicating that the particle size of the ball-milled silicon is reduced to about 50 nm to 700 nm.
[0508] The obtained SiNP (2 g) was mixed with PET particles (4 g) and SnCl2 (4 g). The mixture was placed in an alumina crucible, and then the crucible was placed in a muffle furnace under air atmosphere at 10 ° C min -1 The furnace was then cooled to room temperature and the resulting material was washed with deionized water, vacuum filtered and dried.
[0509] The XRD spectrum of the product is as follows Fig.25 As shown, it can be seen that terephthalic acid (C5H6O4) exists. In addition, Fig.25 The presence of Si and SnO2 is also demonstrated.
[0510] The SEM morphology of the obtained product is as follows Fig.26 a and 26b. In the micrographs, terephthalic acid aggregates SiNPs (particle size is about 50-700 nm) into Si / SnO2 / terephthalic acid nanostructured composite materials with particle size greater than 10 μm.
[0511] Example 16 – Comparison of Nanostructured Terephthalic Acid with Commercial Terephthalic Acid
[0512] According to Example 1, PET can be nanostructured using SnCl2 as a depolymerizing agent in the presence of LiCl-KCl. The nanostructured material is characterized as a mixture of nano-terephthalic acid (C8H6O4) structures and nano-SnO2 crystals. Micron-sized terephthalic acid powder (Shanghai McLean Biochemical Co., Ltd., 400-623-8666, 99%) was characterized as a control group for the material of Example 1. Figure 6 d shows the XRD pattern of commercial terephthalic acid, indicating that commercial terephthalic acid has a crystalline structure. Fig. 27 Ad shows the SEM morphology of the material, showing particles with a size of 10-100 μm. Fig.28Figures 28a and 28b show the powders of PDN-500 (PET+(SnCl2-LiCl-KCl) / 500℃) and commercial terephthalic acid, respectively. Thermal treatment of PET in a molten salt environment forms terephthalic acid, which has the same crystal structure as commercial terephthalic acid, but has a very different morphology, microstructure, and color from commercial terephthalic acid. PDN-500 is darker in color, while commercial terephthalic acid is white, as shown in Figures 28a and 28b, respectively. Fig.28 a and 28b. Considering that SnO2 nanoparticles are white, the dark appearance of this nanostructured material may come from the black color of terephthalic acid therein. Since commercial terephthalic acid is a white crystalline solid, the black appearance of terephthalic acid in PDN-500 may be related to the nanostructured nature of the material.
[0513] Example 17 – Heat treatment of PET, SnCl2 and Li-KCl under Ar atmosphere
[0514] 60 g of PET flakes were mixed with 184 g of SnCl2, 46.4 g of LiCl and 54.9 g of KCl. The mixture was placed in an alumina crucible (H = 10 cm, D = 7.5 cm), the crucible was covered with an alumina lid and placed in a stainless steel reactor equipped with a gas inlet / outlet. The reactor was heated to a maximum of 445 °C in an electric furnace under an argon flow with an average heating rate of 5 °C min -1 , and the temperature of the material in the crucible is measured by a thermocouple preset in the crucible. After reaching the highest temperature, the heating is terminated and the reactor is then cooled naturally to room temperature.
[0515] Fig.29 ad show photos of waste PET, crushed PET, and an alumina crucible loaded with a mixture of PET+SnCl2+LiCl+KCl before and after heat treatment at 445°C. It can be observed that the product obtained after heat treatment is much larger than the initial material, indicating that the product has a porous structure. The porous product can be easily separated from the crucible. Since the apparent density of the salt is greater than that of the porous product, the salt mainly adheres to the bottom of the crucible during the molten salt process. There is a solidified salt disk at the bottom of the crucible, such as Fig.29 The results show that SnCl2-LiCl-KCl can be separated from the porous products based on their density, allowing the products to be easily collected without washing the salt mixture.
[0516] Based on these experimental results, the depolymerization of PET occurs at the interface between the salt and PET, and the depolymerized organic compounds move toward the upper part of the reactor, so at the end of the process, the organic compounds are mainly located in the upper part of the reaction vessel and the molten salt is located at the bottom of the reaction vessel, which greatly simplifies the separation process.
[0517] The material obtained on the upper part of the crucible was washed with water to remove residual salt trapped in its porous structure, and the obtained material was dried at 80° C. for 2 hours. Fig.30 The XRD pattern of the obtained material is shown. It was observed that the product contained various crystalline organic compounds, including phthalic acid (C8H6O4) (ICDD: 00-037-1919), terephthalic acid and protocatechuic acid (C7H6O4; ICDD: 00-008-056) with a monoclinic crystal structure, in addition to basic tin chloride. Basic tin chloride may be formed by the hydrolysis of SnCl2 remaining in the washing step.
[0518] Example 18 – Heat treatment of PET, SnCl2 and Li-KCl in Ar+H2 atmosphere
[0519] A mixture containing 13.79 g KCl, 11.53 g LiCl, 5.05 g SnCl2 and 10 g plastic flakes was placed in an alumina crucible, and the crucible was placed in a tube furnace equipped with an alumina tube. Ar-5% H2 gas was introduced into the pipeline. The temperature was raised to 90°C (8 h) and then heated at 10°C min -1 The heating rate was raised to 500 °C. The sample was kept at 500 °C for 10 min and then cooled to room temperature. The heat treatment was carried out under an atmosphere of Ar-5% H2. The obtained product was washed with deionized water and then vacuum filtered using polymer filter paper. The product was dried at 100 °C for 24 h. The XRD pattern of the product was Cu-K α (λ=0.1542nm) for measurement, such as Fig.31 This spectrum can distinguish organic crystalline compounds such as isophthalic acid (C8H6O4, ICCD: 00-037-1920) and phthalic acid (C8H6O4, ICCD: 00-037-1919), both of which have a monoclinic structure, as well as SnO (ICCD: 01-085-0712) and metallic Sn (ICCD: 00-004-0673).
[0520] Fig.32 ac show TEM micrographs of the product obtained by heating the mixture in Ar-5% H2, followed by washing and drying steps. Fig.32 a shows a bright field TEM micrograph of a crystalline organic compound comprising particles agglomerated from nanoparticles with a size range of 1 to 100 nm. Nanoparticles with sizes of 2, 12, and 68 nm can be observed in the micrograph. Fig.32 b shows SnO nanoparticles with a size of 3.8 nm embedded in an organic compound. Fig.32 c is the fast Fourier transform spectrum of SnO nanoparticles, showing spots corresponding to the (101) crystal plane of SnO with a tetragonal structure.
[0521] Example 19 – Water Purification
[0522] The product in Example 18 contains crystalline organic compounds, SnO and Sn, and this product is used as an adsorbent / photocatalyst to remove organic dyes from aqueous solutions. The photocatalytic and adsorption performance tests of the products were carried out at room temperature in a closed metal box. 0.1g of the product was added to 100mL of methyl orange (MO) or methylene blue (MB) solution at a concentration of 50mg / L. The suspension was magnetically stirred for different durations in the dark and under an LED light source module with a fixed wavelength of 450nm in the visible light region. The reaction temperature was maintained at 20°C using a water-cooled jacket. At specific intervals, 2mL of volume was extracted and filtered into a cuvette and characterized using a UV-visible spectrophotometer.
[0523] Based on the absorption peaks obtained, the concentration of the dye solution can be calculated by comparing the absorption spectrum with the standard curve. The value of the adsorption capacity can be calculated using formula (12):
[0524]
[0525] Where qe is the adsorption capacity at equilibrium, m(g) is the mass of the adsorbent, and V is the volume of the dye solution. e are the initial concentration and equilibrium concentration of the dye solution, respectively. The value of the organic compound removal performance (by adsorption or photocatalytic degradation) at a given time (t) can be evaluated according to formula (13):
[0526]
[0527] Among them C t is the concentration of dye in the solution at a given time (t). The dye removal performance of this product is as follows Fig.33 ab. As shown in the figure, the adsorption of the dye on the adsorbent reaches equilibrium after 30 minutes. The adsorption performance of the product for organic dyes at room temperature is 12-21 mg g -1 At a higher temperature of 40 °C, it can increase to 25 mg g -1 For MO, the dye was completely removed from the solution after 7 hours of LED illumination (450 nm). This period was 20 hours for MB. Contrary to theory, in this case, the embedded SnO nanocrystals in the organic compound are responsible for the visible light photocatalytic properties of this nanocomposite.
[0528] Example 20 – Electrochemical Characterization
[0529] The product of Example 18 was mixed with conductive carbon (C45) and PAA-CMC (1:1, weight ratio) binder in a mass ratio of 7:1:1. The mixture was ground into a uniform slurry in deionized water, applied on copper foil, and dried to form an electrode with a loading of about 1.5 mg cm -2 The prepared electrodes were assembled into CR2025 half-cells, with lithium sheets as reference electrodes / counter electrodes and LB-010 as electrolyte. Fig.34 is the lithium ion storage performance of the electrode at a current density of 100 mA g -1 After 140 cycles, the reversible capacity is 707 mAh g -1 .
[0530] The results show that the product containing crystalline organic compound, SnO and Sn in Example 18 can be used as an anode of a metal ion battery, such as an anode of a lithium ion battery. The results also show that the organic compound can effectively affect the electrochemical properties of the metal oxide so that it maintains the lithium ion storage capacity for at least 140 cycles. It is speculated that the organic compound here can maintain the lithium ion, sodium ion or potassium ion storage capacity of the metal oxide or semi-metal oxide during the battery cycle.
[0531] Example 21 - Conversion of PET into nanostructured terephthalic acid using inorganic salts
[0532] PET mineral water bottles were cut into pieces, and 138.5 g of PET pieces were placed in an alumina crucible. Then, 226.3 g of anhydrous SnCl2 (Sigma, 208256, reagent pure 98%) was added to the crucible. The crucible was placed in a vertical furnace and partially covered with an alumina lid. The furnace was heated while the temperature in the crucible was recorded using an alumina protected thermocouple placed in the crucible. The schematic diagram of the apparatus is shown in Figure 1. Fig.35 a. Heating in air for 151 minutes, with a maximum temperature of 303°C, then the furnace was allowed to cool to room temperature. After heat treatment, the contents of the alumina crucible were washed with 700 ml of acidic water (HCl-27%). This acidic water can dissolve the SnCl2 salt but does not cause hydrolysis (SnCl2 interacts with the aqueous solvent to form an insoluble oxide). The suspension was then vacuum filtered and the product was dried at 100°C for 2 hours.
[0533] Fig.35 b shows the temperature-time curve of the mixture when it is heated from room temperature to a maximum temperature of 303°C in 151 minutes. The curve shows two sloping lines, corresponding to the material being heated from 0 minutes (26°C) to 55 minutes (114°C) and from 55 minutes to 95 minutes (257°C). Then, the curve shows a horizontal line from 95 minutes to 106 minutes (259°C). Fig.35c shows the isotherm at a higher time resolution. The average temperature of this section is calculated to be 258.6 °C. Such a horizontal temperature-time section is usually observed during phase change events such as melting. After that, from 106 to 151 minutes, there is another slope with a much smaller slope than that of the initial section, where the highest temperature (303 °C) is recorded. After this, the furnace is turned off and the temperature is allowed to drop to room temperature.
[0534] Fig.36 The phase transformation during the heat treatment can be observed in the XRD pattern of ad. Fig.36 a shows the XRD pattern of a small piece of plastic material, where the broad peak centered at 2θ≈25.4° corresponds to the presence of disordered non-orthorhombic crystals (C 10 H8O4) n (100) reflection in polyethylene terephthalate (PET). The organic polymer material was heated to 260°C overnight and then cooled to room temperature. Fig.36 b shows the XRD pattern of the obtained heat-treated product, indicating the presence of amorphous structured crystalline PET (ICDD≠00-049-2301). The strongest peak observed at 2θ≈26.0 is associated with the (100) reflection, which has shifted to a larger angle compared to the original PET, confirming the process of crystallization.
[0535] The XRD pattern of the standard anhydrous SnCl2 used in this example is as follows Fig.36 c. It is observed that the raw material is mainly composed of monoclinic tin chloride hydrate SnCl2·H2O (ICDD≠01-077-0053) and orthorhombic tin chloride SnCl2 (ICDD≠01-072-0137). Quantitative analysis of the XRD spectrum showed that the ratio of SnCl2·H2O was about 59wt% and 41wt% SnCl2, indicating that there was ≈11wt% hydrated water in the sample. The water absorption of the sample may be caused by the moisture in the atmosphere during the sample processing. The sample obtained by heat treating nominally anhydrous SnCl2 (containing hydrated water) and PET to a maximum temperature of 303°C is shown in FIG. Fig.36 As shown in the figure, the spectrum contains terephthalic acid C8H6O4 (ICDD≠00-022-1941) with a non-orthorhombic crystal structure.
[0536] Example 22 – Thermal Phase Change Analysis
[0537] 11.046 mg PET and 38.401 mg SnCl2 were mixed and placed in an alumina crucible and then heated at 100 mL min -1 10℃ min under airflow -1The DSC and TGA curves of the mixture were measured at a heating rate of 1.5 %. The thermodynamic results of the mixture and PET and SnCl2 tested separately under the same conditions are shown in Figure 2. Fig.37 As shown in af.
[0538] Fig.37 a shows the DSC curve of PET recorded at 50–350 °C, where the endothermic peak observed at 251.3 °C is associated with the melting of the material. There are no additional peaks and melting is the only transition after heating PET to 350 °C. Fig.37 This is confirmed by the TGA results shown in (d), where the total mass losses at 250, 270, and 350 °C are 0.73, 1.06, and 1.47%, respectively. The small mass loss observed is associated with the gradual evaporation of surface organic contaminants and water. Fig.36 This result is further confirmed by the X-ray diffraction pattern of (b), where no phase transition was observed upon heating PET at 260 °C overnight.
[0539] Fig.37 b shows the DSC curve of nominally anhydrous SnCl2, which contains about 11 wt.% water from the environment ( Fig.36 c). The DSC curve shows an obvious endothermic peak only at 259.1℃, which is related to the melting of SnCl2. Fig.37 As shown in Figure e, the TGA curves of the samples show that the mass losses are 0.61%, 0.89%, and 1.47% at 250, 270, and 350 °C, respectively. Based on the observations, it can be concluded that SnCl2 is able to absorb moisture and retain a considerable portion of hydration water at relatively high temperatures, even after melting.
[0540] Fig.37 c shows the DSC curve recorded on a mixture of PET (11.046 mg) and SnCl2 (38.401 mg). The endothermic peak observed at 258.2 °C can be attributed to the eutectic melting of PET and SnCl2, which is consistent with the Fig.35 This is consistent with the isotherm event at 258.6 °C in c. Fig.37 f shows the TGA curve of the PET+SnCl2 mixture, with mass losses of 1.49%, 2.56% and 23.23% at 250, 270 and 350°C, respectively. Considering that there is about 11 wt.% hydrated water in SnCl2, the total amount of hydrated water in the salt originating from SnCl2·H2O is estimated to be about 8.5 wt.% (4.224 mg). Therefore, at 250°C, just before eutectic, there may be about 7 wt.% hydrated water in the PET+SnCl2 mixture.
[0541] It is speculated that moisture causes the depolymerization of PET. According to possible reaction (3) (discussed above), hydrated SnCl2 and PET co-melt at around 258°C, with the hydrated SnCl2 retaining most of its moisture. At temperatures around 290-320°C, the moisture in the melt causes PET to depolymerize into its monomers, namely terephthalic acid (C8H6O4) and ethylene glycol ((CH2OH)2, which evaporates along with the remaining moisture. Fig.37 The results of the endothermic peak with a maximum value at 314.9 °C in the DSC curve also confirm this process. A mass loss of 15 wt.% ( Fig.37 f) corresponds to the evaporation of ethylene glycol and residual water, leaving solid PET and molten SnCl2. The XRD pattern of the product obtained by heating PET+SnCl2 ( Fig.36 d) confirmed the above mechanism. The peak values are shown in Table 3.
[0542] Table 3. XRD peak information
[0543]
[0544]
[0545] The half-peak width (FWHM, 2θ) values of the peaks at 2θ values of 16.99, 24.54 and 29.31 are 0.1496, 0.1309 and 0.1870 degrees, respectively. Using these values, the average crystal size in different crystal directions was calculated according to the Scherer equation:
[0546] D=(kλ / βcosθ) (14)
[0547] Where k is the Scherer constant (K = 0.9), λ is the wavelength of the X-ray β is the FWHM of the diffraction peak in radians, and θ is the diffraction angle. Fig.36 In the diffraction pattern of d, the average crystal sizes of the peaks located at 2θ values of 16.99, 24.54 and 29.31 were calculated to be 53.6 nm, 62.1 nm and 43.5 nm, respectively.
[0548] Example 23 – Microstructural Characterization of Terephthalic Acid Produced from Waste Plastics
[0549] Fig.38 ac show SEM (FEI Nova Nano-SEM) micrographs of terephthalic acid produced by heat treatment of PET and nominally anhydrous SnCl2 at 303°C (Example 21). Fig.38a shows an agglomerated particle with an overall size of 26 μm. As shown in the micrograph, this agglomerated particle contains nanoscale entities, with entity sizes typically less than 200 nm. Other morphologies observed in the terephthalic acid product include Fig.38 b and 38c. Fig.38 b exhibits a platelet-like morphology, with overall dimensions typically less than about 1 μm, such as 411 nm. Platelet-like particles may include nanoscale entities with dimensions less than 50 nm, such as 27 nm. Fig.38 b also confirms the presence of agglomerated nanostructured particles, highlighting an entity with a particle size of 38 nm. Fig.38 c shows agglomerated nanoparticles with higher resolution. From this micrograph, the terephthalic acid nanoparticles were measured to be smaller than 100 nm, for example 53 and 57 nm. The microstructure of the prepared terephthalic acid is different from existing terephthalic acid materials. Fig.39 ab show SEM micrographs of commercially available crystalline terephthalic acid (Merck, 8.00762, purity ≥98%). Fig.39 As shown in a, terephthalic acid particles are usually much larger than 1 μm and can reach hundreds of microns in size, such as 332 μm. Fig.39 b shows a micrograph at a higher magnification, which clearly shows that the particles are not porous, unlike the terephthalic acid material produced by the depolymerization of PET and SnCl2 ( Fig.38 ac).
[0550] The terephthalic acid obtained by depolymerization of PET and SnCl2 is different from the commercially available terephthalic acid samples. The former has a unique nanostructure morphology and is also different from the terephthalic acid reported in the literature.
[0551] Example 24 – Electrochemical Performance of Nanostructured Terephthalic Acid
[0552] Terephthalic acid produced by depolymerization of waste PET using SnCl2 (Example 21, such as Fig.38 ac) was uniformly mixed with conductive carbon (C45) and PVDF binder in a mass ratio of 60:30:10 and NMP was used as solvent. The resulting slurry was then coated on copper foil using a doctor blade and dried in a vacuum oven at 80 °C for 12 h to obtain a carbon fiber with a density greater than 1.5 mg cm -2 Then, a coin-type half-cell (CR 2032) was assembled using metallic sodium as the counter electrode, 1.0 M NaCF3SO3 diethylene glycol dimethyl ether solution as the electrolyte, and glass microfiber (Whatman, 1823025) as the separator. The battery was tested on a battery test system after being stabilized at room temperature for 10 hours, where the Na ion insertion / extraction cycle was carried out at a constant current density of 30 mA / g at 0.01-3.0 V vs Na / Na +The constant current discharge-charge curves of the first and second cycles are shown in Fig.40 ab. It can be seen that 0.26Vvs Na / Na appears during the first cycle discharge process + (0.23-0.33V vs Na / Na + ) platform, and there is 0.5V vs Na / Na during charging. + Similarly, during the discharge process of the second cycle, 0.28V vs Na / Na + (0.25-0.35V vs Na / Na + ) platform, 0.5V vs Na / Na appears during the charging process + (0.45-0.55V vs Na / Na + ). The platform observed in the second discharge / charge cycle was repeated in the subsequent lithium ion insertion / extraction cycles and was maintained at 100, 500, 1000, and 5000 cycles. The sodium ion storage capacity obtained during the second discharge process was 209.1 mAh g -1 .
[0553] During the discharge / charge process, there is 0.28 / 0.5V vs Na / Na + The platform is very favorable for Na ion storage. This can bring higher safety and avoid the problem of near 0V vs Na / Na + The voltage of 100V leads to sodium deposition on the electrode surface. This value is also relatively low, ensuring high energy density of the battery when using nanostructured terephthalate as the negative electrode material.
[0554] The results show that the insertion / extraction of Na ions into / from the electrode made of nanostructured terephthalic acid occurs at 0.28 / 0.5 V vs Na / Na + , providing safety and high energy density characteristics for batteries using nanostructured terephthalic acid as negative electrode material. The results show that nanostructured terephthalic acid can be used as an electrode for metal ion batteries, including lithium ion, sodium ion and potassium ion batteries.
[0555] Example 25 – Conversion of PET into nanostructured terephthalate with oxide or hydroxide phase using inorganic salts acid
[0556] PET plastic sheets (20.1 g) made from cutting waste water bottles were mixed with nominally anhydrous SnCl2 (142.0 g), and the mixture was then placed in an alumina crucible. The crucible containing the mixture (162.1 g) was placed in an airtight reactor, and the reactor was placed in a vertical resistance furnace. The temperature in the crucible was measured using an alumina protected thermocouple placed in the mixture. The furnace was heated from room temperature to a maximum temperature of 333 °C while passing Ar gas (60 mL min -1 ). The temperature in the crucible increased from 23°C to a maximum temperature of 312°C in 137 minutes. The temperature was then maintained at the maximum temperature for 13 minutes before the furnace was turned off. After the furnace was cooled to room temperature, the material in the crucible was weighed to be 148.3 g. The weight loss (13.8 g) mainly corresponds to the evaporation of ethylene glycol and the remaining water of the melt during the conversion of PET into nanostructured terephthalic acid. The conversion of PET into terephthalic acid using the hydration water (water) in the salt, together with the loss of ethylene glycol, can lead to a mass loss of 13.54%, as shown in reaction (3).
[0557] 20.1 g of PET yielded 17.3 g of terephthalic acid, resulting in a mass loss of approximately 2.8 g. The additional mass loss of approximately 11 g was attributed to the evaporation of the remaining hydration water during the depolymerization process. Based on these calculations, it is expected that 142 g of SnCl2 can produce 85 g of nanostructured terephthalic acid at a temperature of around 300 °C.
[0558] The material obtained by heat treatment of PET and SnCl2 was washed with distilled water (pH ≈ 7) and the obtained suspension was filtered. The product was dried at 80°C for 2 hours and then subjected to X-ray diffraction analysis. The obtained spectrum is as follows Fig.41 As shown, the terephthalic acid monomer C8H6O4 (ICDD≠00-021-1919) with a triclinic crystal structure as the main component and Sn with a rhombohedral crystal structure as the auxiliary component 21 Cl 16 (OH) 14 O6 (ICDD≠00-035-0907). Sn 21 Cl 16 (OH) 14 The formation of O6 may be related to the hydrolysis of SnCl2 during the distilled water washing step (as shown in reaction (1)).
[0559] Sn 21 Cl 16 (OH) 14 O6 has a low solubility in water and therefore remains in the nanostructure of terephthalic acid after washing and filtration.
[0560] Example 26 – Thermal treatment of PET with SnCl2 in the presence of Si to prepare organic compounds embedded in SiNPs
[0561] 6 g of SiNPs (Sigma Aldrich, 633097) with a nominal particle size of less than 100 nm and a spherical morphology were mixed with 20 g of waste PET plastic bottles (cut into pieces several centimeters long) and 159.6 g of SnCl2 powder (Sigma Aldrich, 208256). The mixture was loaded into an alumina crucible. The crucible was placed in an Inconel gas-tight reactor equipped with a gas inlet / outlet. The reactor was located in a resistance furnace and heated from room temperature to a maximum temperature of 284 ° C under the flow of Ar-5% H2, and then stayed for 5 minutes. Then, the temperature was lowered to room temperature, and 1 g of the obtained product was washed with dilute hydrochloric acid (10%) to remove the remaining salt, and then dried at 100 ° C for 2 h under the flow of Ar-5% H2. Then, the obtained sample was measured using an electron microscope. Fig.42 An SEM micrograph of the product is shown, indicating the presence of a porous morphology with SiNPs embedded in terephthalic acid. Fig.43 A higher magnification SEM micrograph is shown, demonstrating the presence of spherical SiNPs in the terephthalic acid matrix. Two SiNPs with diameters of 84 nm and 106 nm are highlighted in the micrograph.
[0562] Example 27 – Electrochemical performance of organic compounds embedded in SiNPs
[0563] 12.21 g of the product obtained by heating a mixture of PET, SnCl2 and SiNPs to 284°C (Example 26) and 2.05 graphene nanosheets were added to 400 mL of concentrated sulfuric acid, and the suspension was ultrasonically treated for 20 minutes and then magnetically stirred for 20 minutes. The suspension was filtered, and the product was washed with deionized water and dried at 180°C for 5 h under the flow of Ar-5% H2. The XRD spectrum of the obtained product is shown in Fig.44 As shown. It can be observed that the obtained product contains terephthalic acid (ICCD: 00-021-1919), silicon (ICCD: 01-089-2749) and graphite carbon (ICCD: 01-075-2078). EDS analysis of the sample shows the presence of silicon (≈28 wt.%) in the sample.
[0564] The obtained material was used to prepare the negative electrode of lithium-ion batteries. PI powder was added to 400 μL NMP and stirred. Then, the sample containing silicon, terephthalic acid and graphene ( Fig.44 ) was added to the PI solution, and the mixture was sonicated and then magnetically stirred for 10 h to obtain a uniform slurry. The resulting uniform slurry was coated on a Cu foil, dried at room temperature for 10 min, and then vacuumed at 100 °C for 2 h to remove NMP. After drying, the electrode was heated at 2 °C min in a tube furnace under the flow of Ar-4% H2. -1The cells were heated to 250 °C at a heating rate of 100 ℃ and the residence time at 250 °C was 2 h. The temperature was then lowered to room temperature under the same airflow. The electrodes obtained were used to assemble button cell CR 2025 half-cells, in which metallic lithium was used as counter and reference electrodes. 1.0 M LiPF6 dissolved in EC:DEC:EMC (1:1:1 wt.%) and Celgard 2400 polypropylene film were used as electrolyte and separator, respectively. The cell was allowed to equilibrate at room temperature for 10 h and then charged at 0.01–3.0 V vs Li / Li at a constant current density of 100 mA / g. + The typical cycling performance of the electrode is as follows: Fig.45 As shown in Figure 2, it can be observed that after 130 cycles of lithium ion insertion and extraction, there is a reversible capacity of 1285 mAh / g. This capacity is calculated based on the total mass of silicon / terephthalic acid / graphene.
[0565] The results suggest that materials with SiNPs embedded in crystalline organic compounds could be used as negative electrodes for metal-ion batteries, such as lithium-ion batteries.
[0566] Example 28 – Conversion of waste plastics into organic compounds embedded with Zn-MOFs
[0567] 16.1 g ZnCl2 (Sigma, 98%) was mixed with a small piece of waste PET material (11.5 g). The mixture (27.6 g) was placed in an alumina crucible, which was placed in a gas-tight steel reactor. The latter was placed in a vertical furnace. The reactor was heated while passing Ar gas (60 mL / min) through the reactor. The temperature in the crucible (measured using an alumina protected thermocouple) was 7 ° C min -1 The heating rate was increased from room temperature to 373°C. Then, the furnace was turned off and the temperature was allowed to cool to room temperature. The obtained product (21.4 g) was washed with distilled water to dissolve the salt and then filtered. The obtained product was dried at 80°C for 2 h and then characterized.
[0568] Fig.46 The X-ray diffraction pattern of the product is shown, based on which the presence of zinc terephthalate hydrate (ZnC8H4O4·3.5H2O, or ZnTP·3.5H2O, ICDD: 00-038-1777) as the main phase was confirmed. Fig.46 It is shown that in addition to the zinc metal organic framework, there are also x H y O z Table 4 reports the 2θ, FWHM, and intensity values associated with ZnC8H4O4·3.5H2O and the observed organic compounds.
[0569] Table 4. XRD peak information of ZnC8H4O4·3.5H2O (referred to as A in this article) and organic compounds (referred to as B in this article) at 2θ Between 1-50 degrees.
[0570]
[0571]
[0572] Example 29 – Conversion of waste plastics into metal-organic frameworks
[0573] 8.47 mg of PET flakes were mixed with 30.51 g of nominally dried ZnCl2 and the mixture (38.98 mg) was placed in an alumina crucible. The crucible was placed in a thermal analysis apparatus at 100 mL min -1 Ar flow rate at 20 °C min -1 The heating rate was 0.15°C and the temperature was heated to 1200°C. Fig.47 and Fig.48 The recorded TGA and DSC curves are shown, respectively.
[0574] according to Fig.47 The TGA curve shows that when heated to 170°C, the mass loss is 0.35%, accompanied by an endothermic peak with a peak value of 110°C ( Fig.48 ). This reaction is associated with the evaporation of non-hydrated water in the material. A second endothermic peak is observed at 195°C, which is associated with the glass transition reaction. This reaction is accompanied by further evaporation of water (1.41%) in the temperature window of 170-227°C. The third endothermic peak (235°C, Fig.48 ) is accompanied by a mass loss of 1.85% in the temperature window of 227-248°C. This reaction may be related to the evaporation of ZnCl2 hydration water. The dehydration of ZnCl2 provides water for the depolymerization of PET. The depolymerization reaction may be related to an exothermic reaction with a peak of 287°C, which is accompanied by the evaporation of depolymerization byproducts (such as ethylene glycol) and residual water, resulting in a mass loss of 3.99wt% in the temperature window of 248-316°C. It is speculated here that according to Fig.48 The DSC curve shows an endothermic reaction at 321°C, which corresponds to the melting of dehydrated ZnCl2 and the reaction of molten ZnCl2 with monomers (such as terephthalic acid, TPA) formed by the depolymerization of PET to form zinc terephthalate. Figure 5c ).
[0575] from Fig.47From the TGA graph, it can be seen that a mass loss of 3.92 wt% is observed in the range of 316-416 °C, which may be related to the gradual removal of HCl from the system. From 416 to ≈800 °C, a large mass loss of 78.26% occurs, which may be related to the decomposition of the Zn metal organic framework, the evaporation of the remaining organic matter (terephthalic acid + terephthalate) and the molten ZnCl2. The remaining mass is relatively stable at higher temperatures, and an amount of 9.0 g is obtained at the end of the heat treatment at 1200 °C. The residual material was analyzed by XRD ( Fig.49 ), and was found to be ZnO having a hexagonal crystal structure (ICSD: 01-079-0207).
[0576] Example 30 – Morphological Characterization of Organic Compounds Embedded in Zn-MOF
[0577] Fig.50 A backscattered electron micrograph of the product of Example 28 is shown, indicating the presence of crystals ranging in size from substantially less than 1 μm to several microns embedded in the organic compound.
[0578] Energy dispersive X-ray spectroscopy (EDS) of ZnMOF crystals and organic compounds such as Fig.51 As shown in Figures ac, it is confirmed that the main elements such as C, Zn and O exist in the Zn metal organic framework, and C and O exist in the organic compound. There is no hydrogen element because EDS cannot detect hydrogen. There is a small amount of Cl in the sample, which may be the residue of ZnCl2 used in the product preparation process. In addition, the EDS elemental map analysis on the backscattered electron micrograph is shown in Figure 4. Fig.52 As shown in Figure 2, the concentration of zinc in the Zn-MOF crystals is much higher. The Zn-MOF crystals have different sizes and shapes. Fig.53 b shows a size distribution histogram of more than 100 crystals. It can be seen that the size of the crystals is generally less than 20 μm, while the size of most crystals is between 1 and 4 μm. There is also a small number of crystals in the range of about 10 nm to 1 μm.
[0579] Fig.54 ad shows backscattered electron micrographs of a zinc metal organic framework embedded in an organic compound (the product of Example 28), highlighting the morphological features of some nanocrystals. Fig.54 As can be seen in a, the total size of the organic compound embedded in the ZnMOF is at most several hundred micrometers, such as 700 μm, 500 μm and 400 μm. Fig.54 b. The total size of the zinc metal organic framework embedded in the organic compound particles is at least 50 μm, 40 μm, 30 μm, 20 μm, 10 μm, 8 μm, 5 μm, 2 μm, 1 μm or 500 nm. Fig.54c and 54d, Zn-MOF crystals are faceted crystals that are embedded in organic compounds. The size of the faceted Zn-MOF crystals ranges from 50 nm to 10 μm.
[0580] Fig.55 ad shows secondary electron scanning electron micrographs of a zinc metal organic framework embedded in an organic compound (the product of Example 28), highlighting some of the morphological features of the organic compound. Fig.55 a and 55b, the product comprises particles with a total size of up to 600 μm or as small as 10 μm. These particles contain zinc metal organic crystals embedded in an organic compound. The shape of the zinc metal organic framework crystals is as follows Fig.55 c and 55d. These images show the presence of faceted crystals with square, rectangular, pentagonal, or hexagonal surfaces. Although most of the crystals were embedded in organic compounds, isolated Zn-MOF crystals were also detected.
[0581] according to Fig.55 In the micrograph of ad, in addition to the metal organic framework crystals, two other morphologies were observed: flake particles and agglomerated nanoparticles. Organic compound flake particles can be found in Fig.55 c and 55d. The lateral size of the plate-like particles varies from 100 nm to several micrometers, such as 10 μm. The thickness of the plate-like particles is approximately between 1 and 10 nm.
[0582] Transmission electron microscopy (TEM, Tecnai F20, 200 kV) was used to further understand the morphological characteristics of the Zn metal organic framework embedded in the organic compound product. Fig.56 A low magnification TEM micrograph of the product is shown, which features zinc terephthalate hydrate (ZnC8H4O4·XH2O) embedded in an organic compound. The woven flake particles and agglomerated nanoparticles are clearly distinguishable. Fig.56 Two woven flake particles with sizes of 750nm×1.1μm and 484nm×584nm can be observed in the . The surface of the flake particles is woven / modified with nanoparticles, e.g. Fig.57 High-magnification TEM micrograph of a shows the flake-like particles.
[0583] like Fig.57 As shown in a, the surface of the platelet-like particles is composed of nanoparticles of various sizes and shapes, mainly hemispherical and worm-like nanoparticles. Fig.57 b shows the records Fig.57a Histogram of the size distribution of more than 100 nanoparticles present on the surface of a plate-like particle. The size ranges of the surface nanoparticles are 0-4nm (5%), 5-9nm (38%), 10-14nm (37%), 15-19nm (7%), 20-24nm (6%), 25-29nm (2%) and 30-60nm (8%).
[0584] Fig.58 a shows a TEM image of the prepared Zn-MOF embedded with organic compounds, and the image shows micron-sized particles containing agglomerated nanoparticles. It can be observed that nanoparticles of various sizes agglomerated to form micron-sized particles. Fig.58 b shows the records Fig.58 a Size distribution histogram obtained for the sizes of more than 60 nanoparticles present in the micrograph. The size ranges of the nanoparticles are 5-9 nm (38%), 10-14 nm (22%), 15-19 nm (10%), 20-24 nm (3%), 25-29 nm (4%) and 30-60 nm (3%).
[0585] Example 31 – Lithium-ion storage performance of organic compounds embedded in Zn-MOFs
[0586] Embed C X H y O z ZnC8H4O4·3.5H2O (as described in Examples 28 and 30) is used to make electrodes. ZnC8H4O4·3.5H2O is embedded in C X H y O z The material, PVDF binder (in NMP) and conductive carbon (Super P) were mixed in a ratio of (6:3:1) to make a uniform slurry, which was coated on copper foil and dried in vacuum at 80 °C for 10 h to remove NMP. The final loading was greater than 1.5 mg cm -2 CR 2025 button cells were assembled with metallic lithium as the counter electrode and reference electrode, 1.0M LiPF6 EC:DEC:EMC (1:1:1wt%) solution and Celgard 2400 polypropylene film as electrolyte and separator, respectively. + The cycling performance was measured at a current density of 100 mA / g over a potential range of 200 Å. Fig.59 As shown in Figure 2, after 156 cycles of lithium ion insertion and extraction, a high reversible specific capacity of 326.3 mAh / g was achieved.
[0587] Example 32 – Thermal treatment of ZnC8H4O4·3.5H2O embedded in an organic compound
[0588] The embedded organic compound (CX H y O z ) is converted into ZnC8H4O4·3.5H2O in heat-treated Zn-TP embedded in terephthalic acid (TPA). X H y O z ) was heated at 150 °C for 2 h under Ar. The X-ray diffraction pattern of the heat-treated sample was compared with that of the original sample. Fig.60 ab. The XRD original sample is as follows Fig.60 As shown in a, the XRD heat-treated sample Fig.60 b. The heat-treated material contains zinc terephthalate (Zn-TP) and terephthalic acid (TPA) produced by heat treatment. The XRD spectrum data of zinc terephthalate (Zn-TP) is provided by the single crystal compound calculated in the following literature. [M.Nakhaei et al., Antibacterial activity of three zinc-terephthalate MOFs and its relation to their structural features, Inorganica Chimica Acta 522 (2021) 120353].
[0589] exist Fig.60 In a, the FWHM of the diffraction peak with a 2θ value of 11.75° is 0.150°, and the grain size is 53.2nm. The FWHM of the diffraction peak with a 2θ value of 16.592° is 0.187°, and the grain size is 42.9nm. The FWHM of the diffraction peak with a 2θ value of 35.202° is 0.228°, and the grain size is 36.5nm.
[0590] exist Fig.60 In b, the FWHM (2θ, degrees) values of the peaks at 9.89, 19.33, 25.27, and 40.11 degrees are 0.1299, 0.1948, 0.1624, and 0.2922, respectively. The average grain sizes associated with these peaks were calculated to be 61.4 nm, 41.3 nm, 50.1 nm, and 28.9 nm. The values of the peaks are shown in Table 5.
[0591] Table 5. XRD peak information
[0592]
[0593]
[0594] Example 33 - Metal Ion Stories of Zinc Terephthalate (Zn-TP) Intercalated with Terephthalic Acid (TPA) after Heat Treatment Storage performance
[0595] To observe the sodium ion storage performance, an electrode made of Zn-TP embedded in terephthalic acid (as described in Example 31) was used as the active material. To this end, NMP was used as a solvent and the active material was mixed with conductive carbon (C45) and PVDF binder in a mass ratio of 6:3:1. The resulting slurry was then coated on a copper foil using a 200 μm doctor blade and dried in a vacuum oven at 80 °C for 12 h. The loading of the electrode was about 1.5 mg cm -2 . A coin-type half-cell (CR 2032) was assembled using metallic sodium as the counter / reference electrode, 1.0 M NaCF3SO3 in diethylene glycol dimethyl ether as the electrolyte, and glass microfiber (Whatman, 1823025) as the separator. The half-cell was assembled in a glove box under high purity argon with O2 and H2O content less than 0.1 ppm. The cell was tested on a battery test system after stabilization at room temperature for 10 hours, with a voltage of 0.01-3.0 V vs Na / Na + The voltage range is 30mA g -1 The constant current charge-discharge curves were recorded at a current density of 30 mA / g. The discharge / charge curves for the first four cycles are shown in Figure 2. Fig.61 As shown in ad. It can be observed that the first discharge curve is at 0.8V and 0.25V vs Na / Na + The charge curve shows a plateau at about 0.5 V vs Na / Na. + There is a plateau between 0.25V and 0.3V vs Na / Na + The discharge platform of about 0.5V vs Na / Na is much higher than 0.0V, which can avoid the formation of metallic Na on the electrode surface, thereby improving the safety of the electrode. + The charging platform is low enough to ensure the high energy density of the battery with Zn-TP embedded in terephthalic acid as the negative electrode active material. Fig.62 Shows that at 30mA g -1 The cycling performance of the electrode was recorded below, with a reversible capacity of 200 mAh / g after 10 cycles of Na ion insertion and extraction.
[0596] The lithium ion storage performance of heat-treated Zn-TP embedded in terephthalic acid was also examined. Zn-TP embedded in terephthalic acid was mixed with PVDF binder and conductive carbon (Super P) (6:1:3) using NMP as solvent. The prepared slurry was coated on copper foil and dried in vacuum at 80 °C for 10 h. As described in the previous example, button cells were assembled using Li as the counter / reference electrode and 1.0 M LiPF6 in EC:DEC:EMC (1:1:1 wt%) solution as the electrolyte. The mass loading was approximately 1.5 mg cm -2 The electrode is at 0.01-3V vs Li / Li + In the potential window of 100 mA g -1 current density cycle. Fig.63 The cycling performance of the electrode is shown. After 23 lithium ion insertion and extraction cycles, the battery has a capacity of 252 mAh g -1 Stable reversible capacity.
[0597] The results show that the heat-treated Zn-TP embedded in the terephthalic acid product (obtained in Example 31) can be used as the negative electrode of metal ion batteries, such as the negative electrode of sodium ion batteries (SIBs) or lithium ion batteries (LIBs).
[0598] Example 34 - Treatment of HDPE with SnCl2
[0599] A plastic bottle made of HDPE was cut into pieces of several centimeters in size. 30.0 g of HDPE pieces were mixed with 140.0 g of SnCl2, and the mixture (170.0 g) was loaded into an alumina crucible. The crucible was heated to 337 °C in a vertical resistance furnace under argon flow, with an average heating rate of 3 °C min -1 , while measuring the temperature inside the crucible throughout the experiment. After the heating was terminated, the crucible was cooled to room temperature. The mass of the material after heat treatment was measured to be 168.0 g, and the loss of mass ≈ 0.7% is negligible and corresponds to the dehydration of the material during the heat treatment. Fig.64 a shows untreated HPDE, Fig.64 b shows the heat treated HDPE. Fig.64 As shown in b, HDPE is not depolymerized during the thermal treatment and is therefore easily collected from the container.
[0600] The X-ray diffraction patterns of HDPE before and after heat treatment are shown in Fig.65 a and 65b. The XRD patterns show that the crystal structure of HDPE remains unchanged during this process.
[0601] The results show that heating a mixture of PET and HDPE with SnCl2 to a sufficiently high temperature will cause PET to depolymerize, while HDPE will melt during the heating process and sink to the bottom of the container, leaving a porous structure of terephthalic acid monomer produced by the depolymerization of PET in the upper part of the container.
[0602] Example 35 – UV-Vis Spectrophotometer Measurement
[0603] Fig.66 a shows the UV-visible absorbance spectra of nanostructured terephthalic acid (TPA) prepared by thermal treatment of PET and SnCl2 (as described in Example 21) and commercially available terephthalic acid. The samples were tested by first adding the samples to deionized water, then ultrasonically cleaning them for 10 minutes, and then measuring their absorption spectra using a UV-visible spectrophotometer (Thermo Scientific Evolution 220). The concentration of TPA was controlled at 0.5 g L -1 , and first detect the absorption spectrum of pure water as the baseline, and when actually detecting TPA, the absorbance of water is automatically deducted as the baseline.
[0604] from Fig.66 As can be seen in a, both samples show peaks at approximately the same wavelength number; 242 nm for nanostructured terephthalic acid and 241 nm for commercial terephthalic acid, indicating that the crystal structures of the two compounds are the same.
[0605] Despite this similarity, the two compounds show significant differences in absorbance. First, the absorbance of nanostructured terephthalic acid at 242 nm (1.840 au) is approximately 2.3 times greater than the absorbance of commercial terephthalic acid at the absorption peak (0.815). Second, the absorbance of commercial terephthalic acid approaches zero after wavelengths greater than 300 nm. In contrast, nanostructured terephthalic acid shows relatively large absorbance at all wavelengths. For example, at 0.5 g L -1 At concentrations, Fig.66 The following absorbance data were observed in a: 450 nm (0.564 au) and 500 nm (0.548 au).
[0606] also, Fig.66 b shows that nanostructured terephthalic acid has an additional peak at 317 nm, which does not exist in commercial terephthalic acid. Without being limited by theory, it is speculated that this peak is attributed to the presence of nanopores on the surface of nanostructured terephthalic acid, which will bring additional absorbance characteristics.
[0607] like Fig.28 As shown in ab, the color of nanostructured terephthalic acid is much darker than the appearance of commercial terephthalic acid and can be distinguished by the human eye.
[0608] Example 36 – Production of Na2TP using commercial and nanostructured TPA
[0609] Mix 1.5 g NaOH and 1.5 g TPA (commercial TPA or nanostructured TPA) in 60 mL ethanol (purity ≥ 99.7%, 0.789-0.791 g mL at 20 °C). -1 ) and then magnetically stirred for different times (6h, 12h, 18h and 24h). After the time is up, the mixture is centrifuged to recover the product, which is then dispersed in ethanol and centrifuged again. The last step is repeated twice, and the resulting powder is then dried under vacuum at 150°C for 1h.
[0610] X-ray diffraction patterns of commercial TPA, nanostructured TPA and products obtained with different stirring times were detected. The instrument was PANalyco instrument and the radiation source was Cu-K α ray The step size was 0.033°, the dwell time was 45 s, and the scanning speed was 0.094 degrees per second.
[0611] like Fig.67 As shown in a, all diffraction peaks of nanostructured TPA are terephthalic acid (ICDD#00-021-1919) with a triclinic crystal structure, proving the successful preparation of nanostructured TPA. Among the diffraction peaks, the peak 2θ values with higher intensity values are located at 17.517° (FWHM = 0.276°), 25.301 (FWHM = 0.276°) and 28.080° (FWHM = 0.335°).
[0612] Fig.67 b shows that the diffraction peaks of commercially available TPA are those of terephthalic acid (ICDD#00-021-1919) with a triclinic crystal structure. XRD peaks of commercial TPA can be observed at 2θ values of 17.483° (FWHM=0.138°), 25.291° (FWHM=0.197°), and 28.019° (FWHM=0.157°). It can be observed that the FWHM value of nanostructured TPA is much larger than that of commercial TPA, indicating that the grain size of nanostructured TPA is much smaller.
[0613] Fig.67 ce show commercial TPA after 6 h, 12 h, and 18 h of treatment, respectively, without showing any structural changes, indicating that the kinetics of the process are relatively slow.
[0614] Compared with commercial TPA, nanostructured TPA is much more reactive with NaOH, so a treatment of only 6 h (or less) is sufficient to prepare Na2TP.
[0615] Example 37 - Silicon thermally modified PI electrode for lithium ion storage
[0616] The effect of PI binder on the lithium storage performance of SiNPs (particle size = 20-60 nm, ≥99.9%, Aladdin) was studied by assembling half-cells. First, 10 mg of PI powder (PI, Mw = 50000-80000, Macklin) was mixed with 405 mg (400 μL) of NMP to form a uniform solution. Then, 10 mg of conductive carbon (Super P, ≥99.9%) and 80 mg of SiNPs were added to the PI solution, and the mixture was ultrasonically treated for 2 h to achieve uniform dispersion. Thereafter, the dispersion was stirred for 3 h, and the resulting slurry was coated on a copper foil. After drying at room temperature for 10 min, it was dried at 100 °C under vacuum for 2 h to remove NMP. After drying, the electrode was heated to different temperatures of 300, 350, and 400 °C in a tube furnace under a gas flow of Ar-4% H2 at a heating rate of 2 °C min -1 , and stay at this temperature for 2 h. Then the temperature was lowered to room temperature under the same airflow, and button batteries were assembled using the obtained electrodes. Fig.68 A schematic diagram of the process used to prepare the electrodes is shown.
[0617] As a control, PAA / CMC (1:1 mass ratio) was used as a binder and the electrodes were manufactured in the same manner as above, but without the high-temperature heat treatment step. The assembly of button cells (2025 type) was carried out in an argon-filled glove box, using polypropylene as a separator, 1M lithium hexafluorophosphate (LiPF6) as an electrolyte lithium salt, and a mixture of ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) (EC / DEC / DEC=1:1:1 mass ratio) as an electrolyte solvent. In the assembled button cells, metal lithium sheets were used as reference electrodes and counter electrodes. The X-ray diffraction (XRD) equipment was D8 ADVANCE, the measurement range was 2θ=10-80°, and the X-ray source was Cu-K α radiation Fourier transform infrared (FTIR) tests were performed using a VERTEX70 device. X-ray photoelectron spectroscopy (XPS) tests were performed using a Thermo Scientific K-Alph instrument. UV-visible absorption spectroscopy was performed using an Evolution 220 instrument. Before the cycled electrode morphology was studied using a scanning electron microscope (SEM, ZEISS EVO18), the electrodes were immersed in dimethyl carbonate (DMC) overnight. Constant current charge and discharge measurements were performed at 0.01-3.0 V (25 °C) using a LAND battery test system. Cyclic voltammetry was used to study the electrochemical process on the electrode, and the equipment was an electrochemical workstation (CHI 660E, China) with a scan rate of 0.1 mV s-1 , voltage range is 0.01-3.0V vs Li / Li + Electrochemical impedance spectroscopy (EIS) measurements were performed using an alternating current with an amplitude of 5 mV and a frequency range of 100 kHz to 10 MHz. EIS data were measured using a CHI 660E electrochemical workstation at OCV steady state.
[0618] The PI material used is a thermoplastic polymer formed by polycondensation and imidization of 1-(4-aminophenyl)-1,3,3-trimethyl-2H-inden-5-amine (DAPI) and benzophenone-3,3',4,4'-tetracarboxylic dianhydride (BTDA), and is soluble in NMP.
[0619] After the PI material was heated to 350°C and maintained for 2 h, the PI material underwent an obvious change from light yellow powder to dark brown hard block. Fig.69 a and 69b show the photographs of PI before and after heat treatment, respectively. It was observed that the heat treated PI (PI-350) became insoluble in polar solvents, e.g. Fig.69 c. It is speculated that this phenomenon can be attributed to the cross-linking and / or crystallization of the compound. In order to study the changes in the crystalline structure of PI, the samples before (PI) and after (PI-350) heat treatment were analyzed by X-ray diffraction, and the obtained spectra are shown in Fig.70 shown.
[0620] In the XRD pattern of PI before heat treatment, two broad diffraction peaks appeared at 2θ = 10-30° and 2θ = 40-50°, corresponding to the amorphous structure of PI, indicating the disordered arrangement of PI molecular chains. At the same time, these two broad peaks also appeared in the XRD pattern of PI-350, indicating that PI-350 has the same amorphous structure. Table 6 lists the physical properties of PI before and after heat treatment. It can be seen that in addition to the differences in appearance and NMP solubility, the mechanical hardness of PI-350 is much higher than that of PI. This implies that the polymer chains in PI-350 are more tightly stacked and the intermolecular space is smaller. As described later, this property helps to improve the mechanical properties of PI binders to alleviate the problems caused by volume expansion involved in Si electrode cycling.
[0621] Table 6. Selected properties of PI before and after heat treatment.
[0622] feature Original polyimide PI-350 structure Amorphous Amorphous color Light yellow Dark Brown Appearance Powder Block Solubility in NMP high Low
[0623] Without being bound by theory, it is speculated that the cross-linking between PI molecular chains that occurs during the heat treatment process may lead to the formation of charge transfer complexes (CTCs), which in turn leads to the observed differences in properties between the original PI and PI-350. It is speculated that CTCs are formed by electron transfer between electron-rich donor molecules and electron-poor acceptor molecules (such as five-membered imide rings and benzene rings). It is also speculated that after heat treatment, the molecular chains of PI are able to approach each other closely enough to allow p-electrons to transfer through the electron donor and acceptor compartments of PI, resulting in the formation of CTCs between PI chains, such as Fig.71 shown.
[0624] In order to prove that CTCs are formed in PI during heat treatment, FTIR spectra of pristine PI and PI-350 were analyzed. FTIR spectra of PI ( Fig.72 a and 72b) show at 1778 cm -1 There is a band nearby, which is the asymmetric stretching of the C=O imide group. -1 The peak at 1367 cm-1 is attributed to the C=O symmetric stretching of the imide group. -1 The peak at 837 cm is attributed to the CN stretching of the imide group. These three peaks represent the stretching vibration of the imide group, proving the existence of PI material. -1 The peaks near are attributed to the vibration of the unsaturated π bond of the aromatic group of the benzene ring. The FTIR spectrum of PI-350 is shown in Fig.72 a, where the peaks corresponding to the symmetric C=O, asymmetric C=O and CN stretching in the imide group can be found at 1778, 1723 and 1362 cm -1 The presence of these peaks indicates that the chemical structure of PI is not affected by the thermal treatment process, confirming the thermal stability of PI. The results show that the polymer structure of PI can be retained during the thermal treatment process and can therefore serve as a binder for Si anode.
[0625] By comparing the FTIR spectra of PI and PI-350, the peaks associated with the C=O and CN bonds in the imide groups are shifted to lower wavenumbers. Without being limited by theory, it is speculated that this red-shift phenomenon is caused by the interaction between the intermolecular groups. It is speculated that for the PI-350 sample, under the influence of heat treatment, the molecular chains can be close enough to each other through cross-linking to form a CTC structure, such as Fig.71 Therefore, after heat treatment, the peak associated with the C=O bond in the imide group changes from 1730 cm -1 Move to 1723cm -1 ,like Fig.72 c. In addition, the peak associated with the CN bond in the imide group increases from 1367 cm -1 Move to 1362cm -1FTIR results indicate that CTC structures are formed between the molecular chains of PI during the thermal treatment, which can explain the observed differences between the properties of PI and PI-350 (Table 6). The presence of CTC structures can provide a greater packing density for the PI binder, thereby imparting mechanical properties that can improve the electrochemical performance of Si-PI electrodes.
[0626] Fig.73 The UV-visible spectrophotometer results of PI / NMP solution and PI-350 / NMP top are shown. Both samples are colorless and transparent due to the dissolution of PI and the sedimentation of PI-350 particles in NMP. No absorption was observed in the UV-visible spectrum of NMP. However, the UV-visible spectra of PI and PI-350 have broad absorption peaks at wavelengths of 229nm and 271nm, respectively. This peak is attributed to the conjugated carbonyl C=O of the benzene ring on the PI molecular chain. It can be observed that the absorption peak of PI-350 is narrower than that of PI and has shifted to a lower wavelength value, which may be related to the formation of CTCs between PI molecular chains. Therefore, it can be further confirmed that CTCs caused by cross-linking between PI molecular chains exist in PI-350.
[0627] PI materials with abundant carbonyl groups (C=O) in the imide ring can form strong hydrogen bonds with SiNPs using the hydroxyl groups (-OH) on their surface. Without being limited by theory, it is speculated that this allows the PI binder to bind relatively firmly to the SiNPs, thereby forming a relatively strong electrode, which may alleviate the Li + Volume expansion during insertion and extraction.
[0628] Surface characterization of SiN, PI, SI-PI, and Si-PI-350 was performed using FTIR and XPS. FTIR characterization was used to explore the interaction between Si active materials and PI binder, such as Fig.74 a and 74b. The schematic diagram of the hydrogen bond between SiNP and PI is shown in Fig.74 c. The FTIR spectra of Si-PI and Si-PI-350 can be characterized by the presence of -1 There are three characteristic peaks near the π, corresponding to the asymmetric stretching of C=O and the symmetric stretching of C=O and CN in the imide ring. Due to the presence of PI characteristic peaks, the FTIR spectra of Si-PI and Si-PI-350 confirm the existence of PI. In the FTIR spectrum of SiNP, as shown in Fig.74 As shown in a, the stretching peak related to the hydroxyl group (-OH) on the surface of the nanoparticles appears at 3739 cm -1 However, Fig.74This peak is absent in the FTIR spectrum of Si-PI-350 shown in a. Without being limited by theory, it is speculated that the –OH group on Si interacts with the C=O group of PI to form a hydrogen bond. In addition, the stretching peak corresponding to the C=O group in the PI imide ring moves from 1730 cm in the original PI to 1722 cm in Si-PI. -1 ,like Fig.74 b. The formation of hydrogen bonds may also cause 8cm -1 The wavenumber redshift.
[0629] Without being limited by theory, it is speculated that the hydrogen bonding between the surface of the Si active material and the binder can provide a more compact structure for the electrode, further enabling the electrode to maintain volume changes during cycling. On the other hand, in the spectrum of Si-PI-350, the peak associated with the vibration of the -OH group (which is not present in Si-PI) is at 3739 cm -1 This strategy can improve the electrochemical performance of the electrode, as discussed below.
[0630] The effect of heat treatment on the electrochemical performance of electrodes made of SiNPs and PI binder was evaluated. Electrodes were fabricated using SiNPs and PI as binder (Si@PI). The electrodes were then heat treated at different temperatures of 300, 350, and 400 °C in a flow of Ar-4% H2 to prepare Si@PI-300, Si@PI-350, and Si@PI-400 electrodes, respectively (see Fig.68 ). The lithium ion storage performance of the electrode was evaluated and the results are as follows Fig.75a -b as shown. Fig.75a Shows that at 200mA g -1 Cycling performance of electrodes recorded at current densities of 100, 200, 500, 1000, and 2000 mA g-1. Figure 75b As shown. Figure 75b For each cycle number, the order of the results from the highest specific capacity to the lowest specific capacity is Si@PI-350, Si@PI-400, Si@PI-300Si@PI. Table 7 summarizes the lithium ion storage performance of the electrodes.
[0631] according to Fig.75aThe specific charge capacities of Si@PI-400, Si@PI-350, Si@PI-300, Si@PI, and Si@PAA / CMC electrodes after 30 cycles were recorded at 1818, 2334, 1383, 737, and 182 mAh g, respectively. -1 . It can be observed that the electrodes made with PI binder show significantly improved cycling performance than those made with PAA / CMC binder. Without being bound by theory, this improvement may be due to the more favorable mechanical properties of PI, brought about by the benzene rings on the molecular chain, allowing the electrode to maintain its integrity during cycling. In addition, it is clear that the electrochemical performance of Si@PI-350 is better than that of some other electrodes. For example, the initial Coulombic efficiency of the Si@PI-350 electrode (88.57%) is the highest among the electrodes, while all PI-containing electrodes maintained a Coulombic efficiency of over 95% in the following cycles. According to Fig.75a And b, Si@PI-350 electrode shows greater specific capacity and rate capability in the electrode, which can be attributed to the structural changes that occur during the heat treatment, especially the formation of optimized CTC structure and hydrogen bonding between PI and SiNP. Without being limited to theory, these modifications can provide the electrode with higher mechanical properties, allowing to accommodate the volume expansion / contraction involved in the lithium ion insertion / deinsertion cycle, thus providing greater electrode integrity to the electrode during cycling.
[0632] Table 7. At 200mA g -1 Lithium ion storage performance of different electrodes after 30 cycles at a current density of .
[0633] electrode Initial Coulombic efficiency (%) <![CDATA[Initial specific capacity (mAh g -1 )]]> <![CDATA[Final specific capacity (mAh g -1 )]]> Si@PI-400 85.76 2628 1818 Si@PI-350 88.57 2894 2334 Si@PI-300 88.05 2557 1383 Si@PI 87.32 2278 737 Si@PAA / CMC 79.99 2344 176
[0634] like Fig.75a -b and Table 7, the cycling performance of the electrode was gradually improved by increasing the heat treatment temperature to 350 °C, where the peak of the electrochemical performance was recorded, showing a capacity of 2334 mAh g for the Si@PI-350 electrode after 30 cycles at 200 mA g-1. -1 By further increasing the heat treatment temperature to 400 °C, the lithium ion storage performance of the sample (Si@PI-400) decreases, which may be due to the damage of the CTC structure and hydrogen bonds at higher temperatures. Without being limited by theory, a suitable CTC structure can provide the electrode with relatively high toughness and improve its cycle stability and rate performance, such as Figure 75b It is worth noting that at 2000mA g -1 At a current density of 1.34 mAh g, after 25 cycles, Si@PI-350 (900 mAh g -1 ) has a reversible capacity greater than that of Si@PI-400 (713 mAh g -1)、Si@PI-300(569mAh g -1 ) and Si@PI (338mAh g -1 ). When the current density is reduced to 100 mA g -1 After 30 cycles, Si-PI@350 still showed 1898 mAh g -1 The high reversible capacity of PI confirms the robustness of the heat-treated PI adhesive. Fig.76 Shows that at 200mA g -1 Figure 2. Galvanostatic charge / discharge (GCD) curves of the Si@PI-350 electrode recorded at a constant current density of . It can be observed that there is a short plateau at around 1.23 V in the first discharge cycle, which is attributed to the formation of the solid electrolyte interface (SEI) layer. The subsequent charge / discharge curves show excellent consistency, indicating that the Si@PI-350 electrode has an ideal cycling performance.
[0635] In addition to the high-voltage plateau in the first discharge cycle, the galvanostatic charge-discharge (GCD) curves of the electrode also show the presence of a low-voltage broad plateau, which can be attributed to the reactivity of SiNPs in lithium-ion insertion / extraction events.
[0636] The effect of heat treatment on the electrochemical resistance of Si@PI electrodes was further investigated by performing electrochemical impedance spectroscopy (EIS) in the frequency range of 0.01-1000000 Hz with an AC amplitude of 5 mV. The EIS curves of Si@PI and Si@PI-350 electrodes are shown in Figure 2. Figure 77a As shown, the EIS curves of PI and PI-350 are as follows Figure 77b shown.
[0637] In the EIS curve, the semicircle observed in the high-frequency region may be related to the charge transfer resistance (R ct ). In addition, the oblique line in the low-frequency region is attributed to the lithium ion diffusion impedance (R s ). A smaller diameter of the semicircle corresponds to a smaller electron transfer resistance. Figure 77a and 77b The impedance values extracted from the heat-treated samples are shown in Table 8. ct This is mainly attributed to the formation of charge transfer complexes between the main molecular chains of PI and hydrogen bonds during the thermal treatment, thus providing a closer contact within SiNPs, conductive carbon, and PI binder.
[0638] Table 8. Impedance data extracted from the fits in Figures 77(a) and (b).
[0639] electrode <![CDATA[R s (Oh)]]> <![CDATA[R ct (Oh)]]> Si@PI 2.857 130.4 Si@PI-350 2.666 37.7
[0640] Electron microscopy of Si@PI and Si@PI-350 before cycling and after 20 lithium-ion insertion / extraction cycles further confirmed the more compact morphology of the heat-treated samples. Fig.78 ad show the SEM micrographs of Si@PI before cycling, Si@PI-350 before cycling, Si@PI after 20 cycles of lithium ion insertion / extraction, and Si@PI-350 after 20 cycles of lithium ion insertion / extraction, respectively.
[0641] After cycling, cracks of several microns in size can be observed on the surface of the Si@PI electrode, while no obvious cracks were found on the surface of the Si@Pi-350 electrode after cycling, maintaining the integrity of the electrode structure.
[0642] The electrochemical performance of the Si@PI-350 anode in terms of specific energy density was evaluated based on the reversible specific capacity and relative average charge potential of the electrode compared to a standard SHE reference for half-cells. + / Li) are 2334mAh g –1 and 0.53 V, the average potential (relative to SHE) of the electrode is 2.54 V, based on the relative potential of metallic lithium (-3.04 V vs. SHE). Therefore, at the 30th cycle, the specific energy density of the Si@PI-350 anode is calculated to be 5858 Wh kg -1 As shown in the figure, after 30 cycles, the Si@PI-350 electrode exhibited extremely high specific capacity and energy density, which were 2334 mAh g -1 and 5858Wh kg -1 , outperforming some other binders, including sodium carboxymethyl cellulose (CMC), sodium hyaluronate-epichlorohydrin (SH-ECH), polyimide, okra gum, carboxymethyl cellulose-cationic polyacrylamide (CMC-CPAM), and PI with carboxyl groups (PI-COOH). Compared with the complex synthetic methods commonly used to prepare binder systems, the preparation of the Si@PI-350 electrode system is relatively simple and easy to scale up. The experimental results presented here show that the implementation of a simple heat treatment step can greatly improve the Li+ / -capacity of the Si anode due to the formation of CTC structure and hydrogen bonding. + Embedding / extraction performance, thus providing a denser morphology structure for the electrode.
[0643] Example 38 - Preparation of SnO2-MoS2-TPA Nanostructures
[0644] 2.0 g MoS2 was mixed with 20.0 g clean waste PET flakes, 10.0 g SnCl2 and 50 g LiCl-KCl eutectic mixture. The mixture was transferred to an alumina crucible and heated in a resistance furnace at 5 °C min -1The samples were heated to various temperatures in the range of 400-600 °C at a heating rate of 1.5 % and the residence time at the highest temperature was 20 min. Then, the temperature was cooled to room temperature and the obtained materials were washed with deionized water to remove the soluble components of the product and then dried at 100 °C for 2 h.
[0645] Fig.79 The XRD patterns of the initial MoS2, as well as the products obtained at different temperatures, are shown, combined with the standard XRD patterns of MoS2, terephthalic acid, and SnO2. It can be observed that the material prepared at 400 °C ( Fig.79 b) mainly contains MoS2 and terephthalic acid. By increasing the temperature to 450℃ ( Fig.79 c), the amount of terephthalic acid increases, which is characterized by relatively stronger peaks of organic compounds in this sample compared to the sample prepared at 400 °C. At 500 °C, in addition to MoS2 and terephthalic acid, diffraction peaks related to SnO2 can also be observed, such as Fig.79 (d) At 600°C, the XRD peak corresponding to terephthalic acid disappears, as shown in Fig.79 (e) as shown.
[0646] Composite materials containing MoS2, SnO2 and C8H6O4 prepared at 500°C were used to prepare electrodes for storing lithium ions and were tested at 0.01-3.0V (vs Li + The electrodes were made of composite materials, conductive carbon (C45), PVDF with a mass ratio of 7:2:1, and NMP as solvent, and the obtained results were about 1.2 mg cm -2 According to the mass load. Fig.80 , the electrode is at 100mA g -1 After 10 cycles at a current density of , the charge capacity is 570 mAh g -1 , at 200mA g -1 After 20 cycles, the charging capacity is 518 mAh g -1 , at 500mA g -1 After 30 cycles, the charging capacity is 416 mAh g -1 , at 1000mA g -1 After 40 cycles, the charging capacity is 309mAh g -1 , at 2000mA g -1 After 50 cycles, the charging capacity is 183 mAh g -1 , at 5000mA g -1 After 60 cycles, the charging capacity is 55 mAh g -1 . The current density was restored to 100 mA g -1After that, the charge capacity recorded at the 71st cycle was 589 mAh g -1 The results demonstrate the high rate capability and specific capacity of the electrode.
[0647] Example 39 - Silicon Thermally Modified Polyimide-TPA Electrode for Lithium Ion Storage
[0648] The process described in Example 27 was repeated, except that the mixture used to make the slurry for coating on the copper foil contained Si nanoparticles: polyimide: nanostructured TPA: conductive carbon in a mass ratio of 5:2:2:1; and the heat treatment was performed at a target temperature of 250° C. The nanostructured TPA was obtained based on the process described in Example 21. Fig.81 It shows that at a current density of 200 mAh g -1 , the cycling performance of the electrodes on lithium obtained in a half-cell button cell configuration (2025 type) with a cut-off voltage of 0.01-1.5 V. The specific capacity values are determined according to the mass of silicon material used in the electrode. The first discharge and charge specific capacities are 4836 and 3225 mAh g -1 , the corresponding Coulombic efficiency is 66.7%. The second discharge and charge specific capacities are 3445 and 3253 mAh g -1 , indicating a Coulombic efficiency of 94.4%. The third discharge and recharge capacities were 3373 and 3256 mAh g, respectively. -1 , indicating a Coulombic efficiency of 96.5%. In addition, the third discharge and recharge capacities were 3373 and 3256 mAh g, respectively. -1 , indicating a Coulombic efficiency of 96.5%. In addition, the discharge and charge capacity values at cycle number 30 were 3132 and 3078 mAh g, respectively. -1 , corresponding to a Coulombic efficiency of 98.3%. The specific energy density of the electrode at the 30th cycle was evaluated to be 7818 Wh kg by considering an average charging voltage of 0.5 V. -1 .
[0649] Other Implementations
[0650] Although certain embodiments have been disclosed above, this disclosure is not limited to such embodiments.
[0651] For example, in certain embodiments, the depolymerizing agent may include an ionic liquid in addition to or in place of an inorganic salt. Examples of ionic liquids include [bmpy][Tf2N] and [BMIM][Tf2N] and imidazolium ionic liquids. Examples of cations in ionic liquids include 1-octyl-3-methylimidazolium ([OMIM]), 1-methylimidazolium ([MIM]), 1-ethyl-3-methylimidazolium ([EMIM]), 1,3-dimethylimidazolium ([M13IM]), 1-(2-hydroxyethyl)-3-methylimidazolium ([HOEMIm]), 1-ethyl-2,3-dimethylimidazolium ([EMMIM]), 1-butyl-3-methylimidazolium ([BMIM]), 1-hexyl-3-methylimidazolium ([HMIM]), 1,2,3-tri ... imidazolium ([MMMIM]), 1-decyl-3-methylimidazolium ([DMIM]), 1-allyl-3-butylimidazolium ([ABIM]), 1,2-dimethylimidazolium ([M12IM]), 1-butyl-2,3-dimethylimidazolium ([BMMIM]), 1-allyl-3-methylimidazolium ([AMIM]), 1-allyl-3-vinylimidazolium ([AVIM]), tetradecyltrihexylphosphine ([P66614]), N-ethylpyridine ([EPy]), and N-butylpyridine ([BPy]). Examples of anions in ionic liquids include bis(trifluoromethylsulfonyl)imide ([Tf2N]), bromide ([Br]), dicyandiamide ([DCA]), hexafluorophosphate ([PF6]), perchlorate ([ClO4]), toluenesulfonate ([TS]), acetate ([Ac]), chloride ([Cl]), glycinate ([Gly]), iodide ([I]), trifluoromethanesulfonate ([TFO]), imidate ([Pro]), alaninate ([Ala]), lysinate ([Lys]), dihydrogen phosphate ([H2PO4]), nitrate ([NO3]), serine ([Ser]), glutamate ([Glu]), hydrogen sulfate ([HSO4]), and tetrafluoroborate ([BF4]).
Claims
1. A composite, characterized in that: A nanostructured organic compound, comprising a plurality of molecules, the general molecular formula of which is C x O y H z , characterized in that: x is from 2 to 12; y is from 2 to 8; and z is from 2 to 14.
2. A complex comprising: Organic compounds; and metal-organic frameworks embedded in organic compounds.
3. A composite comprising: Organic compounds; and a crystalline metal oxide, wherein the organic compound is at least partially crystalline and the crystalline metal oxide is distributed within the organic compound.
4. The composite according to any one of claims 1 to 3, wherein The organic compound is a nanocrystal.
5. The composite according to any one of claims 1 to 4, wherein The composite includes crystalline domains with a size ranging from 1 nm to 100 nm.
6. The composite according to any one of claims 1 to 4, wherein The composite includes crystalline domains with a size ranging from 20 nm to 80 nm.
7. The composite according to any one of claims 1 to 4, wherein The composite comprises crystalline domains with a size of 30 nm to 70 nm.
8. The composite according to any one of claims 1 to 7, wherein The components of the composite have a maximum size of less than 100 nm in at least one dimension.
9. The composite according to any one of claims 1 to 7, wherein The components of the composite have a maximum size of less than 50 nm in at least one dimension.
10. The composite according to any one of claims 1 to 7, wherein The components of the composite have a maximum size of less than 10 nm in at least one dimension.
11. The composite according to any one of claims 1 to 7, wherein The components of the composite have a maximum size of less than 2 nm in at least one dimension.
12. The composite of claim 1, further comprising at least one of a metal oxide, a metal, a metal organic framework, a silicon-containing material, and a graphene-containing material embedded in the nanostructured organic compound.
13. The composite of claim 1 further comprising a crystalline metal oxide embedded within the nanostructured organic compound.
14. The composite according to claims 1 to 13, wherein: The composite has X-ray diffraction (XRD) peaks.
15. The composite according to claim 1, wherein The XRD peak 2θ (±0.2 degrees) value of the composite includes at least one selected from the group consisting of 16.99 degrees, 24.83 degrees and 27.54 degrees.
16. The composite according to claim 1, wherein The 2θ (±0.2 degrees) values of the XRD peak of the composite include at least two selected from the group consisting of 16.99 degrees, 24.83 degrees, and 27.54 degrees.
17. The composite according to claim 1, wherein The 2θ (±0.2 degrees) values of the XRD peaks of the composite include 16.99 degrees, 24.83 degrees, and 27.54 degrees.
18. The composite according to any one of claims 1 and 14-17, wherein The composite has an XRD pattern with characteristic peaks, as shown in FIG36d .
19. The composite according to claim 3 or 13, wherein: The crystalline metal oxide is uniformly distributed within the organic compound.
20. The composite according to claim 3 or 13, wherein: The composite has a first concentration of crystalline metal oxide in an interior region of the composite; The composite has a second concentration of crystalline metal oxide in a surface region of the composite; and The first concentration is greater than the second concentration.
21. The composite according to claim 20, wherein The first concentration is 1 wt.% to 95 wt.%.
22. The composite according to claim 20, wherein The first concentration is 5 wt.% to 80 wt.%.
23. The composite according to claim 20, wherein The first concentration is 10 wt.% to 70 wt.%.
24. The composite according to any one of claims 20 to 23, wherein The second concentration is 0.1 wt.% to 80 wt.%.
25. The composite according to any one of claims 20 to 23, wherein The second concentration is 1 wt.% to 70 wt.%.
26. The composite according to any one of claims 20 to 23, wherein The second concentration is 5 wt.% to 60 wt.%.
27. The composite according to any one of claims 3, 13 and 19-26, wherein The organic compound and the crystalline metal oxide are bonded by hydrogen bonding.
28. The complex according to any one of claims 1 to 27, wherein The composite includes nanoparticles with a size of 1 nm to 200 nm.
29. The complex according to any one of claims 1 to 27, wherein The composite includes nanoparticles with a size of 1 nm to 100 nm.
30. The complex according to any one of claims 1 to 27, wherein The composite forms particles having a size of 0.01 μm to 100 μm.
31. The complex according to any one of claims 1 to 27, wherein The composite forms particles having a size of 10 μm to 100 μm.
32. The complex according to claim 30 or 31, wherein The size of the nanoparticles ranges from 1 nm to 200 nm.
33. The composite according to any one of claims 30 to 32, wherein The plate-like particles have a size range of 1 nm to 1 μm.
34. The composite according to claim 33, wherein The size of the platelet-like nanoparticles ranges from 10 nm to 500 nm.
35. The complex according to claim 2 or 3, wherein The organic compound includes an amorphous phase.
36. The composite according to claim 2, wherein The organic compound is at least partially crystalline.
37. The complex according to claim 2 or 3, wherein The organic compound is crystalline.
38. The complex according to claim 2 or 3, wherein The organic compound has a nanostructure.
39. The complex according to claims 2-38, wherein The organic compound has the general molecular formula C x O y H z .
40. The composite of any one of claims 1, 39 and 420, wherein: x is from 2 to 12; y is from 2 to 8; z is from 2 to 14.
41. The complex of any one of claims 1, 39 and 420, wherein: x is 8; y is from 4 to 6; z is 4.
42. The complex according to any one of claims 1 to 41 and 420, wherein The organic compound includes at least one selected from the group consisting of terephthalic acid, terephthalate, dimethyl terephthalate, bis(2-hydroxyethyl)terephthalate, ethylene glycol, phthalic acid, isophthalic acid and isophthalic acid.
43. The complex according to any one of claims 1-41 and 420, wherein The organic compound includes terephthalic acid.
44. The composite according to claim 3, wherein The organic compound includes an amorphous crystal system.
45. The complex according to any one of claims 3, 13, 19-26 and 44, wherein The composite contains 1 weight percent (wt.%) to 99 wt.% of an organic compound.
46. The complex according to any one of claims 3, 13, 19-26 and 44, wherein The composite contains 5 wt. % to 95 wt. % of an organic compound.
47. The complex according to any one of claims 3, 13, 19-26 and 44, wherein The composite contains 10 wt. % to 90 wt. % of an organic compound.
48. The complex according to any one of claims 3, 13, 19-26 and 44-47, wherein The crystalline metal oxide includes crystalline metal oxide nanoparticles.
49. The complex according to any one of claims 3, 13, 19-26 and 44-48, wherein The composite comprises 1 wt. % to 95 wt. % of the crystalline metal oxide.
50. The complex according to any one of claims 3, 13, 19-26 and 44-48, wherein The composite comprises 5 wt. % to 90 wt. % of the crystalline metal oxide.
51. The complex according to any one of claims 3, 13, 19-26 and 44-48, wherein The composite comprises 10 wt. % to 85 wt. % of the crystalline metal oxide.
52. The complex according to any one of claims 3, 13, 19-26 and 44-51, wherein The crystalline metal oxide particle size is 1 nm to 100 nm.
53. The complex according to any one of claims 3, 13, 19-26 and 44-51, wherein The particle size of the crystalline metal oxide is 1 nm to 50 nm.
54. The complex according to any one of claims 3, 13, 19-26 and 44-51, wherein The particle size of the crystalline metal oxide is 1 nm to 10 nm.
55. The complex according to any one of claims 3, 13, 19-26 and 44-51, wherein The particle size of the crystalline metal oxide is 1 nm to 5 nm.
56. The complex according to any one of claims 3, 13, 19-26 and 44-55, wherein The crystalline metal oxide is at least one of tin (IV) oxide (SnO2), tin (II) oxide (SnO), zinc oxide (ZnO), zinc peroxide (ZnO2), calcium oxide, lithium oxide, potassium oxide, lead oxide and iron oxide.
57. The complex according to any one of claims 3, 13, 19-26 and 44-55, wherein Crystalline metal oxides include tin (IV) oxide (SnO2).
58. The complex according to any one of claims 3, 13, 19-26 and 44-57, wherein The crystalline metal oxide has a tetragonal crystal system.
59. The complex according to any one of claims 3, 13, 19-26 and 44-58, wherein The organic compound has an X-ray diffraction (XRD) peak, and the metal oxide crystal has an XRD peak.
60. The complex according to claim 59, wherein The 2θ (±0.2 degrees) value of the XRD peak of the organic compound includes at least one selected from the group consisting of 17.41°, 25.21°, and 27.95°.
61. The complex according to claim 59, wherein The 2θ (±0.2 degrees) value of the XRD peak of the organic compound includes at least two selected from the group consisting of 17.41°, 25.21°, and 27.95°.
62. The complex according to claim 59, wherein The 2θ (±0.2 degrees) values of the XRD peak of the organic compound include 17.41°, 25.21°, and 27.95° degrees.
63. The complex according to any one of claims 59 to 62, wherein The 2θ (±0.2 degrees) value of the XRD peak of the crystalline metal oxide includes at least one selected from the group consisting of 26.60°, 33.90°, 37.97°, 39.00°, 51.81°, 54.79°, 57.87°, 61.92°, 64.79°, 66.01°, 71.33°, 78.76°, 81.19°, 83.78° and 87.29°.
64. The composite of claims 59-62, wherein the 2θ (±0.2 degrees) values of the XRD peaks of the crystalline metal oxide include at least two selected from the group consisting of 26.60°, 33.90°, 37.97°, 39.00°, 51.81°, 54.79°, 57.87°, 61.92°, 64.79°, 66.01°, 71.33°, 78.76°, 81.19°, 83.78°, and 87.29° degrees.
65. The composite of claims 59-62, wherein the 2θ (±0.2 degrees) values of the XRD peaks of the crystalline metal oxide include at least three selected from the group consisting of 26.60°, 33.90°, 37.97°, 39.00°, 51.81°, 54.79°, 57.87°, 61.92°, 64.79°, 66.01°, 71.33°, 78.76°, 81.19°, 83.78°, and 87.29° degrees.
66. The composite of claims 59-62, wherein the 2θ (±0.2 degrees) values of the XRD peaks of the crystalline metal oxide include at least four selected from the group consisting of 26.60°, 33.90°, 37.97°, 39.00°, 51.81°, 54.79°, 57.87°, 61.92°, 64.79°, 66.01°, 71.33°, 78.76°, 81.19°, 83.78°, and 87.29° degrees.
67. The complex of claims 3, 13, 19-26 and 44-66, wherein The composite has an XRD pattern with characteristic peaks, as shown in Figure 6c.
68. The complex according to any one of claims 3, 13, 19-26 and 44-67, wherein According to a differential scanning calorimetry (DSC) thermogram, the composite has at least one endothermic peak, the highest temperature (±3° C.) of which is selected from the group consisting of 328° C., 461° C. and 528° C.
69. The complex according to any one of claims 3, 13, 19-26 and 44-67, wherein According to the DSC thermogram, the composite has at least two endothermic peaks, and the highest temperature (±3° C.) thereof is selected from the group consisting of 328° C., 461° C. and 528° C.
70. The complex according to any one of claims 3, 13, 19-26 and 44-67, wherein According to the DSC thermogram, the composite has endothermic peaks, and the highest temperatures (±3°C) include 328°C, 461°C and 528°C.
71. A compound according to any one of claims 3, 13, 19-26 and 44-70, wherein The composite has a DSC thermogram as shown in FIG11 .
72. The complex according to any one of claims 3, 13, 19-26 and 44-71, wherein The composite substantially has a thermogravimetric analysis (TGA) thermogram as shown in FIG. 11 .
73. The complex according to any one of claims 3, 13, 19-26 and 44-72, wherein The composite substantially has an X-ray photoelectron spectroscopy (XPS) spectrum as shown in FIG. 15e .
74. The complex according to any one of claims 3, 13, 19-26 and 44-73, wherein The surface area of the composite is 10 m2 / g (m 2 g -1 ) to 50m 2 g -1 .
75. The complex according to any one of claims 3, 13, 19-26 and 44-73, wherein The surface area of the composite is 15 m 2 g -1 Up to 30m 2 g -1 .
76. The complex according to any one of claims 3, 13, 19-26 and 44-73, wherein The specific surface area of the composite is 17 m 2 g -1 Up to 21m 2 g -1 .
77. The complex according to any one of claims 1 to 76, wherein The composite has a thermal conductivity of 5 Siemens per meter (Sm) at 6.3 MPa. -1 ) to 5000Sm -1 conductivity.
78. The complex according to any one of claims 1 to 76, wherein The composite has a strength of 100 Sm at 6.3 MPa. -1 Up to 1500Sm -1 conductivity.
79. The complex according to any one of claims 1 to 76, wherein The composite has a strength of 400Sm at 6.3MPa. -1 Up to 600Sm -1 conductivity.
80. The complex according to any one of claims 1 to 79, characterized in that Silicon-containing materials are also included.
81. The complex according to claim 80, wherein The silicon-containing material is embedded in the organic compound.
82. The complex according to claim 80 or 81, wherein The composite includes 0.1 wt % to 95 wt % of the silicon-containing material.
83. The complex according to claim 80 or 81, wherein The composite contains 5 wt.% to 90 wt.% of a silicon-containing material.
84. The composite according to claims 80 to 81, wherein The composite comprises 10 wt. % to 85 wt. % of a silicon-containing material.
85. The complex according to any one of claims 80 to 84, wherein The silicon-containing material includes elemental silicon.
86. The complex according to any one of claims 80 to 85, wherein The silicon-containing material includes nanoparticles.
87. The complex according to claim 86, wherein The particle size of the silicon-containing material nanoparticles ranges from 1 nanometer (nm) to 1000 nm.
88. The complex according to claim 86, wherein The particle size of the silicon-containing material nanoparticles ranges from 1 nanometer to 500 nanometers.
89. The complex according to claim 86, wherein The particle size of the silicon-containing material nanoparticles ranges from 1 nm to 20 nm.
90. The complex of claim 86, wherein The particle size of the nanoparticles of the silicon-containing material is from 1 nm to 5 nm.
91. The composite of any one of claims 1-90, further comprising graphene nanosheets.
92. The composite of any one of claims 3, 13, 19-26, and 44-76, further comprising graphene nanosheets, wherein: The graphene nanosheets cover at least a portion of the crystalline metal oxide.
93. The complex according to claim 91 or 92, wherein The composite contains 0.1 wt. % to 50 wt. % of graphene nanoplatelets.
94. The complex according to claim 91 or 92, wherein The composite contains 5 wt. % to 45 wt. % of graphene nanoplatelets.
95. The complex according to claim 91 or 92, wherein The composite contains 10 wt. % to 40 wt. % of graphene nanoplatelets.
96. The complex according to any one of claims 91 to 95, wherein Graphene nanosheets range in size from 1 nm to 5 μm.
97. The complex according to claim 96, wherein The size of the flakes ranges from 50 nm to 5 μm.
98. The complex of claim 96, wherein The size of the flakes ranges from 100 nm to 1 μm.
99. The complex according to any one of claims 91 to 98, wherein The number of layers of the graphene nanosheet ranges from 1 to 100.
100. The composite of claims 91-98, wherein the number of graphene nanosheets is from 1 to 50.
101. The composite of claims 91-98, wherein the number of graphene nanosheet layers ranges from 1 to 10.
102. The composite of any one of claims 91-101, wherein the graphene nanoplatelets have a carbon purity of at least 90%.
103. The composite of claims 91-101, wherein the graphene nanoplatelets have a carbon purity of at least 95%.
104. The complex according to any one of claims 91 to 103, wherein The graphene nanosheets include functional groups on their surfaces.
105. The composite of claim 104, wherein: The functional group includes at least one selected from the group consisting of a hydroxyl group, a carbonyl group, a carboxyl group, and an amino group.
106. The complex according to any one of claims 91-105, wherein The composite further includes a silicon-containing material, and the graphene nanosheets cover at least a portion of the silicon-containing material.
107. The composite of claim 1 or 3, further comprising a metal organic framework embedded in the organic compound.
108. The complex according to claim 2 or 107, wherein Metal-organic frameworks are partially crystalline.
109. The complex according to claim 2 or 107, wherein The metal organic framework is crystalline.
110. The complex according to claim 2 or 107, wherein The metal organic framework is a nanostructure.
111. The composite according to any one of claims 2 and 107-110, wherein The metal organic framework includes the organic compound and a metal.
112. The composite according to any one of claims 2 and 107-111, wherein The metal is one selected from the group consisting of Zn, Fe, Cu, Al, Zr, Cr, Co, Li, Na and K.
113. The composite according to any one of claims 2 and 107-111, wherein The metal is Zn.
114. The complex according to any one of claims 2 and 107-113, wherein The metal organic framework molecular formula is MC x H y O z nH2O, wherein M is a metal and n is 0 to 5.
115. The complex according to any one of claims 2 and 107-113, wherein The metal organic framework molecular formula is MC x H y Oz·nH2O, wherein M is a metal and n is 0, 1, 2 or 3.
5.
116. The complex according to any one of claims 2 and 107-113, wherein The metal organic framework molecular formula MC x H y O z ·3.5H2O, where M is a metal.
117. The composite of claims 2 and 107-113, wherein: The metal organic framework molecular formula is MC x H y O z , where M is a metal.
118. The complex of any one of claims 114-117, wherein: x is from 2 to 12; y is from 2 to 8; z is from 2 to 14.
119. The complex of claims 114-117, wherein: x is 8; y is 4; z is 4.
120. The composite according to any one of claims 2 and 107-119, wherein The metal organic framework comprises terephthalate.
121. The composite of claims 2 and 107-119, wherein The composite particle size is 500 nm to 700 μm.
122. The composite of claim 121, wherein The size of the plate-like particles ranges from 10 nm to 10 μm.
123. The composite of claim 122, wherein the thickness of the plate-like particles ranges from 1 nm to 10 nm.
124. The complex according to claim 122 or 123, wherein The plate-like particles include nanoparticles with a size of 1 nm to 60 nm.
125. The complex according to any one of claims 121-124, wherein The particles include agglomerated nanoparticles having a size of 1 nm to 60 nm.
126. The complex according to any one of claims 121-125, wherein The particles comprise metal organic framework crystals with a size range of 10 nm to 10 μm.
127. The complex according to any one of claims 2 and 107-126, wherein The average grain size of the MOFs is between 30 nm and 60 nm.
128. The complex according to any one of claims 2 and 107-127, wherein The 2θ (±0.2 degrees) value of the XRD peak of the composite includes at least one selected from the group consisting of 11.75 degrees, 14.74 degrees, 16.60 degrees, and 16.98 degrees.
129. The complex according to any one of claims 2 and 107-127, wherein The 2θ (±0.2 degrees) values of the XRD peak of the composite include at least two selected from the group consisting of 11.75 degrees, 14.74 degrees, 16.60 degrees, and 16.98 degrees.
130. The complex according to any one of claims 2 and 107-127, wherein The 2θ (±0.2 degrees) values of the XRD peaks of the composite include 11.75 degrees, 14.74 degrees, 16.60 degrees, and 16.98 degrees.
131. The complex according to any one of claims 2 and 107-130, wherein The composite has an XRD pattern with characteristic peaks, as shown in FIG60a .
132. The complex according to any one of claims 2 and 107-127, wherein The 2θ (±0.2 degrees) value of the XRD peak of the composite includes at least one selected from the group consisting of 9.89 degrees, 19.33 degrees, 25.27 degrees, and 40.11 degrees.
133. The complex according to any one of claims 2 and 107-127, wherein The 2θ (±0.2 degrees) values of the XRD peak of the composite include at least two selected from the group consisting of 9.89 degrees, 19.33 degrees, 25.27 degrees and 40.11 degrees.
134. The complex according to any one of claims 2 and 107-127, wherein The 2θ (±0.2 degrees) values of the XRD peaks of the composite include 9.89 degrees, 19.33 degrees, 25.27 degrees, and 40.11 degrees.
135. The complex according to any one of claims 2 and 107-127, wherein The 2θ (±0.2 degrees) value of the XRD peak of the composite includes at least one selected from the group consisting of 17.45 degrees, 25.27 degrees, 28.017 degrees, and 42.99 degrees.
136. The complex according to any one of claims 2 and 107-127, wherein The 2θ (±0.2 degrees) values of the XRD peak of the composite include at least two selected from the group consisting of 17.45 degrees, 25.27 degrees, 28.017 degrees, and 42.99 degrees.
137. The complex according to any one of claims 2 and 107-127, wherein The 2θ (±0.2 degrees) values of the XRD peaks of the composite include 17.45 degrees, 25.27 degrees, 28.017 degrees and 42.99 degrees.
138. The complex according to any one of claims 2, 107-127 and 132-137, wherein The composite has an XRD pattern with characteristic peaks, as shown in FIG60b .
139. The composite of any one of claims 1-138, comprising a tin-containing member consisting of metallic tin, tin chloride, tin chloride hydrate, tin hydroxide, and tin hydroxide oxide.
140. The complex of claim 139, wherein The particle size of the tin-containing member is 1 nm to 100 nm.
141. The complex according to claim 139 or 140, wherein The tin-containing member is at least partially crystalline.
142. The composite of claim 139 or 140, wherein the tin-containing member is crystalline.
143. The complex according to claim 139 or 140, wherein The tin-containing component has a nanostructure.
144. The complex of claim 139, wherein Tin hydroxide chloride chemical formula Sn 21 Cl 16 (OH) 14 O6.
145. The complex according to any one of claims 1 to 144, wherein The composite is a dark powder.
146. The complex according to any one of claims 1-144, wherein The composite is black powder.
147. The complex according to any one of claims 1 to 146, wherein The complex was present at a concentration of 0.5 g L -1 When the absorbance is at least 1 a.u. at 242 nm.
148. The complex according to any one of claims 1-146, wherein The complex was present at a concentration of 0.5 g L -1 When the absorbance is at least 1.5 au at 242 nm.
149. The complex according to any one of claims 1-148, wherein The complex was present at a concentration of 0.5 g L -1 When the absorbance is at least 0.4 au at 450 nm.
150. The complex of claims 1-149, wherein At a concentration of 0.5 g L -1 In this case, the complex has an absorbance of at least 0.4 au at 500 nm.
151. The complex of claims 1-150, wherein: At a concentration of 0.5 g L -1 In this case, the complex has an absorbance of at least 0.5 au at 317 nm.
152. Electrode, comprising: A complex according to any one of claims 1-151, 385-411 or 419-434.
153. Electrode, comprising: A complex according to any one of claims 3, 13, 19-26 and 44-76.
154. The electrode according to claims 152 and 153 further comprises at least one selected from the group consisting of conductive carbon, a binder, a copper foil and graphene nanosheets.
155. The electrode according to claim 154, wherein The adhesive includes polyimide.
156. An electrode according to any one of claims 152-155, wherein The electrode is at 200 mAg -1 After 500 cycles at a current density of 10 mAh g -1 ) to 1500mAh g -1 of lithium-ion discharge capacity.
157. An electrode according to any one of claims 152-155, wherein The electrode is at 200 mAg -1 After 500 cycles at a current density of 100 mAh g -1 Up to 1000mAh g -1 of lithium-ion discharge capacity.
158. An electrode according to any one of claims 152-155, wherein The electrode is at 200 mAg -1 After 500 cycles at a current density of 200 mAh g -1 Up to 800mAh g -1 of lithium-ion discharge capacity.
159. An electrode according to any one of claims 152-158, wherein The electrodes had a coulombic efficiency of 70% to 120% after 500 cycles.
160. The electrode of any one of claims 152-158, wherein The electrodes had a coulombic efficiency of 80% to 110% after 500 cycles.
161. An electrode according to any one of claims 152-158, wherein The electrodes had a Coulombic efficiency of 90% to 100% after 500 cycles.
162. An electrode according to any one of claims 152-161, wherein After 150 cycles, the electrolyte resistance of the half-cell made of the electrode increased from 1.0Ω to 6.0Ω.
163. An electrode according to any one of claims 152-161, wherein After 150 cycles, the electrolyte resistance of the half-cell made of the electrode increased from 2.0Ω to 5.0Ω.
164. An electrode according to any one of claims 152-161, wherein After 150 cycles, the electrolyte resistance of the half-cell made of the electrode increased from 3.0Ω to 4.0Ω.
165. An electrode according to any one of claims 152-164, wherein After 300 cycles, the electrolyte resistance of the half-cell made of the electrode increased from 2.0Ω to 8.0Ω.
166. An electrode according to any one of claims 152-164, wherein After 300 cycles, the electrolyte resistance of the half-cell made of the electrode increased from 2.0Ω to 7.0Ω.
167. An electrode according to any one of claims 152-164, wherein After 300 cycles, the electrolyte resistance of the electrode increased from 3.0Ω to 6.0Ω.
168. An electrode according to any one of claims 152-167, wherein The electrode has a change from 10 to 150 cycles. -11 cm 2 s -1 Up to 9×10 -9 cm 2 s -1 The lithium ion diffusion coefficient.
169. The electrode according to any one of claims 152-167, wherein After 150 cycles, the electrode has a -11 cm 2 s -1 Up to 5×10 -9 cm 2 s -1 The lithium ion diffusion coefficient.
170. An electrode according to any one of claims 152-167, wherein After 150 cycles, the electrode has a -11 cm 2 s -1 Up to 10 -9 cm 2 s -1 The lithium ion diffusion coefficient.
171. An electrode according to any one of claims 152-170, wherein After 300 cycles, the electrode has a -11 cm 2 s -1 Up to 10 -8 cm 2 s -1 The lithium ion diffusion coefficient.
172. The electrode according to any one of claims 152-170, wherein After 300 cycles, the electrode has a -11 cm 2 s -1 Up to 7×10 -9 cm 2 s -1 The lithium ion diffusion coefficient.
173. An electrode according to any one of claims 152-170, wherein The electrode has 10 -10 cm 2 s -1 Up to 9×10 -9 cm 2 s -1 The lithium ion diffusion coefficient.
174. An electrode according to any one of claims 152-173, wherein The electrode is at 100 mAg -1 After 10 cycles at a current density of 300 mAh g -1 Up to 1500mAh g -1 of lithium-ion discharge capacity.
175. An electrode according to any one of claims 152-174, characterized in that The electrode is at a current density of 500 mAg -1 After 30 cycles at a current density of 200 mAh g -1 Up to 1500mAh g -1 of lithium-ion discharge capacity.
176. An electrode according to any one of claims 152-175, characterized in that The electrode is at 1000mAg -1 After 50 cycles at a current density of 200 mAh g -1 Up to 1500mAh g -1 of lithium-ion discharge capacity.
177. An electrode according to any one of claims 152-176, wherein The electrode is at 5000mAg -1 After 60 cycles at a current density of 50 mAh g -1 Up to 1300mAh g -1 of lithium-ion discharge capacity.
178. An electrode according to any one of claims 152-177, wherein Na + The voltage of the ion insertion electrode is 0.1V to 0.9V relative to Na / Na + Reference electrode.
179. An electrode according to any one of claims 152-177, wherein The voltage of Na-ion insertion electrode is 0.15V to 0.8V (vs Na / Na + ).
180. The electrode according to any one of claims 152-177, wherein Na + The voltage of the ion insertion electrode is 0.17V to 0.3V (vs Na / Na + ).
181. An electrode according to any one of claims 152-180, wherein Na + The ion release voltage from the electrode is between 0.3V and 0.7V (vs Na / Na + ).
182. The electrode according to any one of claims 152-180, wherein Na + Ion extraction from the electrode occurs at a voltage between 0.4 V and 0.6 V (vs Na / Na + ).
183. An electrode according to any one of claims 152-182, wherein The lithium ion discharge capacity of the electrode after 500 cycles increased from 100 mAh g -1 Up to 1800mAh g -1 .
184. The electrode according to any one of claims 153, wherein The electrodes have a lithium ion discharge capacity ranging from 100 milliamp hours (mAh) per gram of crystalline metal oxide to 1800 mAh per gram of crystalline metal oxide after 500 cycles.
185. The electrode according to claim 153, wherein The electrodes have a lithium ion discharge capacity of from 200 mAh per gram of crystalline metal oxide to 1800 mAh per gram of crystalline metal oxide after 500 cycles.
186. The electrode according to claim 153, wherein The electrodes have a lithium ion discharge capacity of from 500 mAh per gram of crystalline metal oxide to 1800 mAh per gram of crystalline metal oxide after 500 cycles.
187. Batteries, including: An electrode according to any one of claims 152-186.
188. The battery of claim 187, wherein The electrode is an anode.
189. A battery according to claim 187 or 188, further comprising a cathode.
190. The battery of claim 189, further comprising an electrolyte between the anode and the cathode.
191. The battery of claim 189 or 190, further comprising an electrical connection between the anode and the cathode.
192. A battery according to any one of claims 187-191, characterized in that The batteries are selected from lithium-ion batteries, sodium-ion batteries, calcium-ion batteries and potassium-ion batteries.
193. A motor vehicle, comprising: A battery according to any one of claims 187-192.
194. A structure, characterized in that include: A battery according to any one of claims 187-192.
195. A system capable of generating electricity, wherein: The system is configured to be in electrical contact with the battery of any one of claims 187-192.
196. The system of claim 195, wherein: The system includes at least one selected from the group consisting of a system capable of generating electricity from electromagnetic radiation, a system capable of generating electricity from rotation of a turbine, and a system capable of generating electricity from a combustion reaction.
197. The system of claim 196, wherein: The system includes at least one selected from the group consisting of photovoltaic, wind turbine, hydroelectric generator, hydroelectric power station, nuclear power station, coal-fired power plant, oil-fired power plant and gas-fired power plant.
198. The system of any one of claims 195-197, wherein: The battery is configured to store electrical energy generated by the power production system.
199. A method comprises: treating the composite of any one of claims 1-151 and 385-387 into a first solution constituting a first concentration of a contaminant; and reducing the concentration of the contaminant in the first solution to form a second solution, Wherein, the concentration of pollutants in the second solution is lower than the concentration of pollutants in the first solution.
200. The method of claim 199, wherein: At least a portion of the contaminants in the first solution are adsorbed onto the surface of the composite.
201. The method according to claim 199 or 200, wherein: The composite photocatalytically degrades at least a portion of the pollutants in the first solution.
202. The method according to claim 201, wherein: Reducing the concentration of contaminants in the first solution further comprises exposing the first solution to visible light.
203. The method of any one of claims 199-202, wherein: The pollutant includes one selected from the group consisting of hydrocarbons, azo dyes and xanthate-based compounds.
204. A method comprising: heating a mixture comprising a first polymer, a second polymer, and a depolymerizing agent to a first temperature; depolymerizing the first polymer to form an organic compound; and Formation of complexes containing organic compounds, Wherein, the second polymer does not undergo substantial depolymerization.
205. The method according to claim 204, wherein: The first polymer is a polymer that is capable of depolymerizing in the presence of water.
206. The method of claim 204 or 205, wherein: The first polymer includes at least one selected from the group consisting of polyethylene terephthalate (PET), polystyrene, polyvinyl chloride, nylon, polyurethane, phenolic resin, and epoxy resin.
207. The method according to any one of claims 204-206, wherein: The second polymer includes at least one selected from the group consisting of polyethylene and polypropylene.
208. The method of any one of claims 204-207, further comprising separating the complex from the second polymer.
209. A method comprising: heating a mixture comprising reactants to a first temperature; and forming a composite comprising a nanocrystalline organic compound, Wherein, the reactants include a polymer and a depolymerizing agent.
210. The method of claim 209, wherein: The reactants also include molten salt, and the mixture is heated to convert the molten salt into a molten salt.
211. A method comprising: heating a mixture comprising reactants to a first temperature; and forming a composite comprising an organic compound and a crystalline metal oxide, in: Organic compounds are at least partially crystalline; The reactants include a molten salt, a polymer, and a depolymerizing agent; and Heat the salt to make it molten.
212. The method according to any one of claims 209-211, wherein: Heating the mixture depolymerizes the polymer to generate monomers, and the monomers further form organic compounds.
213. The method according to any one of claims 209-212, wherein: The reactants contain from 1 wt.% to 99 wt.% of polymer.
214. The method of any one of claims 209-212, wherein: The reactants contain 5 wt.% to 95 wt.% of polymer.
215. The method of any one of claims 209-212, wherein: The reactants contain 10 wt.% to 90 wt.% of polymer.
216. The method of any one of claims 209-215, wherein: The polymer includes at least one of the following components: polyethylene terephthalate (PET), polyacrylonitrile, poly(6-aminocaproic acid), polycaprolactam, nylon, polyetheretherketone (PEEK), poly(ethylene) (PE), poly(adipamide), poly(methyl methacrylate), poly(methylene oxide), poly(4-methylpentene), poly(propylene), poly(styrene), poly(trans-1,4-butadiene), poly(vinyl alcohol), poly(vinyl chloride) (PVC), poly(vinyl fluoride), poly(vinylidene chloride) and poly(vinylidene fluoride).
217. The method according to any one of claims 209-215, wherein: The polymer includes polyethylene terephthalate (PET).
218. The method according to any one of claims 209-217, wherein: The polymer is derived from waste plastics.
219. The method of any one of claims 209-218, wherein: The difference in melting temperatures between the polymer and the depolymerizing agent is less than 100°C.
220. The method of any one of claims 209-218, wherein: The difference in melting temperatures between the polymer and the depolymerizing agent is less than 75°C.
221. The method of any one of claims 209-218, wherein: The difference in melting temperatures between the polymer and the depolymerizing agent is less than 50°C.
222. The method according to any one of claims 209-221, wherein: The reactants contain 1 wt.% to 95 wt.% of a depolymerizing agent.
223. The method of any one of claims 209-221, wherein: The reactants contain 5 wt.% to 90 wt.% of a depolymerizing agent.
224. The method of any one of claims 209-221, wherein: The reactants contain 10 wt.% to 85 wt.% of a depolymerizing agent.
225. The method of any one of claims 209-224, wherein: The depolymerizing agent includes an inorganic salt.
226. The method according to claim 211, wherein: The inorganic salt comprises the metal of the crystalline metal oxide.
227. According to the method of claim 211 or 226, the inorganic salt undergoes an oxidation reaction during heating.
228. The method according to any one of claims 211-227, wherein: The depolymerizing agent includes at least one selected from the group consisting of tin (II) chloride (SnCl2), zinc chloride (ZnCl2), calcium chloride (CaCl2), lead chloride (PbCl2), sodium chloride (NaCl), potassium chloride (KCl) and ferric chloride (FeCl2).
229. The method of any one of claims 211-227, wherein: The depolymerizing agent includes tin(II) chloride (SnCl2).
230. The method of any one of claims 211-227, wherein: The depolymerizing agent includes zinc chloride (ZnCl2).
231. The method according to any one of claims 211-225, wherein: The depolymerizing agent includes an ionic liquid.
232. The method according to claim 231, wherein: The ionic liquid comprises at least one selected from the group consisting of [BMPY][Tf2N], [BMIM][Tf2N] and imidazolium ionic liquids.
233. The method according to claim 231, wherein: The ionic liquid comprises a cation selected from 1-octyl-3-methyl-imidazolium ([OMIM]), 1-methyl-imidazolium ([MIM]), 1-ethyl-3-methyl-imidazolium ([EMIM]), 1,3-dimethyl-imidazolium ([M13IM]), 1-(2-hydroxyethyl)-3-methylimidazolium ([HOEMIm]), 1-ethyl-2,3-dimethylimidazolium ([EMMIM]), 1-butyl-3-methylimidazolium ([BMIM]), 1-hexyl-3 1-HMIM), 1,2,3-trimethylimidazolium ([MMMIM]), 1-decyl-3-methylimidazolium ([DMIM]), 1-allyl-3-butylimidazolium ([ABIM]), 1,2-dimethylimidazolium ([M12IM]), 1-butyl-2,3-dimethylimidazolium ([BMMIM]), 1-allyl-3-methylimidazolium ([AMIM]), 1-allyl-3-vinylimidazolium ([AVIM]), tetradecyltrihexylphosphine ([P 66614 ]), N-ethylpyridine ([EPy]) and N-butylpyridine ([BPy]).
234. The method according to claim 231, wherein: The ionic liquid comprises an anion selected from the group consisting of bis(trifluoromethylsulfonyl)imide ([Tf2N]), bromide ([Br]), dicyandiamide ([DCA]), hexafluorophosphate ([PF6]), perchlorate ([ClO4]), toluenesulfonate ([TS]), acetate ([Ac]), chloride ([Cl]), glycine ester ([Gly]), iodide ([I]), trifluoromethanesulfonate ([TFO]), linolenate ([Pro]), alanine ester ([Ala]), lysine ester ([Lys]), dihydrogen phosphate ([H2PO4]), nitrate ([NO3]), serine ester ([Ser]), glutamate ([Glu]), hydrogen sulfate ([HSO4]) and tetrafluoroborate ([BF4]).
235. The method according to claim 210 or 211, wherein: Such salts include chloride salts.
236. The method according to any one of claims 210-211 and 235, wherein The salt includes at least one selected from the group consisting of LiCl and KCl.
237. The method of any one of claims 210-211 and 235-236, wherein the salt comprises LiCl and KCl.
238. The method of any one of claims 210-211 and 235-237, wherein the salt comprises 40 wt. % LiCl to 80 wt. % LiCl.
239. The method of any one of claims 210-211 and 235-237, wherein: The chemical composition of the salt contains 50 wt. % LiCl to 70 wt. % LiCl.
240. The method of any one of claims 210-211 and 235-237, wherein: The salt contains 55 wt. % LiCl to 65 wt. % LiCl.
241. The method of any one of claims 210-211 and 235-241, wherein the salt comprises 20 wt.% KCl to 70 wt.% KCl.
242. The method of any one of claims 210-211 and 235-241, wherein the salt comprises 30 wt.% KCl to 55 wt.% KCl.
243. The method of any one of claims 210-211 and 235-241, wherein the salt comprises 35 wt.% KCl to 40 wt.% KCl.
244. The method of any one of claims 210-211 and 235-243, wherein: The melting point of salt is 250°C to 700°C.
245. The method of any one of claims 210-211 and 235-243, wherein: The melting point of salt is 300°C to 600°C.
246. The method of any one of claims 210-211 and 235-243, wherein: The melting point of salt is 320°C to 500°C.
247. The method of any one of claims 209-246, wherein: The heating is performed under an atmosphere selected from the group consisting of air, nitrogen, argon and hydrogen.
248. The method of any one of claims 209-246, wherein: The heating is performed under air.
249. The method of any one of claims 209-246, wherein: The heating is performed under an inert atmosphere.
250. The method of any one of claims 209-246, wherein: The heating was performed under argon.
251. The method of any one of claims 209-246, wherein: The heating was carried out under argon and hydrogen.
252. The method of any one of claims 209-246, wherein: The heating is carried out under argon gas and a gas containing 1% to 99% hydrogen.
253. The method of any one of claims 209-252, wherein: The heating is performed at a temperature higher than the melting point of the polymer and the melting point of the depolymerizing agent.
254. The method of any one of claims 210-211 and 235-246, wherein: The heating is performed at a temperature higher than the melting point of the polymer, the melting point of the salt and the melting point of the depolymerizing agent.
255. The method of any one of claims 209-254, wherein: The heating is performed at a temperature lower than the carbonization temperature of the polymer and the decomposition temperature of the organic compound.
256. The method of claim 210 or 211, wherein: The first temperature is 200°C to 600°C.
257. The method of any one of claims 210 or 211, wherein: The first temperature is 600°C at most.
258. The method of any one of claims 209-255, wherein: The first temperature range is 200°C to 450°C.
259. The method of any one of claims 209-255, wherein: The first temperature is at least 250°C.
260. The method of any one of claims 209-255, wherein: The first temperature is at least 300°C.
261. The method of any one of claims 209-255, wherein: The first temperature is at most 500°C.
262. The method of any one of claims 209-255, wherein: The first temperature is at most 400°C.
263. The method of any one of claims 209-255, wherein: The first temperature is at most 310°C.
264. The method of any one of claims 209-263, wherein: The feed mixture is maintained at the first temperature for 0.01 minute to 120 minutes.
265. The method of any one of claims 209-263, wherein: The feed mixture is maintained at the first temperature for 1 minute to 60 minutes.
266. The method of any one of claims 209-263, wherein: The feed mixture is maintained at the first temperature for 5 minutes to 30 minutes.
267. The method of any one of claims 209-263, wherein: The feed mixture was held at the first temperature for 1 second.
268. The method of any one of claims 209-267, wherein: The raw material mixture was heated to 1°C min -1 To 100℃min -1 Heating rate.
269. The method of any one of claims 209-267, wherein: The raw material mixture was heated at 2℃ min -1 To 50℃min -1 Heating rate.
270. The method of any one of claims 209-267, wherein: The mixture was heated at 3°C min -1 To 20℃min -1 Heating rate.
271. The method of any one of claims 209-270, further comprising contacting the complex with a solvent.
272. The method of claim 271, wherein: The solvent includes at least one selected from the group consisting of an aqueous solution, an alkaline aqueous solution, an acidic aqueous solution and a polar organic liquid.
273. The method of claim 271 or 272, wherein: The pH value of the solvent is 0.1 to 7.
274. The method of claim 271 or 272, wherein: The pH value of the solvent is 1 to 6.
275. The method of claims 271 to 272, wherein: The pH value of the solvent is 2 to 5.
276. The method of any one of claims 271-275, wherein: The solvent includes an acid selected from the group consisting of hydrochloric acid, sulfuric acid, nitric acid and phosphoric acid.
277. The method of claim 276, wherein: The concentration of the acid in the solvent is 1 vol.% (volume %) to 98 vol.%.
278. The method of claim 276, wherein: The concentration of the acid in the solvent ranges from 2 vol.% to 95 vol.%.
279. The method of claim 276, wherein: The concentration of the acid in the solvent ranges from 5 vol.% to 90 vol.%.
280. The method of claim 271 or 272, wherein: The pH range of the solvent is 7 to 14.
281. The method of claim 271 or 272, wherein: The pH range of the solvent is 8 to 13.
282. The method of claim 271 or 272, wherein: The pH range of the solvent is 9 to 12.
283. The method of any one of claims 271-272 and 280-282, wherein: The solvent includes a hydroxide.
284. The method of claim 283, wherein: The hydroxide is derived from sodium hydroxide and potassium hydroxide.
285. The method of claim 271 or 272, wherein: The polar organic liquid comprises ethanol.
286. The method of any one of claims 271-285, wherein: The complex includes the deaggregation agent, and the mixture is contacted with the solvent to remove at least a portion of the deaggregation agent.
287. The method of any one of claims 271-285, wherein: The complex includes a depolymerizing agent, and contacting the complex with the solvent can hydrolyze at least a portion of the depolymerizing agent.
288. The method of claim 287, wherein: The depolymerizing agent includes SnCl2; The hydrolysis of SnCl2 forms a second material composed of tin, chlorine, hydrogen, and oxygen; and The contacting forms a reaction product comprising the composite and the second material dispersed within the organic compound of the composite.
289. The method of claim 288, wherein: The second material includes tin hydroxide chloride.
290. The method of claim 288 or 289, wherein: The second material includes Sn 21 Cl 16 (OH) 14 O6.
291. The method of any one of claims 288-290, wherein: The second material is at least partially crystalline.
292. The method of any one of claims 271-291, further comprising separating the complex from the solvent.
293. The method according to claim 292, wherein: Separation steps include vacuum filtration and centrifugation methods.
294. The method of claim 292 or 293, further comprising drying the complex after separating the complex.
295. The method of claim 294, wherein: The composite is dried in an atmosphere selected from the group consisting of air, an inert atmosphere, and a vacuum.
296. The method of claim 294 or 295, wherein: The composite is dried at a temperature between -196°C and 100°C.
297. The method of claim 294 or 295, wherein: The composite was dried at a temperature between -196°C and 0°C.
298. The method of claim 294 or 295, wherein: The composite is dried at a temperature of 20°C to 100°C.
299. The method of any one of claims 271-298, wherein: The solvent includes a precursor of the silicon-containing material, and the composite is contacted with the solvent to introduce the silicon-containing material into the composite.
300. The method of any one of claims 209-298, wherein: The mixture also includes a precursor of the silicon-containing material, and the composite also includes the silicon-containing material.
301. The method of claim 300, wherein the reactants comprise 0.1 wt.% to 98 wt.% of a precursor of the silicon-containing material.
302. The method of claim 300, wherein the reactants comprise 5 wt.% to 90 wt.% of a precursor of the silicon-containing material.
303. The method of claim 300, wherein the reactants comprise 10 wt.% to 85 wt.% of a precursor of the silicon-containing material.
304. The method of any one of claims 299-303, wherein: The precursor of the silicon-containing material includes nanoparticles.
305. The method of any one of claims 299-304, wherein: The precursor of the silicon-containing material includes at least one selected from the group consisting of elemental silicon, Ca2Si, Ca5Si3, CaSi, Ca3Si4, CaSi2 and Mg2Si.
306. The method of any one of claims 299-305, wherein: The particle size of the silicon-containing material precursor ranges from 1 nm to 1000 nm.
307. The method of any one of claims 299-305, wherein: The particle size of the precursor of the silicon-containing material ranges from 1 nm to 500 nm.
308. The method of any one of claims 299-305, wherein: The particle size of the silicon-containing material precursor ranges from 1 nm to 20 nm.
309. The method of any one of claims 299-305, wherein: The particle size of the silicon-containing material precursor ranges from 1 nm to 5 nm.
310. The method of any one of claims 299-309, wherein: The precursor of the silicon-containing material includes surface functional groups.
311. The method of any one of claims 299-310, further comprising ball milling the precursor of the silicon-containing material.
312. The method according to claim 311, wherein: The ball milling is performed in the presence of a solvent.
313. The method of claim 312, wherein: The solvent includes n-hexane.
314. The method of any one of claims 271-299, wherein: The solvent includes graphene nanosheets, and the composite is contacted with the solvent to introduce the graphene nanosheets into the composite.
315. The method of any one of claims 209-313, wherein: The mixture further includes graphene nanoplatelets, and the composite further includes graphene nanoplatelets.
316. The method according to claim 315, wherein: The mixture includes 0.1 wt. % to 80 wt. % of graphene nanoplatelets.
317. The method of claim 315, wherein: The composite contains 2 wt. % to 45 wt. % of graphene nanoplatelets.
318. The method of claim 315, wherein: The composite contains 5 wt. % to 40 wt. % of graphene nanoplatelets.
319. The method of any one of claims 314-318, wherein: The graphene nanosheets have a size range from 1 nm to 5 μm.
320. The method of claim 319, wherein: The flake sizes range from 50 nm to 5 μm.
321. The method of claim 319, wherein: The flake sizes range from 100 nm to 1 μm.
322. The method of any one of claims 314-321, wherein: The number of layers of the graphene nanosheet ranges from 1 to 100.
323. The method of any one of claims 314-321, wherein: The number of layers of the graphene nanosheet ranges from 1 to 50.
324. The method of any one of claims 314-321, wherein: The number of layers of the graphene nanosheet ranges from 1 to 10.
325. The method of any one of claims 314-324, wherein: The graphene nanosheets have a carbon purity of at least 90%.
326. The method of any one of claims 314-324, wherein: The graphene nanosheets have a carbon purity of at least 95%.
327. The method of any one of claims 314-326, wherein: The surface of the graphene nanosheet contains functional groups.
328. The method of claim 327, wherein: The functional group includes at least one selected from the group consisting of a hydroxyl group, a carbonyl group, a carboxyl group, and an amino group.
329. The method of any one of claims 314-328, wherein: The graphene nanosheets are prepared by cathode electrochemical stripping of a graphite electrode.
330. The method of claim 329, wherein: Cathodic electrochemical stripping was performed in a molten salt electrolyte.
331. The method of claim 330, wherein: The molten salt includes at least one of a system consisting of lithium chloride and sodium chloride.
332. The method of any one of claims 329-331, wherein: Cathodic electrochemical stripping is carried out in the temperature range of 500°C to 900°C.
333. The method of claim 211, wherein the organic compound comprises an amorphous phase.
334. The method of claim 211, wherein the organic compound is crystalline.
335. The method of claim 211, wherein the organic compound has a nanostructure.
336. The method of any one of claims 209-335, wherein: The organic compound has the molecular formula C x O y H z .
337. The method according to claim 336, characterized in that: x is from 2 to 12; y is from 2 to 8; and z is from 2 to 14.
338. The method according to claim 336, characterized in that: x is 8; y is from 4 to 6; and z is 4.
339. The method of any one of claims 209-338, wherein: The organic compound includes at least one selected from the group consisting of terephthalic acid, terephthalate, dimethyl terephthalate, bis(2-hydroxyethyl)terephthalate, ethylene glycol, phthalic acid, isophthalic acid and isophthalic acid.
340. The method of any one of claims 209-338, wherein: The organic compound includes terephthalic acid.
341. The method of claim 340, wherein: Terephthalic acid has a nanostructure, with at least one dimension being less than 100 nanometers.
342. The method of any one of claims 209-341, wherein: The heating is carried out at a pressure of 0.01 to 100 atmospheres.
343. A method according to any one of claims 209-341, wherein: The heating is carried out at a pressure of 0.1 to 10 atmospheres.
344. The method of any one of claims 209-341, wherein: The heating is carried out at a pressure of 0.5 to 5 atmospheres.
345. The method of any one of claims 209-341, wherein: The heating is carried out at a pressure of 0.8 to 1.5 atmospheres.
346. The method of any one of claims 209-341, wherein: The heating is carried out at atmospheric pressure.
347. The method of any one of claims 209-346, further comprising: forming a suspension comprising the composite and graphene nanosheets; The suspension was subjected to ultrasonic treatment; The product was collected from the suspension, Wherein, the product includes the composite and the graphene nanosheet.
348. The method of claim 347, wherein: The suspension also includes an acid.
349. The method of claim 347 or 348, wherein: The product contains 50 wt.% to 99.9 wt.% of the complex.
350. The method of any one of claims 347-349, wherein: The product contains 0.1 wt.% to 50 wt.% of graphene nanoplatelets.
351. The method of any one of claims 209-351, wherein: The reactants also include water.
352. The method of any one of claims 209-351, wherein at least a portion of the depolymerizing agent has hydrating properties.
353. The method of any one of claims 209-351, wherein: The deagglomerating agent is hydrated.
354. The method of any one of claims 209-353, wherein: The deagglomeration agent contains 0.1 wt. % to 20 wt. % of water.
355. The method of any one of claims 209-354, further comprising: removing at least a portion of the complex; and Add additional polymer.
356. The method of any one of claims 209-355, wherein: The composite also includes a metal organic framework embedded in the organic compound.
357. A method according to claim 356, wherein: The metal organic framework includes the organic compound and the metal.
358. The method of claim 356 or 357, wherein: The metal is selected from Zn, Fe, Cu, Al, Zr, Cr, Co, Li, Na and K.
359. The method of claim 356 or 357, wherein: The metal is Zn.
360. The method of any one of claims 356-359, wherein: The metal organic framework molecular formula is MC x H y O z nH2O, where M is a metal and n ranges from 0 to 5.
361. The method of any one of claims 356-359, wherein: The metal organic framework molecular formula is MC x H y O z nH2O, wherein M is a metal and n is 0, 1, 2 or 3.
5.
362. The method of any one of claims 356-359, wherein: The metal organic framework molecular formula is MC x H y Oz·3.5H2O, where M is a metal.
363. The method of any one of claims 356-359, wherein: The metal organic framework molecular formula is MC x H y O z , where M is a metal.
364. The method according to any one of claims 360-363, characterized in that: x is from 2 to 12; y is from 2 to 8; and z is from 2 to 14.
365. The method according to any one of claims 360-363, characterized in that: x is 8; y is 4; and z is 4.
366. The method of any one of claims 356-363, wherein: The metal organic framework comprises terephthalate.
367. The method of any one of claims 356-366, wherein: The metal organic framework includes hydration water; and The method further comprises The composite is heated to a second temperature, in: The heating removes at least a portion of the water of hydration from the metal organic framework.
368. The method of claim 367, wherein: The metal organic framework comprises a first crystal structure before being heated to the second temperature, and the metal organic framework comprises a second crystal structure after being heated to the second temperature, wherein the second crystal structure is different from the first crystal structure.
369. The method of claim 367 or 368, wherein: The second temperature range is 50°C to 400°C.
370. The method of any one of claims 367-369, wherein: The composite is maintained at the second temperature for a period ranging from 1 millisecond to 10 hours.
371. The method of any one of claims 209-370, further comprising cooling the mixture after heating the mixture.
372. The method of claim 371, wherein: The cooling step is performed in the same atmosphere as that of the heating step.
373. The method of any one of claims 209-372, wherein: The complex comprises a complex according to any one of claims 1-151.
374. The method of any one of claims 209-373, wherein the reactants do not contain any acid, base or enzyme.
375. The method of any one of claims 209-270, wherein: The method does not involve a separation step.
376. The method of any one of claims 209-375, wherein: The heating forms a second organic compound, and the second organic compound is evaporated.
377. The method of claim 376, wherein: The second organic compound is ethylene glycol.
378. The method of claim 209, wherein: The composite consists of nanostructured organic compounds.
379. The method of claim 209, wherein: The composite consists of nanostructured terephthalic acid.
380. The method of claim 209, further comprising reacting the complex with a metal hydroxide to form a reaction product comprising the complex and the metal of the hydroxide, The longest reaction time was 18 hours.
381. The method of claim 380, wherein: The molecular formula of the product includes Na2C8H4O4, Li2C8H4O4, K2C8H4O4 or ZnC8H6O4.
382. The method of claim 380 or 381, wherein: The reaction was allowed to proceed for a maximum of 12 hours.
383. The method of claim 380 or 381, wherein: The reaction was allowed to proceed for a maximum of 6 hours.
384. The method of any one of claims 380-383, wherein: The hydroxide is selected from NaOH, LiOH, KOH and Zn(OH)2.
385. The composite of claim 1 further comprising a metal embedded in the organic compound.
386. The complex of claim 385, wherein: The metal is one of Na, Li, K and Zn.
387. The complex of claim 385 or 386, wherein The molecular formula of the complex includes Na2C8H4O4, Li2C8H4O4, K2C8H4O4 or ZnC8H6O4.
388. The complex of claim 1, wherein: The composite consists of nanostructured organic compounds.
389. The complex of claim 1, wherein: The composite consists of nanostructured terephthalic acid.
390. The complex of any one of claims 1-151 or 385-387, wherein The complex includes a transition metal disulfide.
391. The complex of claim 390, wherein: Transition metal dichalcogenides have the molecular formula MX2, where M is a transition metal atom and X is a chalcogen atom.
392. A complex according to claim 391, wherein M comprises Mo or W.
393. A complex according to claim 391 or 392, wherein the sulfur atoms include S, Se and Te.
394. The complex of any one of claims 390-393, wherein The transition metal disulfide includes a two-dimensional transition metal disulfide.
395. The complex of any one of claims 390-394, wherein Transition metal dichalcogenides are embedded in organic compounds.
396. The complex of any one of claims 390-395, wherein: The composite includes metal oxide crystals; and Transition metal dichalcogenides are embedded in metal oxide crystals.
397. The complex of any one of claims 1-151, 385-387, and 390-396, further comprising a polymer.
398. The complex of claim 397, wherein: The composite also includes a silicon-containing material.
399. The complex of claim 397 or 398, wherein The polymer is prepared from monomers, and at least a portion of the monomers are cross-linked to each other.
400. The complex of claim 399, wherein: The monomers include imide monomers.
401. The complex of any one of claims 398-400, wherein A portion of the material and a portion of the polymer are bonded by hydrogen bonding.
402. The complex of any one of claims 398-401, wherein The material includes silicon particles embedded within the organic compound.
403. The complex of any one of claims 398-402, wherein The material includes silicon particles.
404. The complex of claim 403, wherein: The size of the silicon particles ranges from 1 nm to 5 μm, optionally from 10 nm to 1 μm, optionally from 20 nm to 500 nm, optionally from 20 nm to 200 μm.
405. The complex of any one of claims 397-404, wherein The polymer comprises polyimide.
406. A composite according to any one of claims 398-405, wherein Based on the mass of silicon in the material, at a current density of 200mAg -1 The lithium ion storage capacity of the composite is 1000 mAh g -1 , after 30 cycles, it reaches 3500mAh g -1 .
407. A composite according to any one of claims 398-406, wherein At 200mAg -1 At a current density of 1.3 %, the specific energy density of the composite lithium storage was 3000 Wh kg in the first 30 cycles. -1 Up to 8000Wh kg -1 .
408. The complex of any one of claims 398-407, wherein The lithium ion diffusion resistance of the composite material is 10Ω to 60Ω, and optionally ranges from 20Ω to 40Ω.
409. The complex of any one of claims 398-408, wherein The infrared spectrum of the polymer is at 1723 cm -1 There are peaks at 1362cm and / or -1 There are peaks everywhere.
410. The complex of any one of claims 398-409, wherein The infrared spectrum of the complex is at 3739 cm -1 There are no peaks.
411. The complex of any one of claims 398-410, wherein The polymer is a polyimide.
412. The method of any one of claims 209-383, wherein: The reactants and complexes include transition metal disulfides.
413. The method of claim 412, wherein: The transition metal disulfide has a molecular formula of MX2, wherein M is a transition metal atom and X is a chalcogen atom.
414. The method of claim 413, wherein M comprises Mo or W.
415. The method of claim 413 or 414, wherein the sulfide atoms include S, Se and Te.
416. The method of any one of claims 412-415, wherein: The transition metal disulfide includes a two-dimensional transition metal disulfide.
417. The method of any one of claims 412-416, wherein: The transition metal disulfide is intercalated into the organic compound.
418. The method according to any one of claims 412-417, characterized in that: The composite includes a crystalline metal oxide; and Transition metal dichalcogenides are embedded in metal oxide crystals.
419. A composite comprising: Materials containing silicon; and A polymer made from imide monomers, Among them, a portion of the imide monomers are cross-linked, and a portion of the material and a portion of the polymer are bonded by hydrogen bonds.
420. A composite, characterized in that: polymer; and An organic compound consisting of multiple molecules with the formula C x O y H z ,in: Organic compounds have a crystalline structure; x is from 2 to 12; y is from 2 to 8; and z is from 2 to 14.
421. The complex of claim 420, wherein: The composite also includes a silicon-containing material.
422. The complex of claim 420 or claim 421, wherein Polymers are made from monomers, and at least some of the monomers are cross-linked to each other.
423. The complex of any one of claims 419-422, wherein The monomers include imide monomers.
424. The complex of any one of claims 419-423, wherein A portion of the material and a portion of the polymer are bonded to each other through hydrogen bonds.
425. The complex of any one of claims 420-422, wherein The material includes silicon particles embedded in the organic compound.
426. The complex of any one of claims 420-424, wherein The material includes silicon particles.
427. The complex of claim 426, wherein: The size of the silicon particles ranges from 1 nm to 5 μm, optionally from 10 nm to 1 μm, optionally from 20 nm to 500 nm, optionally from 20 nm to 200 nm.
428. The complex of any one of claims 420-422 and 425, wherein The crystalline organic compound has a nanostructure and nanocrystals.
429. The complex of any one of claims 419-428, wherein Based on the mass of silicon in the material, at a current density of 200mAg -1 When the lithium storage capacity of the composite is 1000 mAh g -1 , after 30 cycles it is 3500mAhg -1 .
430. The complex of any one of claims 419-429, wherein At 200mAg -1 At the current density of -1 Up to 8000Wh kg -1 .
431. The complex of any one of claims 419-430, wherein The lithium ion diffusion resistance of the composite is from 10Ω to 60Ω, and optionally from 20Ω to 40Ω.
432. The complex of any one of claims 419-431, wherein The infrared spectrum of the polymer is at 1723 cm -1 There are peaks at 1362cm and / or -1 There are peaks everywhere.
433. The complex of any one of claims 419-432, wherein The infrared spectrum of the complex is at 3739 cm -1 There are no peaks.
434. The complex of any one of claims 419-433, wherein The polymer is a polyimide.
435. A method for preparing a composite according to any one of claims 419-434, characterized in that: The mixture feedstock containing the polymer is heated to a temperature ranging from 150°C to 400°C.
436. The method of claim 435, wherein the heating time comprises 1 second to 5 hours.
437. The method of claim 435 or claim 436, wherein: The heating is carried out in an inert atmosphere or a nitrogen atmosphere.
438. The method of any one of claims 435-437, wherein: The hydrogen content of the gas used ranges from 0.1% to 99.9%.